Oceanic redox evolution in an early Cambrian intrashelf basin, South China - Yuyue Han; Meng Cheng; Jianbo Chen; Thomas J. Algeo; Bo Ran; Mengchun Cao; Zihu Zhang; Haiyang Wang; Dasheng Zhao; Tao Dong; Feng Wang; Taiping Huang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Spatially variable carbon transport pathways in a volcanic and geothermal environment, Menengai Caldera, Kenya - Emmanuel Turinimana; James D. Muirhead; Tsung-Han J. Yang; Christine Kiptoo; Gerd Sielfeld; Patrick Kariuki; Nicholas Mariita; Isaac Kanda; Nicolas Muli; Paul Kiprono; Julie V. Rowland; Luitgard Schwendenmann; et al. (Journal of Volcanology and Geothermal Research, 2026)

Imported virtual water is physically scarcer than domestic water globally - Han Su; Oleksandr Mialyk; Rick J. Hogeboom; Markus Berger (Water Research, 2026)

Clinical outcomes of patients with brain metastases from primary esophageal cancer - Bianca Nolde-Lopez; Christina K. Cramer; Scott Isom; Anthony Naquin; Caio M.S.P. Rocha Lima; Ravi K. Paluri; Jimmy Ruiz; Fei Xing; Christopher T. Whitlow; Stephen B. Tatter; Adrian W. Laxton; Jaclyn J. White; et al. (Next Research, 2026)

Detection of seizurogenic compounds in human and rat neurons in vitro: A multi-laboratory, multi-model assessment - Ruth Roberts; Ksenia Blinova; Coby Carlson; Matthew Cato; Katherine Czysz; Tromondae K. Feaster; Xiaobo Han; Yuto Ishibashi; Yasunari Kanda; Mohamed Kreir; Paul Levesque; Norimasa Miyamoto; et al. (NeuroToxicology, 2026)

Linking ambient fire emissions to respiratory effects using gelatin filter sampling - Olivia C.G. Lampe; Tate J. Matthews; Akshat Verma; Bowie P. Lam; Eva C.M. Vitucci; Carolyn L. Cannon; Arum Han; Shankararaman Chellam; Natalie M. Johnson (Journal of Hazardous Materials, 2026)

Probabilistic seismic hazard assessment for Taiwan: Updates and improvements in TEM PSHA2025 - Jia-Cian Gao; Jo-Chen Kao; Chung-Han Chan; Ray Y. Chuang; Cheng-Hung Chen; J. Bruce H. Shyu; Kuo-En Ching; Yu Wang; Kuo-Fong Ma (Engineering Geology, 2026)

Examination of DNAm PhenoAge as an epigenetic biomarker for perioperative risk in adult spinal deformity surgeries - Michael P. Kelly; Jeffrey Hills; Justin S. Smith; Lawrence G. Lenke; Han Jo Kim; Shay Bess; Breton Line; Virginie Lafage; Renaud Lafage; Eric Klineberg; Ferran Pellise; Khaled Kebaish; et al. (GeroScience, 2026)

Targeting Mitochondrial Dysfunction in Acute Organophosphate Toxicity: A Preliminary Evaluation of Cyclosporine A - David H. Jang; Jarelis Cabrera; Jonathan Starr; Abigail Insana; Angela N. Viaene; John C. Greenwood; Frances S. Shofer; Johannes K. Ehinger; Shih-Han Kao; Todd J. Kilbaugh (Journal of Medical Toxicology, 2026)
Background Organophosphate (OP) compounds are widely used agricultural chemicals that pose significant public health and chemical threat concerns due to their neurotoxic effects. Although OP toxicity has classically been attributed to acetylcholinesterase inhibition and cholinergic crisis, emerging evidence suggests mitochondrial dysfunction may represent an additional and clinically relevant mechanism of injury. Experimental OP exposure has been associated with impaired electron transport chain activity, reduced ATP production, increased oxidative stress, and disruption of mitochondrial membrane integrity. However, there are currently no established mitochondrial-targeted therapies for OP poisoning. Diisopropyl fluorophosphate (DFP), a well-established OP surrogate, reproduces several neurologic and mitochondrial features of nerve agent exposure. Cyclosporine A (CsA), an inhibitor of the mitochondrial permeability transition pore (mPTP), may represent a potential mitochondrial-targeted intervention. Methods This preliminary translational study employed both in vitro and in vivo models to evaluate mitochondrial respiratory dysfunction following acute DFP exposure and to explore the feasibility of mitochondrial-targeted treatment paradigms using CsA. Human donor-derived peripheral blood mononuclear cells (PBMCs) were used for DFP and CsA dose-finding and mitochondrial respiratory characterization using high-resolution respirometry (Oroboros O2k) with standardized substrate–uncoupler–inhibitor titration (SUIT) protocols. In parallel, a non-survivor Sprague–Dawley rat model of acute DFP exposure was developed incorporating invasive hemodynamic monitoring, controlled ventilation, venous blood gas analysis, and CsA treatment paradigms administered either following DFP exposure or as pretreatment prior to exposure. Brain cortical homogenates were prepared for ex vivo respiratory assessment. Results Preliminary findings demonstrated that DFP exposure was descriptively associated with impaired mitochondrial respiration across multiple oxidative phosphorylation (OXPHOS)- and electron transport system (ETS)-linked respiratory states in both PBMC and rodent models. DFP exposure was additionally associated with physiologic and metabolic derangements, including acidosis and elevated lactate concentrations. Post-DFP CsA administration was associated with partial preservation of mitochondrial respiration across several respiratory states, while the Pre-DFP CsA group demonstrated respiratory profiles more closely approximating control values in select OXPHOS- and ETS-linked states, accompanied by relatively preserved physiologic and metabolic parameters. Conclusions These preliminary findings support the feasibility of integrating mitochondrial respiratory phenotyping into translational models of acute OP toxicity and further support investigation of mitochondrial-targeted strategies in OP-associated mitochondrial dysfunction. The observed respiratory and physiologic trends associated with CsA exposure, particularly in the pretreatment paradigm, provide an exploratory foundation for future preclinical studies evaluating mitochondrial-directed countermeasures in OP poisoning.

A comparative analysis of regulatory frameworks and their market impacts on health functional foods: perspectives from South Korea, Canada, the United States, and China - Da-Eun Min; Dal Eum Han; Kwonsoo Kang; Ke Ding; Guangpeng Xu; Mi-Young Lee; Dong Sung An; Nayon Hur; Jin Man Kim; Ji Youn Hong; Bok Kyung Han; Martin J. T. Reaney; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Present-Day Sea Level Variations in Coastal Areas from Daily to Multidecadal Time Scales: Observations and Causes - A. Cazenave; R. Almar; P. Almeida; N. K. Ayoub; J. H. Bettencourt; F. Birol; W. Han; M. Herrmann; S. Jevrejeva; L. Leclercq; F. Niño; J. Oelsmann; et al. (Surveys in Geophysics, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Development of a multi-criteria indicator for product life cycle decision-making - Yong Han Kim; Sidi Deng; Thomas Maani; Matthew J. Triebe; Nehika Mathur; John W. Sutherland (Journal of Cleaner Production, 2026)

Eight recommendations to enhance biodiversity outcomes of nature-based solutions at multiple scales - Charles B. van Rees; Collin VanBuren; Lori A. Han; Andrew Altieri; Matt Bilskie; James E. Byers; Jon Calabria; Matthew L. Chambers; Daniel J. Coleman; Katie Foster; Aliza Leit; Alec Nelson; et al. (Journal of Environmental Management, 2026)

Variable silicate weathering and enhanced reverse weathering during the Ordovician-Silurian transition - Xiangrong Yang; Detian Yan; Denglin Han; David J. Wilson; Philip A.E. Pogge von Strandmann; Xianyi Liu; Chun-Yao Liu; Ke Xu; Can Chen; Mu Liu; Daizhao Chen (Geochimica et Cosmochimica Acta, 2026)

Microalgae concentration system for early harmful algae bloom detection using inertial microfluidic focusing - Dohyun Park; Marina Nichols; Qinmin Zheng; William J. Jeang; Andrew J. Whittle; Jongyoon Han (Bioresource Technology, 2026)

Phylogeography of ‘tropical Daphnia ’ — Diaphanosoma dubium : Refugia, Lineage Divergence, and Historical Colonization Over a Warm and Complex Landscape in East Asia - Ping Liu; Meng Xu; Qi Huang; Henri J. Dumont; Diego Fontaneto; Bo‐Ping Han (Journal of Biogeography, 2026)
Aim East Asia spans temperate to tropical zones, with limited glacial influence and a complex geological history shaped by the Tibetan Plateau. Consequently, species here may show distinct phylogeographic patterns compared with those of Europe and North America. Using the warm‐adapted cladoceran Diaphanosoma dubium as a model, we tested whether it persisted in multiple watershed refugia, especially the Yangtze River Basin, during past climate oscillations, leading to geographically structured lineage divergence. Location East Asia, with a specific focus on watersheds across China. Taxon The cyclically parthenogenetic cladoceran Diaphanosoma dubium (‘tropical Daphnia ’). Methods We applied ecological niche modelling on a global occurrence dataset and population genetics analyses on mitochondrial and nuclear gene datasets from 60 populations. Results High‐fitness areas were identified mainly in the eastern Yellow River Basin plains during the Last Glacial Maximum (LGM). Phylogenetic analysis resolved five deep lineages coalescing in the Late Miocene. Ancestral cold‐adapted lineages dominated the Yellow River Basin in the Late Miocene, later dispersing and permeating southward into the Yangtze River Basin during pre‐Pleistocene cooling. Three deep lineages indicated a large refugium downstream of the Yellow River Basin and west of the Bohai Gulf, and two lineages indicated two cryptic southern refugia. The two most common lineages overlapped widely in China, expanding post‐LGM from the Paleo‐Bohai refugium, showing climate tracking and niche conservatism. Main Conclusion In contrast to our expectation, the Yangtze River Basin acted as a dispersal hub rather than a refugium in middle China. D. dubium exhibited a watershed‐associated latitudinal structure, distinct from Daphnia in Europe. Historical north‐to‐south colonization and strong gene flow mitigated genetic differentiation among watersheds. Life‐history traits drove D. dubium 's successful colonization of tropical China, with geographic range and mountainous landscapes further shaping its continental‐scale distribution and divergence.

Using life-history information to identify management priorities within an emergent multi-species grey mullet fishery - Calum J. Pritchard; Ayşegül Tuğçe Han; Andrew Macleod; Rachel M. Turnbull; Jamie Small; Sarah Birchenough; Simon Pengelly; Benjamin J. Ciotti (Fisheries Research, 2026)

Dopaminergic expression and the regulation of foraging in response to water stress - J. Frances Kamhi; Dajia Ye; Jason Chen; Han Lam Do; Corinne W. Marble; Jonathan Starcke; Ignacio Arganda-Carreras; Deborah M. Gordon (Journal of Insect Physiology, 2026)

Eelgrass (Zostera marina) can tolerate salinity fluctuations - Katrin Rehlmeyer; Dindi Hiddink Verberne; Ellis J. Weinberg; Wilhelmina F. van Dorp; Maite L. Vogel; Oscar Franken; Hans van Veen; Han Olff; Tjisse van der Heide; Laura L. Govers (Journal of Experimental Marine Biology and Ecology, 2026)

Extraction and characterization of bioactive oligosaccharides from pulse processing byproducts using subcritical water extraction: a proof-of-concept study - Jasmin S. Yang; T. Truc K. Pham; Andrea J.C. Tam; Han Peng; Tássia B. Pessato; You-Tae Kim; Peter J. Russell; Zhiliang Fan; David A. Mills; Daniela Barile; Juliana Maria Leite Nobrega de Moura Bell (Food Chemistry, 2026)

Food structure-mediated stomach-brain neural signaling controls gastric emptying - Hongi Shi; Peter J. Wilde; Heng Yu; Jianzhong Han; Weilin Liu (Critical Reviews in Food Science and Nutrition, 2026)

Erratum to “Validation of bearing capacity methods for working platforms with test and numerical data” [Transp. Geotech. 60 (2026) 101986] - S. Demirdogen; J. Han (Transportation Geotechnics, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Drinking Water Hardness (as a Proxy for Calcium) Significantly Modifies the Relationship Between Dental Caries Prevalence in 5 Year Old Children and Drinking Water Fluoride and Socio-economic Inequalities in England - Mohammad Mehrabi; Yang Han; Deborah Moore; Matthew J. Ascott; Anne-Marie Glenny; David A. Polya (Exposure and Health, 2026)
Dental caries (DC) is the most prevalent chronic disease. Previous studies have revealed negative associations between DC prevalence and both drinking water fluoride concentration (F) and socioeconomic status but further predictors, notably drinking water calcium, have been little explored, particularly in the UK. Therefore, this study employed multiple linear regression (MLR) to model the dependency of children’s DC on all three of these predictors, namely (i) F, (ii) IMD: index of multiple deprivation, and (iii) WH: water hardness—as a proxy for calcium concentration; in England. The results showed that all three predictors are statistically significantly (p < 0.05) associated with DC, with, separately, increased fluoride, increased water hardness, and decreased deprivation being associated with lower DC. A key novel finding is that the DC ~ F relationship is quantitatively less pronounced (by about 24%) when WH is included as a predictor—thus the oral health and financial benefits of water fluoridation based on models not considering water calcium may overestimate or underestimate those benefits depending upon water calcium (or WH as a proxy). Moreover, segmented analyses showed that, potentially and partially due to WH’s influence, the DC ~ F relationship is dependent upon F concentration, with the dependence much stronger for drinking water F < 0.10 mg/L than for F > 0.37 mg/L, a concentration considerably lower than the widely reported optimal F, i.e., (0.7–1.0) mg/L. Any modelling of expected costs and benefits for fluoridation should explicitly include consideration of water calcium (or WH as proxy) and the non-first-order linear DC ~ F relationship.

Stewardship Behaviour Among Residents of the Great Barrier Reef Region and the Role of Self-Efficacy - Jane Dousset; Matthew I. Curnock; Ju-Han Zoe Wang; Tracy Schultz; Angela J. Dean (Environmental Management, 2026)
As the Great Barrier Reef (GBR, the Reef) faces unprecedented threats, reducing anthropogenic pressures and fostering stewardship within coastal communities are among the strategic priorities identified in the Australian and Queensland Government’s Reef 2050 Long-Term Sustainability Plan. While research indicates that Australians have limited awareness of reef stewardship actions, few studies have specifically examined patterns and enablers of stewardship in reef communities. To address this gap, we surveyed residents of the GBR region ( n = 2317) to examine (i) the types and prevalence of Reef stewardship actions amongst Reef residents (ii) the role of self-efficacy (i.e. an individual’s confidence in their own ability to achieve an outcome) in shaping stewardship behaviour on the GBR and (iii) factors that influence self-efficacy in relation to Reef-protection. We found that many residents report they perform stewardship actions related to pollution, like beach cleanups, with few respondents identifying actions related to climate mitigation. Analysis examining how factors shape stewardship and self-efficacy revealed a complex pattern of findings. On one hand, factors such as feeling a moral obligation to act supported stewardship engagement and self-efficacy. In contrast, being satisfied with reef management was associated with lower rates of stewardship and self-efficacy. These findings suggest a potential trade-off in perceptions of personal and institutional responsibility for action, and highlight the need promote narratives of shared responsibility when promoting stewardship.

Improved methods for determining maximum horizontal stress from borehole breakout - Yanhui Han; Khaqan Khan; Tameem M. Almani; Murtadha J. AlTammar; Osman Hamid (Computational Geosciences, 2026)

Emerging Viruses in Decapod Crustaceans: A Global Review - Xuan Dong; Guohao Wang; Kejun Wang; Kaisong Zhang; Hua Xu; Liying Wang; Xuan Li; Liang Qiu; Win Surachetpong; Jing Wang; Jee Eun Han; Kathy F. J. Tang; et al. (Reviews in Aquaculture, 2026)
Due to its advantages of a short production cycle, wide market demand, and profitability, decapod crustacean aquaculture has become one of the fastest‐growing food production systems. However, disease outbreaks have become one of the most important factors limiting the sustainability of decapod crustaceans. This review synthesizes current advancements in the understanding of emerging viral pathogens in decapod crustacean aquaculture, with emphasis on their genomic‐based taxonomical classification, susceptible hosts, global distribution, clinical manifestations, pathogenic mechanisms, diagnostic developments, and management strategies. This paper summarizes details of emerging viruses with confirmed pathogenicity (such as decapod iridescent virus 1), as well as viruses with uncertain or yet‐unconfirmed pathogenic roles. In addition, we highlight the role of next‐generation sequencing in virus discovery and examine the challenges posed by coinfection with other microorganisms. This review provides information to help the decapod crustacean aquaculture industry in setting up early warning systems to prevent the introduction of emerging pathogens into the production systems.

Validation of bearing capacity methods for working platforms with test and numerical data - S. Demirdogen; J. Han (Transportation Geotechnics, 2026)

Dose-dependent cerebral metabolic impairment in a swine model of carbon monoxide poisoning - Alistair Lewis; Rodrigo M. Forti; Tiffany S. Ko; John C. Greenwood; Matthew Kelly; Frances S. Shofer; Shih-Han Kao; Samuel S. Shin; Devesh Bungatavula; Mckenna Mason; Jonathan Starr; Johannes K. Ehinger; et al. (NeuroToxicology, 2026)

Modifying the digestion behavior of soy-based milk alternatives through calcium-mediated gastric structuring - Davood Zaeim; Weilin Liu; Jianzhong Han; Peter J. Wilde (Food Hydrocolloids, 2026)

Evaluation for the machine learning based PM2.5 estimation using different spatial resolution of geostationary satellite AOD over megacities in Korea - Juhee Lee; Jhoon Kim; Yeseul Cho; Seoyoung Lee; Drew C. Pendergrass; Daniel J. Jacob; Hyunkwang Lim; Hahn Chul Jung; Kwang-Min Myung; Young-Doh Kim; Kyung Man Han; Ja-Ho Koo (Atmospheric Environment, 2026)

Seismic Precursors to Shear Failure of Dry and Saturated Rock Fractures - Kyungsoo Han; Laura J. Pyrak-Nolte; Antonio Bobet (Rock Mechanics and Rock Engineering, 2026)

Non‐Correlated Variation of Leaf and Fine Root Traits in Subtropical Forest Plants - Yuzhi Zhu; Meng Li; Junyong Zheng; Yongqiang Wang; Yanghang Ren; Han Zhang; Zeyu Feng; Sandy P. Harrison; I. Colin Prentice; Yue Zhang; Lewei Jin; Shuang Sun; et al. (Ecology Letters, 2026)
Plants employ multiple strategies to adapt to their growth environment. Characterizing key dimensions in plant trait space is important for understanding functional diversity within ecosystems. Leaf and root functional traits have been studied in the context of resource economics, but whether they covary, and through which mechanisms, is still debated. We investigated this in subtropical forests by sampling root and leaf traits on individuals of co‐existing species in two communities with different resource availability. We found largely non‐correlated variation between leaf and fine root traits both across and within communities, and a clear decoupling between leaf economic spectrum and root economic space, independent of evolutionary history. Our results suggest that leaf‐root trait relationships are shaped by an interplay between microenvironmental heterogeneity that drives decoupling and shared selection pressures promoting covariation. The interplay explains the weak observed coordination and highlights the importance of environmental context in predicting above‐ and below‐ground plant functions.

Analysis of Helium Monte Carlo Data for the ISS-CREAM Instrument - A. Bagga; S. Aggarwal; Y. Amare; D. Angelaszek; D.P. Bowman; Y.C. Chen; G.H. Choi; M. Copley; L. Derome; Z.M. Dorris; L. Eraud; J.H. Han; et al. (Advances in Space Research, 2026)

Tailored surface sulfur modification of nano-scale zero-valent iron reduces microbial toxicity and enhances compatibility with organohalide-respiring bacteria for chlorinated solvent detoxification - Feilong Gao; Jinting Liu; Han Wu; Wenzhu Zhang; Matthew J. Rogers; Jingchun Tang; Jianzhong He; Guofang Xu (Journal of Hazardous Materials, 2026)

Combined benefits of multi-hazard early warnings on human mobility resilience to tropical cyclones - Haiyan Liu; Jianghao Wang; Zhifeng Cheng; Siqin Wang; Laurence Hawker; Jiatong Han; Phil J. Ashworth; Steve Darby; Faith Ka Shun Chan; Jian Liu; Andrew J. Tatem; Shengjie Lai (Global Environmental Change, 2026)

Laboratory observations of long wave inundation of shorelines in the shadow of islands - John T. Goertz; Nikos Kalligeris; Sunghoon Han; James M. Kaihatu; Patrick J. Lynett; Costas E. Synolakis (Coastal Engineering, 2026)

Impacts of climate and land-use change on ecosystem services in the agro-pastoral ecotone of western Liaoning - Y. Li; D. Ye; X. Han; S. Xia; J. Jin; X. Jiang; L. Lv (International Journal of Environmental Science and Technology, 2026)

The mechanism and performance of new CoFe2O4/MoS2/MIL-101(Fe) activated peroxymonosulfate for efficient degradation of tetracycline - C. Zhang; X. Hou; J. Wei; K. He; X. Han; C. Wang (International Journal of Environmental Science and Technology, 2026)

Peptide-functionalized nanoparticles for brain-targeted therapeutics - Sophia Tang; Emily L. Han; Michael J. Mitchell (Drug Delivery and Translational Research, 2026)
Despite the rapid development of nanoparticle (NP)-based drug delivery systems, intravenous delivery of drugs to the brain remains a major challenge due to various biological barriers. To achieve therapeutic effects, NP-encapsulated drugs must avoid accumulation in off-target organs and selectively deliver to the brain, successfully cross the blood–brain barrier (BBB), and reach the target cells in the brain. Conjugating receptor-specific ligands to the surface of NPs is a promising technique for engineering NPs to overcome these barriers. Specifically, peptides as brain-targeting ligands have been of increasing interest given their ease of synthesis, low cytotoxicity, and strong affinity to target proteins. The success of peptides as targeting ligands is largely due to the diverse strategies of designing and modifying peptides with favorable properties, including membrane permeability and multi-receptor targeting. Here, we review the design and implementation of peptide-functionalized NP systems for neurological disease applications. We also explore advances in rational peptide design strategies for brain targeting, including using generative deep-learning models to computationally design new peptides. Graphical Abstract

3,3'-Dichlorobiphenyl (PCB 11) alters the hepatic expression of cytochrome P450 enzymes in the liver of mouse dams exposed orally during pregnancy and lactation - Crystal M. Roach; Nate R. Koester; Xueshu Li; Jeonghyeon Ahn; R. Marshall Pope; Rebecca J. Wilson; Rosalia Mendieta; Anthony Valenzuela; Weiguo Han; Xinxin Ding; Pamela J. Lein; Hans-Joachim Lehmler (Archives of Toxicology, 2026)
Healthy maternal metabolism is critical during pregnancy and lactation to support fetal development and protect against environmental toxins. Polychlorinated biphenyl 11 (PCB 11), a lower-chlorinated, non-legacy congener, is detected in human serum, including pregnant women and children; however, its impact during these sensitive life stages remains poorly understood. This study presents the first comprehensive hepatic proteome analysis of mouse dams exposed to PCB 11 during pregnancy and lactation. Female C57BL/6 J mice received daily oral doses of PCB 11 (0, 1.0 or 6.0 mg/kg) prior to conception through lactation. At postpartum day 21, brain, liver, and serum samples were analyzed for PCB 11 and its metabolites, and hepatic proteomic changes were assessed. Low detection of PCB 11 and its metabolites was observed in tissues, suggesting rapid clearance. Metabolite screening revealed OH-PCB 11, PCB 11 sulfate, and OH-PCB 11 sulfate metabolites in serum. Global proteomics identified significant alterations in hepatic protein expression, including downregulation of cytochrome P450 enzymes, solute carriers, and enzymes involved in fatty acid and steroid metabolism. Pathway enrichment analyses indicated disruptions in xenobiotic metabolism and endocrine pathways. These findings suggest that PCB 11 exposure during pregnancy and lactation impairs hepatic detoxification and metabolic capacity, potentially compromising maternal and offspring health. This work highlights the need for further investigation into the long-term consequences of PCB 11 exposure during pregnancy and lactation.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Refining the timing and genesis of Nb Ta Mufushan–Lianyunshan Orefield pegmatites (South China) using muscovite - Nurkanati Madayipu; Huan Li; Thomas J. Algeo; Nuo Li; Wen-Bo Sun; Alessandro Petroccia; Biao Liu; Safiyanu Muhammad Elatikpo; Han Zheng (Lithos, 2026)

A scalable machine learning approach for predicting wheat growth stages with a large national dataset - Harris D. Ledvinka; Si Yang Han; Rebecca J. Thistlethwaite; Richard M. Trethowan; Patrick Filippi (Field Crops Research, 2026)

3D channeled porous carbon hosts with cobalt nanoparticle-induced zincophilicity for stable zinc anodes - Hyunsoo Lee; Donghyeon Nam; Chaehyeon Moon; Jinseok Park; Michael J. Lee; Keun Hee Kim; Hyeonsoo Han; Donghyeok Roh; Kyungmo Kim; Jaeyoung Choi; Seung Woo Lee; Byung-Hyun Kim; et al. (Chemical Engineering Journal, 2026)

Dissection of Fusarium head blight resistance in a modified nested association mapping panel of synthetic and bread wheat germplasm - Anil Karmacharya; Dhondup Lhamo; Krishna Acharya; Qijun Zhang; Han-Chang Chang; Shaobin Zhong; Andrew J. Green; Jason D. Fiedler; Mingcheng Luo; Kirk M. Anderson; Amanda R. Peters Haugrud; Elias M. Elias; et al. (Theoretical and Applied Genetics, 2026)

Antagonistic microbiota drive soil suppressiveness against Sclerotinia sclerotiorum, a widespread soil-borne fungal plant pathogen - Viet-Cuong Han; Nicole E. White; Pippa J. Michael; Bec Swift; Duong Vu; Sarita Jane Bennett (Applied Soil Ecology, 2026)

Cumulative environmental exposures adversely impact social behaviour and are associated with dysregulation of genes and proteins involved in epigenetic, ribosomal, and immune regulation in male mice - Morgan C. Bucknor; Brooke A. Keating; Velda X. Han; Brian S. Gloss; Pinki Dey; Nader Aryamanesh; Lee L. Marshall; Mark E. Graham; Ruwani Dissanayake; Xianzhong Lau; Shrujna Patel; Stela P. Petkova; et al. (Inflammation Research, 2026)
Objective This study investigated how cumulative environmental exposures influence offspring behaviour and inflammation-related molecular signatures in the brain and peripheral immune system. Methods A novel "triple-hit" mouse model was developed using C57Bl/6JAusB mice (N = 70), combining preconceptual social stress, antenatal high-fat diet, and a postnatal immune challenge (poly(I:C), 10 mg/kg). At 12 weeks, offspring underwent behavioural tests relevant to neurodevelopmental disorders (NDDs), including the Elevated Plus Maze, 3-Chamber Social Preference, Self-Grooming, and Marble Burying. A composite NDD-risk index was calculated. Single-cell RNA sequencing (scRNA-seq) and bulk proteomics were performed on male triple-hit offspring to identify differentially expressed genes and proteins associated with inflammatory pathways. Results Male triple-hit offspring showed elevated NDD-related behavioural risk and social deficits, not observed in females. scRNA-seq revealed altered inflammatory and ribosomal pathways in brain glia and peripheral immune cells. Proteomic analysis showed decreased abundance of proteins involved in inflammation, translation, chromatin remodelling, and synaptic function in both brain and blood. Conclusion Combined environmental stressors may drive male-specific behavioural and inflammatory changes relevant to NDDs. The identification of overlapping inflammatory signatures in brain and peripheral immune cells supports a role for shared immune mechanisms in brain–immune axis dysfunction. However, these pathway-level findings should be interpreted as preliminary hypotheses and warrant independent validation to confirm their mechanistic significance.

Ex vivo-stimulated cytokine expression in whole blood indicates swine influenza vaccine-induced immune memory - Giulia Fantoni; Andrea Müllebner; Nimród Pálmai; Péter Trampus; Kathrin Lillie-Jaschniski; Han Smits; Navodita Maurice; Krishna Latha; J. Catharina Duvigneau; István Kiss (Veterinary Immunology and Immunopathology, 2026)

Temperature shapes the biogeography of rdhA and reductive dehalogenators in sediment across northwestern Pacific marginal seas - Yangru Xu; Yingchun Han; Xiyang Dong; Yanlei Feng; Fabai Wu; Fengmin Xing; Junyu He; Matthew J. Rogers; Xiwu Luan; Rulong Liu; Jianzhong He; Hongyue Dang; et al. (Journal of Hazardous Materials, 2026)

Quantifying the response of bankfull channel width to active faulting in the Qianhe Graben on the southwest margin of Ordos Block, China - Zhiheng Liu; Sarah J. Boulton; Suiping Zhou; Jianhua Guo; Tingting Wu; Wenjie Zhang; Ling Han (Geomorphology, 2026)

High-resolution marine records of human-nature interactions in the Yellow River Basin since 2.2 kyr ago - Wenqiang Pei; Shiming Wan; Peter D. Clift; Jin Zhang; J. Paul Liu; Yongming Han; Debo Zhao; Zhendong Luan; Zhaojie Yu; Zehua Song; Anchun Li (Global and Planetary Change, 2026)

Hormesis induced by persistent organic pollutants: Mechanisms, ecological implications, and challenges for risk assessment - Evgenios Agathokleous; Haitao Liu; Peter Pressman; Jian-Gang Han; A. Wallace Hayes; Edward J. Calabrese (Environmental Pollution, 2026)

Fuel concentration directs the reaction path of methane oxidation over Pt-ceria catalyst - Siwon Lee; Hyuk Choi; Seunghyun Kim; Ju Hyeok Lee; Yoonseok Choi; Jeong Do Yoo; Minsu Park; Han Gil Seo; Ki-jeong Kim; Ethan J. Crumlin; Beomgyun Jeong; Hyun You Kim; et al. (Chemical Engineering Journal, 2026)

PM2.5 exposure risks in urban outdoor jogging: multiple environmental determinants and mitigation strategies - L. Han; Y. J. Qi; L. Luo; W. Ding; K. Li; W. Li; L. Y. Tang (International Journal of Environmental Science and Technology, 2026)

The analysis of road stormwater runoff pollution in the typical coastal city of Lianyungang, East China - H. Leng; H. Luo; R. Han; W. Wu; B. Song; Y. Zhao; B.-J. He (International Journal of Environmental Science and Technology, 2026)

Digestive ripening and fragmentation of goethite nanorods into nanospheres under natural wet-dry cycles: Unveiling hidden nanocolloid mobilization to water system - Junho Han; Evert J. Elzinga; Minhee Kim (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Biochar-derived dissolved organic matter induced changes in the bacterial communities structure and metabolic functions in As and Cd contaminated soil - Muhammad Azeem; Ruixia Han; Siyao Liu; Kubwimana J. Jacques; Hamada Abdelrahman; Syed S.H. Kazmi; Abdul Kareem; Zulqarnain H. Khan; Nazia Rafiq; Hui Li; Yakov Kuzyakov; Kun Qin (Environmental Research, 2025)

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

Clinical Efficacy of Stem Cell Therapy in Neurotraumatic and Neurodegenerative Conditions: A Comparative Review - Jun Beom Ku; Ray J. Pak; Sarah S. Ku; Robert D. Holland; Han-Soo Kim (Tissue Engineering and Regenerative Medicine, 2025)

Assessing humic acid as natural surfactant in sustainable electrokinetic remediation of low-permeability soil contaminated with petroleum hydrocarbons - J. Han; Y. J. Nam; H.-M. Ro; M. Kim (International Journal of Environmental Science and Technology, 2025)

Reply to “Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China” - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Field measurements of icing parameters and their application towards ice load maps: An overview - Pavlo Sokolov; Muhammad S. Virk; Xingbo Han; Bjørn Egil Nygaard; Eero O. Molkoselkä; Ville A. Kaikkonen; Anssi J. Mäkynen (Cold Regions Science and Technology, 2025)

Evaluation of accuracy on bottom-up NH3 emissions and sensitivity of PM2.5 to emission control in South Korea - K.M. Han; C.H. Jung; C.H. Song; J. Yu; Y. Pan; S.J. Cho; S.D. Shim; J.-H. Koo; J.H. Woo; J. Madalipay; K.Y. Kim; H.S. Kim (Atmospheric Environment, 2025)

Provenance analysis of late Pleistocene sediment from IODP site U1477 reveals climate and river basin dynamics in the Zambezi river catchment - Youhong Gao; Hucai Zhang; Xiaonan Zhang; Lizeng Duan; Huayong Li; Ian R. Hall; Sidney R. Hemming; Leah J. LeVay; Junsheng Nie; Xibin Han; S. Barker; M.A. Berke; et al. (Gondwana Research, 2025)

Impact of mycorrhization with Laccaria bicolor on physiological responses of jack pine (Pinus banksiana) and white spruce (Picea glauca) seedlings to novel oil sands tailing - Gaosen Wang; Yexin Han; Janusz J. Zwiazek; Wen-Qing Zhang (Plant Ecology, 2025)

Research on carbon peak measurement and potential of China’s logistics industry - S. Han; Z. Zhou; J. Gui (International Journal of Environmental Science and Technology, 2025)

Marine Benthic Community Assembly Is Taxonomically Stochastic but Functionally Deterministic in a Dynamic Coastal Sea - Milenka Sloots; Oscar Franken; Kasper J. Meijer; Tjisse van der Heide; Laura L. Govers; Han Olff (Ecology Letters, 2025)
Understanding the balance between deterministic and stochastic processes in community assembly is crucial for interpreting ecological community dynamics. Moreover, it provides perspective for conservation and management actions, as deterministic processes can be subject to targeted interventions, but stochastic processes are less manageable. Through a spatially explicit macrozoobenthic monitoring campaign consisting of 1323 sampling locations in the Dutch Wadden Sea, we examined the relative importance of deterministic and stochastic processes, including the role of hydrodynamic disturbance gradients. We found species‐based community assembly to be mainly driven by stochastic processes, while trait‐based assembly was more deterministic and environmentally driven. Environmental disturbance levels minimally affected the relative importance of stochastic and deterministic processes. For coastal benthic ecosystems, we therefore recommend management actions to target specific desired functional groups rather than specific changes in community composition.

Reconstructing historical catch trends of threatened sharks and rays based on fisher ecological knowledge - Guido Leurs; Rima W. Jabado; Assana Camará; Lilísio Dos Santos; Diosnes Manuel Nonque; Thije J. Zuidewind; Iça Barry; Pierre Campredon; Benja Blaschke; Karin de Boer; Nadia Hijner; Han Olff; et al. (Conservation Biology, 2025)
Small‐scale fisheries often lack historical shark and ray catch information, hampering their management. We reconstructed historical catch trends and current fishing pressure by combining local ecological knowledge, satellite‐based vessel counts, and a short‐term landing‐site survey. To test the effectiveness of this method, we focused on the Bijagós Archipelago (Guinea‐Bissau, West Africa), where historical fisheries data are lacking. Benthic rays (stingrays [Dasyatidae] and butterfly rays [ Gymnura spp.]), benthopelagic rays (duckbill eagle rays [ Aetomylaeus bovinus ] and cownose rays [ Rhinoptera marginata ]), guitarfish ( Glaucostegus and Rhinobatos spp.), requiem sharks (Carcharhinidae), and hammerhead sharks ( Sphyrna spp.) declined in abundance by 81.5–96.7% (species dependent) from 1960 to 2020. Fishing effort increased annually: fishing trip duration by 42.0% (SE 3.4), numbers of fishing vessels at sea as perceived by fishers by 36.3% (1.0) (1960–2020), and number of vessels by 12.0% (1.1) (2007–2022). We estimated that in 2020, fishing vessels collectively captured 61–264 sharks and 522–2194 rays per day in the archipelago, depending on the proportion of the fishing fleet that was active (i.e., low fleet activity of 18% and high fleet activity of 80%). We advocate for reducing shark and ray catches by regulating fleet size, reinforcing boundaries of protected areas, and collecting fisher‐dependent information on shark and ray landings to safeguard these vulnerable species and coastal livelihoods. We demonstrated the effectiveness of using this 3‐pronged approach to provide baseline data on shark fisheries, a common challenge in areas with small‐scale fisheries and limited research capacity.

LP-35 Development of an Optimized in vitro model for Range Finding in Acute Inhalation Toxicity: An Alternative to MucilAir™ - J.Y. Park; I.J. Bang; Y. Han; G.E. Kim; J.E. Lim; J.H. Yu; J. Yoo; H.R. Kim (Toxicology Letters, 2025)

P29-12 Four-Week Repeated Inhalation Toxicity Study of SiO2-ZnO Mixed Nanoparticles in Sprague-Dawley Rats - Y.-J. Heo; M.-J. Yang; H.-Y. Han; H.J. Jin; G.J. Oh; G.-H. Bae; M.-K. Song (Toxicology Letters, 2025)

LP-13 Occurrence and dietary exposure assessment of cyanotoxin in fish consumed in Korea - S. Han; J. Yoon; S. Hyun; J. Seo; J. Kim (Toxicology Letters, 2025)

P31-21 Detection Methods for Injection-Induced Pseudoallergic Reactions - C. Liu; Y. Yi; C. Li; Y. Zhao; Y. Zhang; J. Han; J. Tian; C. Pan; L. Wang; S. Liu; L. Ma; A. Liang (Toxicology Letters, 2025)

Synergy-optimized spin support for reinforced intermediate supply in ultrafast water splitting - Chao Meng; Deyu Kong; Yue Zhou; Bin Wang; Mirabbos Hojamberdiev; Jialin Zhang; Jianglong Ji; Ning Wang; Yanjiao Wang; Mengxin Huang; Lina Li; Alistair J. Fielding; et al. (Science Bulletin, 2025)

Prevalence and related factors of antenatal depression in 11 provinces and cities of China: a 100,000 population-based study - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Imaging viscosity after the 2021 Mw 7.4 Maduo earthquake: Insights on the regional rheology variation beneath the Bayan Har block - Zhen Li; Wei Xiong; Andrew Hooper; Zeyan Zhao; Yuan Gao; John R. Elliott; Tim J. Wright; Han Yue; Teng Wang (Earth and Planetary Science Letters, 2025)

Tailoring oxygen adsorption on nickel nitride for selective 2e− ORR to hydrogen peroxide - Jiahao Liu; Zhaorui Zhang; Zhihang Xu; Ye Zhu; Chenshuai Han; Wei Xiong; J. Paul Attfield; Jianrong Zeng; Siqi Liu; Minghui Yang (Chemical Engineering Journal, 2025)

Seismic observations from injection experiments and a recharge event in a karst aquifer: potential compressed air pocket release - Andrew J. Luhmann; Susan L. Bilek; Matthew D. Covington; Ronni Grapenthin; Han Byul Woo; Jacob Alexander Gochenour; E. Calvin Alexander; Scott C. Alexander; Martin R. Larsen (Hydrogeology Journal, 2025)
After deploying a seismic network above a karst aquifer that feeds Bear Spring in Minnesota, USA, three injection experiments were conducted, which involved pouring ~10,000 L of water just above an overflow spring to induce and characterize ambient seismic noise from subsurface water flow. A rainstorm event followed the second experiment and caused the overflow spring to start flowing with meters of water level rise, increasing the total spring discharge (perennial and overflow emanations) from ~100 to 300 L/s. Water level, electrical conductivity, and temperature data were used to estimate the conduit hydraulic diameter of ~0.06 m from the second injection experiment and ~0.5 m from the recharge event, which suggested both open channel and full pipe conduit flow. The rainstorm led to the largest seismic signals over a 5 s period while water levels rose, producing ground motion up to ~0.5 mm/s, possible oscillatory behavior, and 1–150 J of radiated seismic energy at frequencies of ~30–50 and 70–90 Hz (similar to signal frequencies when the large water slug from the second injection experiment reached a sump or water-filled passage). The seismic sources originated from multiple directions. The calculations suggest these signals came from conduits with air pockets that were compressed from rising water levels and later released via ventilation pathways. Seismic records of this process enable identification of the change in mode of water level propagation and potential delineation of unknown subsurface pathways, facilitating karst aquifer characterization beyond what is possible with traditional monitoring strategies.

Enhanced understanding of soil methane processes through modeling microbial kinetics and taxonomy - Shuhao Zhou; Gangsheng Wang; Wenjuan Huang; Kefeng Wang; Liping Zhang; Zehao Lv; Yajing Han; Shanshan Qi; Wei Zhang; Daifeng Xiang; Steven J. Hall (Soil Biology and Biochemistry, 2025)

Quantitative comparison of seasonal and diurnal characteristics for urban heat using meteorological monitoring data - Y. Gao; J. Zhao; L. Han (International Journal of Environmental Science and Technology, 2025)

A Meta‐Regression of 18 Wildfire Chronosequences Reveals Key Environmental Drivers and Knowledge Gaps in the Boreal Nitrogen Balance - Stefan F. Hupperts; Frank Berninger; Han Y. H. Chen; Nicole Fenton; Mélanie Jean; Kajar Köster; Markku Larjavaara; Michelle C. Mack; Marie‐Charlotte Nilsson; Marjo Palviainen; Anatoly Prokushkin; Jukka Pumpanen; et al. (Global Change Biology, 2025)
Climate change has increased the size and frequency of wildfires across the boreal biome. Severe wildfires in boreal forests have been found to trigger shifts from evergreen to deciduous canopies, which has cascading effects on carbon and nitrogen cycling. Ecosystem productivity and carbon uptake in boreal forests are strongly linked with nitrogen, and Earth system models increasingly depend on our understanding of the nitrogen balance to predict post‐fire carbon uptake. To investigate the post‐fire boreal nitrogen balance, we combined a mass balance approach and literature synthesis to estimate rates of nitrogen accumulation and nitrogen inputs across a network of 18 boreal wildfire chronosequences that varied in both wildfire regime and post‐fire canopy type, comprising 527 forest stands. We found that deciduous‐ or mixed‐dominance boreal forests establishing after severe, stand‐replacing fires had the highest nitrogen accumulation rates (15.7 ± 3.8 kg ha −1 year −1 ), while evergreen‐dominated forests establishing after surface‐ or mixed‐severity fires had the lowest nitrogen accumulation rates (1.4 ± 1.1 kg ha −1 year −1 ). Annual known inputs from nitrogen deposition and biological nitrogen fixation combined, estimated from published data, largely failed to explain the rate of nitrogen accumulation, particularly in deciduous or mixed‐dominance forests establishing after stand‐replacing fires, suggesting that the origins of most nitrogen in these forest types remain poorly understood. As the frequency of severe wildfires increases across the boreal biome and shifts toward deciduous canopies become more common, our study reveals a large knowledge gap in the resulting nitrogen balance that needs to be resolved in order to improve predictions of forest carbon uptake.

Glyceryl lignin enhances lytic polysaccharide monooxygenase (LPMO) oxidative activity via electron transfer and H2O2 generation: Mechanistic insights from glycerol pretreatment - Lingfeng Long; Han Wang; Chong Wang; Shoushuai Feng; Hailin Yang; Xianzhi Meng; Chen Huang; Arthur J. Ragauskas (Chemical Engineering Journal, 2025)

Blood Cells as a Cellular Biomarker for Mitochondrial Function in a Experimental Model of Acute Carbon Monoxide Poisoning with Treatment - Devesh Bungatavula; John C. Greenwood; Frances S. Shofer; Guthrie Buehler; Shih-Han Kao; Matthew Kelly; Samuel S. Shin; Johannes K. Ehinger; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2025)
Introduction Carbon monoxide (CO) is a leading cause of environmental poisoning in the United States with substantial mortality and morbidity. The mechanism of CO poisoning is complex and includes hypoxia, inflammation, and mitochondrial dysfunction. Currently both biomarkers and therapies for CO poisoning are limited and require new approaches. Methods Rats (~ 300 g) were divided into four groups of ten rodents per group (exposure): Control (room air), CO-400 (400 ppm), CO-1000 (1000 ppm) and CO-2000 (2000 ppm). Rodents received the assigned exposure through a secured tracheotomy tube over 120 min followed by 30 min of re-oxygenation at room air for a total of 150 min. Five additional rodents in each group were administered a succinate prodrug (NV354) at the start of exposure for the duration of the experiment until the reoxygenation period as separate experiments. Cortical brain tissue and whole blood were obtained for mitochondrial respiration. Stored plasma and snap frozen tissue stored at -80 o C were used to obtain protein quantification with Western Blotting. Results All animals in the Sham, CO-400, and CO-1000 groups survived until the end of the exposure period; no animals in the CO-2000 groups survived the exposure and were counted as attrition. We observed a dose-dependent decrease in key respiratory states in both isolated brain mitochondria and peripheral blood mononuclear cells (PBMCs), and, PBMCs respiration more positively correlated with isolated brain mitochondria when compared to carboxyhemoglobin (COHb). There was no significant difference in mitochondrial respiratory states in animals treated with NV354 compared to the untreated group. Conclusions The primary findings from this study include: (1) A dose-dependent decrease with key respiration states with higher concentrations of CO; (2) PBMCs had a higher correlation to isolated brain mitochondria respiration when compared to COHb; and (3) there was no treatment effect with the use of NV354.

Alzheimer’s disease polygenic risk’s association with all-cause dementia through the plasma metabolome in the UK Biobank study - May A. Beydoun; Yi-Han Hu; Zhiguang Li; Michael F. Georgescu; Hind A. Beydoun; Nicole Noren Hooten; Keenan A. Walker; Mustapha Bouhrara; Lenore J. Launer; Michele K. Evans; Alan B. Zonderman (GeroScience, 2025)
Dementia, with Alzheimer’s Disease (AD) accounting for 60–70% of its occurrences, is a multifactorial disorder marked by cognitive and functional decline. Polygenic risk scores (PRS) stratify genetic risk for complex diseases, including AD. Integrating PRS with metabolomics offers a pathway to better understand AD etiology and identify biomarkers for early detection. We explored the association between AD PRS, metabolomics, and dementia risk using data from the UK Biobank. The analysis emphasizes sex-specific associations and the mediating role of metabolites between AD PRS and dementia risk. The study utilized data from 205,219 UK Biobank participants aged ≥ 50 years at baseline. Dementia outcomes were derived using ICD-10 codes. AD PRS were computed using genome-wide association study data, while metabolomic data included 249 biomarkers measured via Nuclear Magnetic Resonance. Time-to-event analyses (Cox proportional hazards models) and generalized structural equation modeling assessed associations and mediation effects, adjusting for age, sex, and genetic principal components. Higher AD PRS was associated with increased risks of all-cause dementia (HR: 1.75, 95% CI: 1.70–1.79, P < 0.001) and AD (HR: 2.02, 95% CI: 1.95–2.09, P < 0.001), with stronger effects in women for both outcomes when considering the main AD PRS which was related to APOE4 status. Metabolomic analyses identified lipid-related markers as key mediators. LDL phospholipid content was the metabolite marker with the strongest positive relationship with AD genetic risk (effect size, b = + 0.11), while HDL phospholipids percentage showed a similarly strong inverse association (effect size b = -0.09). No metabolomic markers were significantly associated with another version of AD PRS that was less correlated with APOE4 status. Mediation analyses applied to the main AD PRS revealed modest effects, with LDL-related metabolomic components partially mediating the effect of genetic risk on dementia incidence, through a protective type of mediation (< -2%). Nevertheless, most genetic risk operated independently of metabolites. AD PRS is significantly associated with dementia risk, with sex differences and metabolomic pathways providing further insights. Lipid metabolism, particularly LDL-centric measures, emerged as potential mediators. This integrative approach highlights the utility of combining genetic and metabolomic data to identify biomarkers and potential targets for early intervention in AD and dementia.

Asymmetric Micro‐Evolutionary Responses in a Warming World: Heat‐Driven Adaptation Enhances Metal Tolerance in a Planktonic Rotifer, but Not Vice Versa - Shuwen Han; Paul J. Van den Brink; Steven A. J. Declerck (Global Change Biology, 2025)
The resilience of natural populations in the face of global environmental change is determined by their ability to adapt to multiple, often interacting, stressors. Microevolutionary adaptation to one stressor can either enhance or reduce tolerance to other stressors. In the context of climate change, it is crucial to understand the effect of warming on the tolerance of organisms to additional environmental challenges. Conversely, adaptation to localized stressors, such as pollution, may also affect an organism's capacity to withstand climate change. Here, we investigate how prior adaptation to either high temperature or copper (Cu) contamination influences subsequent tolerance to the other stressor in populations of the freshwater zooplanktonic rotifer Brachionus calyciflorus (Pallas, 1766). Using an experimental evolution approach, we subjected populations to either gradually increasing Cu levels, elevated temperature, or control conditions over multiple generations. Subsequently, we conducted a common garden experiment to assess the effect of selection history on population performance. We found that heat‐adapted populations exhibited increased tolerance to Cu, whereas Cu‐adapted populations showed no enhanced tolerance to high temperatures. This form of “asymmetric cross‐adaptation” is likely driven by selection for generalized stress responses associated with heat adaptation, while Cu adaptation selected for more specialized detoxification mechanisms with limited cross‐protection. These findings suggest that the legacy of warming may enhance population tolerance to other stressors, whereas the benefits of adaptation to local pollution may be more constrained. Our study highlights the need to assess the generality of such patterns across taxa and stressor combinations, as this knowledge could inform environmental management strategies in multi‐stressor contexts.

Exploring suitable domain size for high-resolution urban rainfall simulation - Sichan Du; Lu Zhuo; Elizabeth J. Kendon; Dawei Han (Urban Climate, 2025)

Pharmacotherapeutic role of astringin against chromium induced nephrotoxicity via modulating TLR4/MyD88, HMGB1/RAGE and NF-κB pathway: A biochemical and pharmacokinetic approach - Han Hu; Muhammad Faisal Hayat; Syeda Sania Zahara; Ali Akbar; Khalid J. Alzahrani; Khalaf F. Alsharif; Fuad M. Alzahrani; Ahmed Al-Emam (Journal of Trace Elements in Medicine and Biology, 2025)

Dual functionalities of inexpensive Mn/TiO2 catalyst to produce oxychar for ammonia capture - Kexin Zhao; Yunhong Jiao; Zeyu Zhu; Russell J. Varley; Wei Liu; Bo Niu; Chaoyu Li; Bing Han (Journal of Environmental Chemical Engineering, 2025)

Nutrient production, water consumption, and stresses of large-scale versus small-scale agriculture: A global comparative analysis based on a gridded crop model - Han Su; Timothy Foster; Rick J. Hogeboom; Diana V. Luna-Gonzalez; Oleksandr Mialyk; Bárbara Willaarts; Yafei Wang; Maarten S. Krol (Global Food Security, 2025)

3D facial imaging: a novel approach for metabolic abnormalities risk profiling - Qianqian Peng; Yam Ki Cheung; Yu Liu; Yiyang Wang; Jingze Tan; Yajun Yang; Jiucun Wang; Jing-Dong J. Han; Li Jin; Fan Liu; Sijia Wang (Science China Life Sciences, 2025)

Progress and Perspective of Convection and Cloud Parameterizations in Numerical Models - Yong Wang; Wenwen Xia; Yilun Han; Guang J. Zhang (Journal of Meteorological Research, 2025)

Environment and phytoplankton relative abundances in a hypersaline lake: 27 years in Great Salt Lake, USA and experiments - Gary E. Belovsky; Chad Larson; Younjin Han; Richard Wilson; Hannah J. Appiah-Madson; Heidi Mahon (Aquatic Ecology, 2025)
Over 27 years in Great Salt Lake (GSL: Utah, USA), phytoplankton relative abundances of chlorophytes, diatoms and cyanobacteria varied dramatically (monthly > 90%) of several of the most common GSL phytoplankton (chlorophyte– Dunaliella viridis , diatom– Nitzschia epithemioides , cyanobacterium– Euhalothece sp.). Maximum abundances and growth rates were measured across ranges of temperature (10–30 °C), salinity (30–150 ppt) and nutrients (nitrogen: 0.0–0.64 mg/L, silica:17–51 mg/L) observed within GSL. Experimental results indicated the abundance and growth rate of D. viridis increased as salinity and nitrogen increased and decreased as temperature increased. The abundances and growth rates of N. epithemioides and Euhalothece decreased as salinity increased, and increased as temperature and nitrogen increased, and N. epithemioides increased as silica increased. Observed GSL phytoplankton relative abundances responded to environmental conditions as observed in the experiments, but correlations were weak except for chlorophytes, as diatoms and cyanobacteria relative abundances occasionally increased with unfavorable experimental conditions. The weak correlations between laboratory results and GSL observations could be due to the release of diatoms and cyanobacteria from microbialite biofilms in the lake’s benthos with cold stress and high winds, as a 5–10% release can produce diatom and cyanobacteria phytoplankton relative abundances of 24–48%. This suggests a novel potential link between GSL pelagic and benthic zones.

Synthesis of Population Trends Reveals Seascape‐Wide Reorganisation of Biodiversity From Microalgae to Birds - Anika Happe; Kasper J. Meijer; Jan‐Claas Dajka; Oscar Franken; Holger Haslob; Laura L. Govers; Michael Kleyer; Annebelle C. M. Kok; Lucie Kuczynski; Kertu Lõhmus; Sancia E. T. van der Meij; Han Olff; et al. (Global Change Biology, 2025)
Many monitoring programs aim to understand regional biodiversity patterns in relation to global and regional conservation targets, using either community‐wide biodiversity metrics to describe the community status or trends of pre‐selected “key” species as biodiversity change indicators. However, the former often lacks information on which species are changing, and the latter is heavily skewed towards specific taxa, potentially overlooking changes in other, functionally important taxa. We gathered an extensive set of monitoring data with over 3000 population trends (ranging from 5 to 91 years in duration) for a wide range of taxa across the Wadden Sea. We combined a systematic and quantitative categorization of population trends (weighted vote count) with a meta‐analysis on different taxonomic levels. This allowed the first cross‐taxa synopsis of species declines and increases and determined their directionalities throughout time. Our meta‐analysis showed an overall decrease in population size for fish, zooplankton, and plant species, while birds showed an overall increase. However, these increases mask recent negative trends within specific bird groups since the late 1990s. In contrast, fish populations exhibited declines over the entire monitoring period. Species with declining populations (losers) were phylogenetically related, whereas species with increasing populations (winners) represented various organismal groups. Directionality and onsets of change in population trends were temporally synchronized throughout several groups, such as bivalves, fish, and birds, and may provide warning signals for future local extinctions in these taxa. Our analysis moves beyond typical indicator species by including the entire species inventory of the system. Basal trophic levels of aquatic ecosystems, such as zooplankton and phytoplankton, are often missing from policy assessments but are among the most important organism groups for ecosystem functioning. Here, we show that without additional monitoring effort, a systematic analysis of population trends adds to our understanding of trophic and compositional restructuring of ecosystems.

Impact of dispersion correction in DFT-enhanced anisotropic NMR for stereochemical elucidation of flexible marine natural products - Lu-Ping Chi; Xiao-Lu Li; Anton F. Ketzel; Armando Navarro-Vázquez; Caspar J. Schattenberg; Xiao-Ming Li; Xin Li; Han Sun; Bin-Gui Wang (Marine Life Science & Technology, 2025)
Although anisotropic NMR spectroscopy has emerged as a powerful method for determining the relative configuration of complex natural products, major challenges persist with structurally flexible molecules. In this study, we conducted a systematic comparative analysis of stereochemical elucidation, combining anisotropic NMR spectroscopy and density functional theory (DFT) calculations on spiroepicoccin B ( 1 ) and epicoccin V ( 2 ), which were characterized as thiodiketopiperazine marine natural products isolated from the deep-sea-derived fungus Epicoccum nigrum SD-388. For the flexible compound 2 , we compared various conformational sampling approaches, including an assessment of the quality of relative energies within the obtained ensembles. We demonstrated the critical role of dispersion correction within DFT computations to precisely account for weak non-bonded intramolecular interactions. By integrating anisotropic NMR analysis, chemical shifts, electronic circular dichroism, and DFT computations, we determined the absolute configurations and conformational ensembles for 1 and 2 , respectively, highlighting the significance of the intramolecular methyl–π interaction in stabilizing one of the conformers. Our study introduces new strategies to address conformational flexibility in the stereochemical elucidation of challenging organic molecules.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Assessing the impact of climate change on rainfall-triggered landslides: a case study in California - Shabnam J. Semnani; Yi Han; Céline J. Bonfils; Joshua A. White (Landslides, 2025)
Landslides are widespread natural hazards which take a heavy toll on lives, property, and infrastructure each year. In January 2023 and 2024, widespread landslides occurred in California as a result of extreme winter precipitation. Estimating the regional evolution of landslide hazard in a changing climate is essential for adaptation planning and risk mitigation efforts. The complex effects of climate change on landslide hazard, however, are poorly understood. Here, we use climate and landslide observations to develop a novel data-driven approach for landslide susceptibility assessment under historical and future climate conditions. We apply this framework to investigate the evolution of landslide susceptibility in California and its impacts on the roadway system based on downscaled climate projections under moderate and high greenhouse gas emission scenarios. On average, the results indicate an increase in landslide susceptibility through 2100 in regions where historical susceptibility is moderate to very high. Although the spatio-temporal variations in landslide susceptibility are sensitive to climate model uncertainties in predicting extreme rainfall, the direst impacts are largely circumvented in lower emission scenarios.

Paper-immobilized liquid-phase microextraction for direct paper spray mass spectrometry and immuno-detection of atropine in baby food, buckwheat cereals, and edible oils at regulatory levels - Ids B. Lemmink; Sipke J. Bosma; Toine F.H. Bovee; Han Zuilhof; Gert IJ. Salentijn (Analytica Chimica Acta, 2025)

Complexity in long-term stand dynamics of mixed-species, multi-cohort stands using an imputation/copula tree growth model - Yung-Han Hsu; John A. Kershaw; Aaron R. Weiskittel; Mark J. Ducey (Forest Ecology and Management, 2025)

Fluorapatite fingerprints on magmatic-hydrothermal fluid evolution of the Lianyunshan Nb-Ta-Sn deposit, NE Hunan (South China) - Nuerkanati Madayipu; Huan Li; Thomas J. Algeo; Safiyanu Muhammad Elatikpo; Han Zheng; Biao Liu; Da-Peng Zhu; Nuo Li; Victor Ikechukwu Vincent (Chemical Geology, 2025)

Mapping the impact of age and APOE risk factors for late onset Alzheimer’s disease on long range brain connections through multiscale bundle analysis - Jacques Stout; Robert J. Anderson; Ali Mahzarnia; Zay Yar Han; Kate Beck; Jeffrey Browndyke; Kim Johnson; Richard J. O’Brien; Alexandra Badea (Brain Structure and Function, 2025)

Do biopores created by perennial fodder crops improve the growth of subsequent annual crops? A synthesis of multiple field experiments - Dominik Behrend; Miriam Athmann; Eusun Han; Paul Martin Küpper; Ute Perkons; Sara L. Bauke; Ulrich Köpke; Timo Kautz; Thomas Gaiser; Sabine J. Seidel (Field Crops Research, 2025)

Biochar-derived dissolved organic matter (BDOM) shifts fungal community composition: BDOM-soil DOM interaction - Muhammad Azeem; Jian Wang; Jean J. Kubwimana; Syed S.H. Kazmi; Zulqarnain H. Khan; Kaiwen He; Ruixia Han (Applied Soil Ecology, 2025)

Elevated vascular endothelial growth factor a is associated with disruption of default network connectivity in older adults - Arunima Kapoor; Jung Yun Jang; Allison C. Engstrom; Trevor Lohman; Shubir Dutt; John Paul M. Alitin; Isabel J. Sible; Anisa Marshall; Fatemah Shenasa; Aimee Gaubert; Amy Nguyen; David Robert Bradford; et al. (Brain Imaging and Behavior, 2025)
Vascular Endothelial Growth Factor A (VEGF-A) is an angiogenic signaling protein involved in the maintenance of the cerebral vasculature. No prior study has explored whether plasma VEGF-A levels may be associated with brain functional connectivity changes, such as disruption of the default mode network (DMN), which often precedes the development of cognitive changes in aging. Seventy-six independently living older adults (mean age = 70.3 years; SD = 7.5; 31.6% male) free of dementia or clinical stroke underwent venipuncture and brain MRI. Plasma was assayed for VEGF-A. Using resting state functional MRI, region of interest (ROI) to ROI connectivity and graph theory analysis were conducted to determine average connectivity and global efficiency between each of the following ROIs comprising the DMN: medial prefrontal cortex, lateral parietal cortex and precuneus cortex. Multiple linear regression analysis revealed a significant negative association between VEGF-A levels and DMN connectivity (B = − 0.14, 95% CI (-0.26, − 0.01), p =.038), accounting for age, sex, education, and vascular risk factors. Graph theory analysis similarly revealed that VEGF-A levels are associated with global efficiency of the entire network (B = − 0.18, p =.004). These findings suggest that VEGF-A may be elevated early in the progression of neurocognitive disorders. Whether higher levels of VEGF-A contribute to the pathogenesis of neurocognitive disorders or play a protective role in preserving cognitive function warrants further investigation. Clinical Trial Number: N/A; None.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Chalcones, flavonoids, and aristolactam alkaloids from Friesodielsia kingii and their biological activities - Sorraya Champakam; Virayu Suthiphasilp; Brian O. Patrick; Zi Han Loh; Tharakorn Maneerat; Thidarat Duangyod; Rawiwan Charoensup; Panom Winyayong; Phunrawie Promnart; Sarot Cheenpracha; Siau Hui Mah; Raymond J. Andersen; et al. (Phytochemistry Letters, 2025)

Scalable fabrication of a tough and recyclable spore-bearing biocomposite thermoplastic polyurethane - Han Sol Kim; Evan M. White; Grant Crane; Kush Patel; Myung Hyun Noh; Md Arifur Rahman; Adam M. Feist; Jason J. Locklin; Jonathan K. Pokorski (Chemical Engineering Journal, 2025)

Grassland bud and shoot demographic responses to single and recurrent droughts vary across an aridity gradient - Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Yuan Shi; Lin Song; Jiaqi Chen; Hongqiang Wang; Jianqiang Qian; Qiang Yu; Zhengwen Wang; Xiaotao Lü; Xingguo Han; et al. (Ecology, 2025)
Clonal demographic traits play important roles in regulating community dynamics. Yet, it remains unclear how the responses of these clonal traits to drought might depend on previous drought exposure, and how drought responses vary among grasslands. We conducted a repeated drought experiment across four grasslands along an aridity gradient in northern China. We assessed the effects of single (precipitation reduction in 2021–2022) versus recurrent (precipitation reduction in 2015–2018 and 2021–2022) drought on bud density, shoot density, and the ratio of bud to shoot density. Drought reduced bud density at all grasslands and shoot density at most grasslands. Drought reduced the ratio of bud‐to‐shoot density only in the most arid grasslands. Recurrent drought had larger negative effects than a single drought on bud density and composition of bud and shoot at only one of four grasslands, and on shoot density at two of four grasslands. Our results suggest that previous drought exposure can alter the response of plant clonal demographic traits to subsequent drought in some but not all grasslands, and that responses can vary with mean climate.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

China's methane emissions derived from the inversion of GOSAT observations with a CMAQ and EnKS-based regional data assimilation system - Xingxia Kou; Zhen Peng; Xiao Han; Jialin Li; Li Qin; Meigen Zhang; Robert J. Parker; Hartmut Boesch (Atmospheric Pollution Research, 2025)

Trends and classification of aerosol observed from MODIS sensor over Northern Europe and the Arctic - Kyung M. Han; Chang H. Jung; Chul H. Song; Ja H. Koo; Young J. Yoon; Bang Y. Lee; Hyun S. Kim; S. Seo (Atmospheric Pollution Research, 2025)

Development of Zinc-Containing Chitosan/Gelatin Coatings with Immunomodulatory Effect for Soft Tissue Sealing around Dental Implants - Jing Han; Jorine G. F. Sanders; Lea Andrée; Bart A. J. A. van Oirschot; Adelina S. Plachokova; Jeroen J. J. P. van den Beucken; Sander C. G. Leeuwenburgh; Fang Yang (Tissue Engineering and Regenerative Medicine, 2025)
BACKGROUND: Soft tissue integration (STI) around dental implant abutments is a prerequisite to prevent bacterial invasion and achieve successful dental implant rehabilitation. However, peri-implant STI is a major challenge after dental abutment placement due to alterations in the immune microenvironment upon surgical dental implant installation. METHODS: Based on known immunomodulatory effects of zinc, we herein deposited zinc/chitosan/gelatin (Zn/CS/Gel) coatings onto titanium substrates to study their effect on macrophages. First, we exposed macrophages to cell culture media containing different zinc ion (Zn 2+ ) concentrations. Next, we explored the immunomodulatory effect of Zn/CS/Gel coatings prepared via facile electrophoretic deposition (EPD). RESULTS: We found that Zn 2+ effectively altered the secretome by reducing the secretion of pro-inflammatory and enhancing pro-regenerative cytokine secretion, particularly at a Zn 2+ supplementation of approximately 37.5 μM. Zn/CS/Gel coatings released Zn 2+ in a concentration range which effectively stimulated pro-regenerative macrophage polarization as demonstrated by M2 macrophage polarization. Additionally, the impact of these Zn 2+ -exposed macrophages on gingival fibroblasts incubated in conditioned medium showed stimulated adhesion, proliferation, and collagen secretion. CONCLUSION: Our promising results suggest that controlled release of Zn 2+ from Zn/CS/Gel coatings could be applied to immunomodulate peri-implant STI, and to enhance dental implant survival.

Single-cell omics: experimental workflow, data analyses and applications - Fengying Sun; Haoyan Li; Dongqing Sun; Shaliu Fu; Lei Gu; Xin Shao; Qinqin Wang; Xin Dong; Bin Duan; Feiyang Xing; Jun Wu; Minmin Xiao; et al. (Science China Life Sciences, 2025)

Nutrient effects on plant diversity loss arise from nutrient identity and decreasing niche dimension - Yang Peng; Jianxia Yang; Eric W. Seabloom; Andrew R. Leitch; Ilia J. Leitch; Ruzhen Wang; Cunzheng Wei; Xingguo Han (Ecology, 2025)
Two hypotheses have been used to explain the loss of plant diversity with nutrient addition. The nutrient identity hypothesis posits that biodiversity loss is due to a specific limiting nutrient, such as nitrogen (N) or phosphorus (P), while the niche dimension hypothesis posits that adding a larger number of limiting nutrients, regardless of their identity, results in biodiversity loss. These two hypotheses have not previously been tested together simultaneously. Here, we conduct that analysis to enable their relative effect sizes to be compared. We manipulated the supply of eight nutrients in the same experimental meadow grassland site to isolate the effects of the identity of added nutrients versus the number of added nutrients on biodiversity loss. We found support for both hypotheses, with the largest negative effects on biodiversity measures being due to N, or N and P treatment, with additional more minor effects of the number of added nutrients. Structural equation models (SEMs) suggested both identity and number of added nutrients had direct negative effects on biodiversity, likely caused by species' innate ability to competitively respond to nutrients, especially in response to disease, herbivory, and stress. SEMs also suggested indirect effects arising from nutrient‐driven increases in aboveground biomass, which resulted in intensified competition for light and the competitive exclusion of short‐statured species. These effects were exacerbated by the nutrients N and P which caused a shift in biomass accumulation from belowground to aboveground. The results highlight that a multi‐nutrient perspective will improve our ability to effectively manage, monitor, and restore ecosystems.

Emerging roles of inositol pyrophosphates in signaling plant phosphorus status and phytohormone signaling - Tao Wu; Chuang Wang; Bei Han; Zhu Liu; Xinyu Yang; Wei Wang; Guangda Ding; John P. Hammond; Philip J. White; Fangsen Xu; Lei Shi (Plant and Soil, 2024)

Positive cooperativity in synergistic activation of Wnt proteins - Clemence Bonnet; Christiana S. Han; Sophie X. Deng; Jie J. Zheng (Molecular Biology Reports, 2024)
Background Wnt proteins are crucial for embryonic development, stem cell growth, and tissue regeneration. Wnt signaling pathway is activated when Wnt proteins bind to cell membrane receptors. Methods and results We employed a luciferase reporter assay in HEK293STF cells to measure Wnt protein-induced signaling. We observed that Wnt3a uniquely promotes the Wnt/β-catenin pathway through positive cooperativity. Additionally, MFH-ND, a molecular mimic of Wnt ligands, markedly increased Wnt3a-induced signaling in a dose-responsive manner. This suggests that various Wnt ligands can synergistically enhance Wnt pathway activation. Conclusions The study suggests the likelihood of various Wnt ligands coexisting in a single signalosome on the cell membrane, providing new insights into the complexities of Wnt signaling mechanisms.

Alzheimer’s Disease polygenic risk, the plasma proteome, and dementia incidence among UK older adults - May A. Beydoun; Hind A. Beydoun; Zhiguang Li; Yi-Han Hu; Nicole Noren Hooten; Jun Ding; Sharmin Hossain; Christian A. Maino Vieytes; Lenore J. Launer; Michele K. Evans; Alan B. Zonderman (GeroScience, 2024)
Alzheimer’s Disease (AD) is a complex polygenic neurodegenerative disorder. Its genetic risk’s relationship with all-cause dementia may be influenced by the plasma proteome. Up to 40,139 UK Biobank participants aged ≥ 50y at baseline assessment (2006–2010) were followed-up for ≤ 15 y for dementia incidence. Plasma proteomics were performed on a sub-sample of UK Biobank participants ( k = 1,463 plasma proteins). AD polygenic risk scores (PRS) were used as the primary exposure and Cox proportional hazards models were conducted to examine the AD PRS-dementia relationship. A four-way decomposition model then partitioned the total effect (TE) of AD PRS on dementia into an effect due to mediation only, an effect due to interaction only, neither or both. The study found that AD PRS tertiles significantly increased the risk for all-cause dementia, particularly among women. The study specifically found that AD PRS was associated with a 79% higher risk for all-cause dementia for each unit increase (HR = 1.79, 95% CI: 1.70–1.87, P < 0.001). Eighty-six plasma proteins were significantly predicted by AD PRS, including a positive association with PLA2G7, BRK1, the glial acidic fibrillary protein (GFAP), neurofilament light chain (NfL), and negative with TREM2. Both GFAP and NfL significantly interacted synergistically with AD PRS to increase all-dementia risk (> 10% of TE is pure interaction), while GFAP was also an important consistent mediator in the AD PRS-dementia relationship. In summary, we detected significant interactions of NfL and GFAP with AD PRS, in relation to dementia incidence, suggesting potential for personalized dementia prevention and management.

Palliative effect of abalone insulin-related peptide 2 on emersion stress-induced hyperglycemia in the Pacific abalone (Haliotis discus hannai) - Mi-Jin Choi; Young Dae Oh; J. Sook Chung; Han Kyu Lim (Aquaculture, 2024)

Short-term air pollution and greenness exposures on oxidative stress in urban and peri-urban residents in Beijing: A part of AIRLESS study - Wenhao Qi; Hanbin Zhang; Yiqun Han; Wu Chen; Yanbo Teng; Lia Chatzidiakou; Benjamin Barratt; Rod Jones; Frank Kelly; Tong Zhu; Junfeng Zhang; John S. Ji; et al. (Science of The Total Environment, 2024)

Is human perception reliable? Toward illumination robust food freshness prediction from food appearance — Taking lettuce freshness evaluation as an example - Dongyi Wang; Swarna Sethu; Sabari Nathan; Zhenye Li; Victoria J. Hogan; Chao Ni; Shengfan Zhang; Han-Seok Seo (Journal of Food Engineering, 2024)

Heterogeneous marine response during the Toarcian Oceanic Anoxic Event (TOAE): The potential role of storminess - Yuzhu Ge; Zhong Han; Thomas J. Algeo; David B. Kemp; Luya Wu (Global and Planetary Change, 2024)

Uncovering mediational pathways behind racial and socioeconomic disparities in brain volumes: insights from the UK Biobank study - May A. Beydoun; Hind A. Beydoun; Marie T. Fanelli-Kuczmarski; Yi-Han Hu; Danielle Shaked; Jordan Weiss; Shari R. Waldstein; Lenore J. Launer; Michele K. Evans; Alan B. Zonderman (GeroScience, 2024)
Mediation pathways explaining racial/ethnic and socioeconomic (SES) disparities in structural MRI markers of brain health remain underexplored. We examined racial/ethnic and SES disparities in sMRI markers and tested total, direct, and indirect effects through lifestyle, health-related, and cognition factors using a structural equations modeling approach among 36,184 UK Biobank participants aged 40–70 years at baseline assessment (47% men). Race (non-White vs. White) and lower SES-predicted poorer brain sMRI volumetric outcomes at follow-up, with racial/ethnic disparities in sMRI outcomes involving multiple pathways and SES playing a central role in those pathways. Mediational patterns differed across outcomes, with the SES-sMRI total effect being partially mediated for all outcomes. Over 20% of the total effect (TE) of race/ethnicity on WMH was explained by the indirect effect (IE), by a combination of different pathways going through SES, lifestyle, health-related, and cognition factors. This is in contrast to < 10% for total brain, gray matter (GM), white matter (WM), and frontal GM left/right. Another significant finding is that around 57% of the total effect for SES and the normalized white matter hyperintensity (WMH) was attributed to an indirect effect. This effect encompasses many pathways that involve lifestyle, health-related, and cognitive aspects. Aside from WMH, the percent of TE of SES mediated through various pathways ranged from ~ 5% for WM to > 15% up to 36% for most of the remaining sMRI outcomes, which are composed mainly of GM phenotypes. Race and SES were important determinants of brain volumetric outcomes, with partial mediation of racial/ethnic disparities through SES, lifestyle, health-related, and cognition factors.

Trans-crop applications of atypical R genes for multipathogen resistance - Peng Sun; Xinyu Han; Ricky J. Milne; Guotian Li (Trends in Plant Science, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Estimating merchantable and non-merchantable wood volume in slash walls using terrestrial and airborne LiDAR - Nicholas Cranmer; Tao Han; Brett Chedzoy; Peter J. Smallidge; Colin Beier; Lucas Johnson; Xiangtao Xu (Forest Ecology and Management, 2024)

Biotechnological approaches for targeted strain screening and enhancement of Daqu for quality baijiu production - Akhtiar Ali; Yanfang Wu; Weiwei Li; Xi Chen; Prasanna J. Patil; Meiyue Han; Haroon Shah; Lei Zhao; Xiuting Li (Food Bioscience, 2024)

Estimating ambient air pollutant concentrations outside and inside homes in the Subpopulations and Intermediate outcomes in COPD air pollution (SPIROMICS air) cohort - Kipruto Kirwa; Amanda J. Gassett; Coralynn Sack; Laura M. Paulin; Cheryl S. Pirozzi; R. Graham Barr; Prescott G. Woodruff; MeiLan Han; May-Lin Wilgus; Igor Barjaktarevic; Stephen Peters; Nadia N. Hansel; et al. (Environmental Research, 2024)

Harnessing the power of tidal flat diatoms to combat climate change - Jihae Park; Hojun Lee; Jana Asselman; Colin Janssen; Stephen Depuydt; Jonas De Saeger; Thomas Friedl; Koen Sabbe; Wim Vyverman; Catharina J. M. Philippart; Jaime Pitarch; Philippe M. Heynderickx; et al. (Critical Reviews in Environmental Science and Technology, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Cytotoxicity and cell membrane interactions of choline-based ionic liquids: Comparing amino acids, acetate, and geranate anions - Mohamad El Mohamad; Qi Han; Brendan Dyett; Haitao Yu; Sara Edgecomb; Mercedes C. Pride; Claylee M. Chism; Angela Roberts; Deauntaye Jones; Eden E.L. Tanner; Calum J. Drummond; Tamar L. Greaves; et al. (Chemosphere, 2024)

Evolutionary ecology of masting: mechanisms, models, and climate change - Michal Bogdziewicz; Dave Kelly; Davide Ascoli; Thomas Caignard; Francesco Chianucci; Elizabeth E. Crone; Emilie Fleurot; Jessie J. Foest; Georg Gratzer; Tomika Hagiwara; Qingmin Han; Valentin Journé; et al. (Trends in Ecology & Evolution, 2024)

Molecular determinants of the selectivity and potency of α-conotoxin Vc1.1 for human nicotinic acetylcholine receptor subtypes - Han-Shen Tae; Andrew Hung; David J. Adams (Toxicon, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Proximity Labelling Confirms the Involvement of Papain-Like Cysteine Proteases and Chaperones in Cyclotide Biosynthesis - Meng-Han Lee; Mark A. Jackson; Fabian B. H. Rehm; Deborah S. Barkauskas; Wing L. Ho; Kuok Yap; David J. Craik; Edward K. Gilding (Plant Molecular Biology Reporter, 2024)
Cyclotides are disulfide-rich insecticidal peptides from plants that harbour a cyclic cystine knot motif that imparts them with high stability. Like most ribosomally encoded peptides, cyclotides are produced as precursor proteins that are subsequently processed to maturity through proteolytic activity. Although the final maturation of the prototypic cyclotide kalata B1 (kB1) is known to involve asparaginyl endopeptidases, the role of the in planta folding machinery is less well characterized, as is also the case for in planta N-terminal processing enzyme(s). Here, we used proximity labelling to identify proteins involved in the biosynthesis of kB1 in both a cyclotide-bearing plant species, Petunia × hybrida [Regel], and in Nicotiana benthamiana [Domin] that does not naturally produce cyclotides. Together, several ER resident chaperones, protein disulfide isomerases, a papain-like cysteine protease, and an asparaginyl endopeptidase were identified in the kB1 interactome. We found that overexpression of the identified papain-like cysteine protease resulted in an improvement in the yield of cyclic kB1, while this was not the case for the overexpression of protein disulfide isomerases, despite their interaction being verified using bimolecular fluorescence complementation. Together, these results provide a significant advance in our understanding of the role of auxiliary biosynthetic elements for heterologous cyclotide production in plants.

Tailoring wheat agronomic management to ENSO phases to manage climate variability in Australia at 5-minute resolution - Juan Cao; Zhao Zhang; Jun Xie; Yuchuan Luo; Jichong Han; Patrick J. Mitchell; Fulu Tao (Agricultural and Forest Meteorology, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Leveraging meta-regression to test if medication effects on cue-induced craving are associated with clinical efficacy - Steven J. Nieto; Han Du; Lindsay R. Meredith; Suzanna Donato; Molly Magill; Lara A. Ray (Psychopharmacology, 2024)
Rationale The alcohol cue exposure paradigm is a common method for evaluating new treatments for alcohol use disorder (AUD); however, it is unclear if medication-related reductions in cue-induced craving in the human laboratory can predict the clinical success of those medications in reducing alcohol consumption during clinical trials. Objectives To use a novel meta-analytic approach to test whether medication effect sizes on cue-induced alcohol craving are associated with clinical efficacy in clinical trials. Method We searched the literature for medications tested for AUD treatment using both the alcohol cue-reactivity paradigm and randomized clinical trials (RCTs). For alcohol cue-reactivity studies, we computed medication effect sizes for cue-induced alcohol craving (k = 36 studies, 15 medications). For RCTs, we calculated medication effect sizes for heavy drinking and abstinence (k = 139 studies, 19 medications). Using medication as the unit of analysis, we applied the Williamson-York bivariate weighted least squares estimation to account for errors in both independent and dependent variables. We also conducted leave-one-out cross validation simulations to examine the predictive utility of cue-craving medication effect sizes on RCT heavy drinking and abstinence endpoints. Results There was no significant relationship between medication effects on cue-induced alcohol craving in the human laboratory and medication effects on heavy drinking ( $$\widehat{β }$$ β ^ = 0.253, SE = 0.189, p = 0.090) and abstinence ( $$\widehat{β }$$ β ^ = 0.829, SE = 0.747, p = 0.133) in RCTs. Conclusions The preliminary results of the current study challenge the assumption that alcohol cue-reactivity alone can be used as an early efficacy indicator for AUD pharmacotherapy development. These findings suggest that a wider range of early efficacy indicators and experimental paradigms be considered for Phase II testing of novel compounds.

Sustainable regulation of calcium magnesium phosphate and rapeseed cake on soil-tea system in Mount Lushan, China - C. Han; Y. Ding; Z. J. Tang; Y. Q. Lai; M. Liu (Environmental Geochemistry and Health, 2024)

Human atherosclerotic plaque transcriptomics reveals endothelial beta-2 spectrin as a potential regulator a leaky plaque microvasculature phenotype - Timo Rademakers; Marco Manca; Han Jin; Tanguy Orban; Ljubica Matic Perisic; Hubertus J. M. Frissen; Frank Rühle; Petra Hautvast; Jos van Rijssel; Kim van Kuijk; Barend M. E. Mees; Carine J. Peutz-Kootstra; et al. (Angiogenesis, 2024)
The presence of atherosclerotic plaque vessels is a critical factor in plaque destabilization. This may be attributable to the leaky phenotype of these microvessels, although direct proof for this notion is lacking. In this study, we investigated molecular and cellular patterns of stable and hemorrhaged human plaque to identify novel drivers of intraplaque vessel dysfunction. From transcriptome data of a human atherosclerotic lesion cohort, we reconstructed a co-expression network, identifying a gene module strongly and selectively correlated with both plaque microvascular density and inflammation. Spectrin Beta Non-Erythrocytic 1 ( sptbn1 ) was identified as one of the central hubs of this module (along with zeb1 and dock1 ) and was selected for further study based on its predominant endothelial expression. Silencing of sptbn1 enhanced leukocyte transmigration and vascular permeability in vitro, characterized by an increased number of focal adhesions and reduced junctional VE-cadherin. In vivo, sptbn1 knockdown in zebrafish impaired the development of the caudal vein plexus. Mechanistically, increased substrate stiffness was associated with sptbn1 downregulation in endothelial cells in vitro and in human vessels. Plaque SPTBN1 mRNA and protein expression were found to correlate with an enhanced presence of intraplaque hemorrhage and future cardiovascular disease (CVD) events during follow-up. In conclusion, we identify SPTBN1 as a central hub gene in a gene program correlating with plaque vascularisation. SPTBN1 was regulated by substrate stiffness in vitro while silencing blocked vascular development in vivo, and compromised barrier function in vitro. Together, SPTBN1 is identified as a new potential regulator of the leaky phenotype of atherosclerotic plaque microvessels.

Microbial communities overwhelm environmental controls in explaining nitrous oxide emission in acidic soils - Shengwen Xu; Yongxiang Yu; Haoxin Fan; Nataliya Bilyera; Xiangtian Meng; Jiantao Xue; Zhong Lu; Zhihan Yang; Stephen J. Chapman; Fuyun Gao; Wenyan Han; Yaying Li; et al. (Soil Biology and Biochemistry, 2024)

Fiddler crab bioturbation stimulates methane emissions in mangroves: Insights into microbial mechanisms - Guoming Qin; Zhe Lu; Shuchai Gan; Lulu Zhang; Jingtao Wu; Christian J. Sanders; Zhili He; Xiaoli Yu; Jingfan Zhang; Jinge Zhou; Ruyi Ding; Xingyun Huang; et al. (Soil Biology and Biochemistry, 2024)

Cyclic peroxides and analogs: Antibacterial, antimalarial, and cytotoxic marine products from Xisha sponge Diacarnus sp. - Xue Leng; Hongying He; J. Enrico H. Lazaro; Xiaohui Chen; Han Ouyang; Te Li; Xia Yan; Shan He (Phytochemistry, 2024)

Coordinate-wise monotonic transformations enable privacy-preserving age estimation with 3D face point cloud - Xinyu Yang; Runhan Li; Xindi Yang; Yong Zhou; Yi Liu; Jing-Dong J. Han (Science China Life Sciences, 2024)

Plant diversity decreases greenhouse gas emissions by increasing soil and plant carbon storage in terrestrial ecosystems - Pengfei Dang; Miaomiao Zhang; Xinli Chen; Michel Loreau; J. Emmett Duffy; Xin'e Li; Shuyue Wen; Xiaoqing Han; Lechen Liao; Tiantian Huang; Chenxi Wan; Xiaoliang Qin; et al. (Ecology Letters, 2024)
The decline in global plant diversity has raised concerns about its implications for carbon fixation and global greenhouse gas emissions (GGE), including carbon dioxide (CO 2 ), nitrous oxide (N 2 O) and methane (CH 4 ). Therefore, we conducted a comprehensive meta‐analysis of 2103 paired observations, examining GGE, soil organic carbon (SOC) and plant carbon in plant mixtures and monocultures. Our findings indicate that plant mixtures decrease soil N 2 O emissions by 21.4% compared to monocultures. No significant differences occurred between mixtures and monocultures for soil CO 2 emissions, CH 4 emissions or CH 4 uptake. Plant mixtures exhibit higher SOC and plant carbon storage than monocultures. After 10 years of vegetation development, a 40% reduction in species richness decreases SOC content and plant carbon storage by 12.3% and 58.7% respectively. These findings offer insights into the intricate connections between plant diversity, soil and plant carbon storage and GGE—a critical but previously unexamined aspect of biodiversity–ecosystem functioning.

Oxygen supersaturation adds resistance to a cnidarian: Symbiodiniaceae holobiont under moderate warming in experimental settings - Silvia Arossa; Shannon G. Klein; Elisa Garuglieri; Alexandra Steckbauer; Anieka J. Parry; Jacqueline V. Alva Garcia; Taiba Alamoudi; Xinyuan Yang; Shiou-Han Hung; Octavio R. Salazar; Ramona Marasco; Marco Fusi; et al. (Frontiers in Marine Science, 2024)
Ocean warming reduces O 2 solubility and increases organismal O 2 demand, endangering marine life. Coastal ecosystems, however, experience O 2 supersaturation during peak daytime temperatures due to metabolic cycles. Recent discoveries show that this environmental supersaturation can reduce the vulnerability of tropical species to warming by satisfying their oxygen requirements. To test whether this also occurs within the cnidarian holobiont, we elevated internal O 2 in Cassiopea andromeda at nighttime (i.e. holobiont respiration prevails on Symbiodniaceae O 2 production) relying on bell pulsation for ventilation, then experimentally subjected them to thermal stress (+1°C day -1 ). Though ecologically unrealistic, this approach verified our hypothesis and eliminated confounding factors. Holobionts were exposed to either constant levels of 100% air saturation (100AS) or nighttime supersaturation (NSS; where 100% air saturation transitioned to O 2 supersaturation at nighttime). At sublethal temperatures, supersaturation mitigated reductions in holobiont size of ~ 10.37% (-33.418% ± 0.345 under 100AS vs -23.039% ± 0.687 under NSS). Supersaturation alleviated chlorophyll- a loss by 42.73% until 34°C, when counteraction of this process could not be sustained due to excessive thermal stress. Supersaturation also enriched potentially beneficial bacterial taxa of the microbiome and selected a more consistent bacterial community. Although modest, the detected effects show that a O 2 surplus increased the resistance of the holobionts to thermal stress.

Anti-obesogenic effects of plant natural products: A focus on Korean traditional foods - Gitishree Das; Luis Alfonso Jiménez Ortega; Sandra Gonçalves; J. Basilio Heredia; Maria de Lourdes Gomes Pereira; Anabela Romano; Han-Seung Shin; Jayanta Kumar Patra (Trends in Food Science & Technology, 2024)

Sustainability information, taste perception and willingness to pay: The case of bird-friendly coffee - Klaus G. Grunert; Han-Seok Seo; Di Fang; Victoria J. Hogan; Rodolfo M. Nayga Jr. (Food Quality and Preference, 2024)

Bioturbation by Benthic Stingrays Alters the Biogeomorphology of Tidal Flats - Janne Nauta; Guido Leurs; Brian O. Nieuwenhuis; Donné R. A. H. Mathijssen; Han Olff; Tjeerd J. Bouma; Daphne van der Wal; Nadia Hijner; Aissa Regalla; Samuel Ledo Pontes; Laura L. Govers (Ecosystems, 2024)
Fishing-down-marine-food-webs has resulted in alarming declines of various species worldwide. Benthic rays are one examples of such overexploited species. On tidal flats, these rays are highly abundant and play an ecologically important role. They use tidal flats as refuge, feeding and resting grounds, during which they bury into the sediment, which results in sediment bioturbation. Changes in bioturbation intensity, following ray removal, may affect the biogeomorphology of tidal flats with possible cascading effects on the macrozoobenthic community. However, it is poorly understood how these indirect effects could influence ecosystem function. We therefore studied the geomorphic impact of benthic rays (specifically the pearl whipray/stingray Fontitrygon margaritella ) on the tropical tidal flats of the Bijagós Archipelago, Guinea-Bissau, on a landscape scale. We investigated 1) bioturbation rates by rays using drone and ground surveys, 2) the spatial distribution of ray pits on multiple tidal flats, 3) the impact of rays on sediment properties and macrozoobenthos by experimental exclusion (15 months). Benthic rays bioturbated 3.7 ± 0.35% of the tidal flat’s sediment surface per day over one single 24-h period, which equals a complete top-sediment-surface turnover every 27 days. The spatial distribution of ray pits was affected by tidal flat geomorphology since pits decayed faster at areas exposed to strong hydrodynamic forces. Predator exclusion altered sediment properties, leading to changes in sedimentation (− 17%) and erosion (− 43%) rates. In addition, macrozoobenthic species composition changed, marked by an increase in Capitellidae worms and a greater biomass of Malacostraca over time. These changes indicated substantial effects of ray bioturbation on the biotic and geomorphic landscape of tidal flats. Overall, we conclude that changing abundances of benthic rays can have clear landscape-wide geomorphological effects on intertidal ecosystems. These indirect consequences of fisheries should be incorporated in integrative management plans to preserve tidal flats and connected ecosystems.

Quantitative Applications of Weather Satellite Data for Nowcasting: Progress and Challenges - Jun Li; Jing Zheng; Bo Li; Min Min; Yanan Liu; Chian-Yi Liu; Zhenglong Li; W. Paul Menzel; Timothy J. Schmit; John L. Cintineo; Scott Lindstrom; Scott Bachmeier; et al. (Journal of Meteorological Research, 2024)

The effects and mechanisms of deep straw incorporation and denitrifying bacterial agents on mitigating nitrate leaching and N2O emissions in four soil types in the North China Plain - Ya-Bo Zhang; Si-Yi Liu; Jun-Tao Wang; Hong J. Di; Li-Li Han; Pei-Pei Li; Ju-Pei Shen; Bing Han; Li-Mei Zhang (Agriculture, Ecosystems & Environment, 2024)

Change in rate of healthcare encounters for respiratory infection from air pollution exposure after improved vehicle emissions standards in New York State - Daniel P. Croft; Mark J. Utell; Han Liu; Shao Lin; Philip K. Hopke; Sally W. Thurston; Yunle Chen; David Q. Rich (Air Quality, Atmosphere & Health, 2024)
The introduction of Tier 3 light-duty vehicles with reduced emissions began in New York State (NYS) in 2017, with required compliance by 2025. We hypothesized that improved air quality during the early implementation of Tier 3 (2017–2019) would result in reduced rates of hospitalizations and emergency department (ED) visits for respiratory infection associated with increased PM 2.5 compared to 2014–2016 (pre-Tier 3). Using data on adult patients hospitalized or having an ED visit for influenza, upper respiratory infection, culture-negative pneumonia, or respiratory bacterial infection, living within 15 miles of six air quality monitoring sites in NY, and a case-crossover design and conditional logistic regression, we estimated the rates of respiratory infection hospitalizations and ED visits associated with increased ambient PM 2.5 concentrations in the previous 0–6 days and each week thereafter up to 1 month. Interquartile range (IQR) increases in PM 2.5 in the previous 6 days were associated with 4.6% (95% CI: − 0.5, 10.1) and 11.9% (95% CI = 6.1, 18.0) increased rates of influenza hospitalizations in 2014–2016 and 2017–2019, respectively. This pattern of larger relative rates in 2017–2019 observed at all lag times was only present in males hospitalized for influenza but not other infections or in females. The rates of respiratory infection visits associated with increased PM 2.5 were generally not reduced in this early Tier 3 implementation period compared to 2014–2016. Limited fleet penetration of Tier 3 vehicles and differences in particle deposition, infection type, and sex by period may all have contributed to this lack of improvement.

Reintroduction of self-facilitating feedbacks could advance subtidal eelgrass (Zostera marina) restoration in the Dutch Wadden Sea - Katrin Rehlmeyer; Oscar Franken; Tjisse van der Heide; Sander J. Holthuijsen; Kasper J. Meijer; Han Olff; Wouter Lengkeek; Karin Didderen; Laura L. Govers (Frontiers in Marine Science, 2024)
Extensive subtidal eelgrass ( Zostera marina ) meadows (~150 km 2 ) once grew in the Dutch Wadden Sea, supporting diverse species communities, but disappeared in the 1930s and have been absent ever since. Identifying the most critical bottlenecks for eelgrass survival is a crucial first step for reintroduction through active restoration measures. Seagrasses are ecosystem engineers, inducing self-facilitating feedbacks that ameliorate stressful conditions. Consequently, once seagrass, including its self-facilitating feedbacks, is lost, reintroduction can be challenging. Therefore, we aimed to test whether 1) sediment stabilization and 2) hydrodynamic stress relief would facilitate eelgrass survival in a field experiment replicated at two sites in the Dutch Wadden Sea. We induced feedbacks using biodegradable root-mimicking structures (BESE-elements) and sandbag barriers. Root mimics had a significant positive effect, increasing the chances of short-term survival by +67% compared to controls. Contrary to our expectations, barriers decreased short-term survival probabilities by -26%, likely due to hydrodynamic turbulence created by the barrier edges, leading to high erosion rates (-14 cm). Site selection proved crucial as short-term survival was entirely negated on one of the two study sites after five weeks due to high floating and epiphytic macroalgae loads. No long-term survival occurred, as plants died at the other site two weeks later. Overall, we found that sediment stabilization by root-mimicking structures was promising, whereas manipulating hydrodynamic forces using sandbag barriers had adverse effects. A mechanistic understanding of transplant failures is required before attempting large-scale restoration. Our study indicates that for seagrass restoration in the Wadden Sea, one should carefully consider 1) the reintroduction of positive feedbacks through restoration tools, 2) donor population choice and transplantation timing, and 3) site selection based on local biotic and abiotic conditions. Optimizing these restoration facets might lower additive stress to a degree that allows long-term survival.

Consensus Paper: Cerebellum and Reward - Mario Manto; Michael Adamaszek; Richard Apps; Erik Carlson; Julian Guarque-Chabrera; Elien Heleven; Shinji Kakei; Kamran Khodakhah; Sheng-Han Kuo; Chi-Ying R. Lin; Mati Joshua; Marta Miquel; et al. (The Cerebellum, 2024)

Metabolism-dependent mutagenicity of two structurally similar tobacco-specific nitrosamines (N-nitrosonornicotine and N-nitrosoanabasine) in human cells, partially different CYPs being activating enzymes - Yijing Chen; Zongying Yang; Zhao Zhou; Ellery J. Liu; Wenwen Luo; Zhini He; Weili Han; Yungang Liu (Toxicology, 2024)

Strontium isotope evidence for regional enhanced continental weathering during the early Toarcian in the Tethys Himalaya - Yubo Yang; Zhong Han; Xiumian Hu; Tianchen He; Robert J. Newton; Jason Harvey (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Agronomic monsoon onset definitions to support planting decisions for rainfed rice in Bangladesh - Eunjin Han; Carlo Montes; Sk. Ghulam Hussain; Timothy J. Krupnik (Climatic Change, 2024)
The usability gaps between climate information producers and users have always been an issue in climate services. This study aims to tackle the gap for rice farmers in Bangladesh by exploring the potential value of tailored agronomic monsoon onset definitions. Summer aman rice is primarily cultivated under rainfed conditions, and farmers rely largely on monsoon rainfall and its onset for crop establishment. However, farmers’ perception of the arrival of sufficient rains does not necessarily coincide with meteorological definitions of monsoon onset. Therefore, localized agronomic definitions of monsoon onset need to be developed and evaluated to advance in the targeted actionable climate forecast. We analyzed historical daily rainfall from four locations across a north-south gradient in Bangladesh and defined dynamic definitions of monsoon onset based on a set of local parameters. The agronomic onset definition was evaluated in terms of attainable yields simulated by a rice simulation model compared to results obtained using conventional meteorological onset parameters defined by the amount of rainfall received and static onset dates. Our results show that average simulated yields increase up to 7 – 9% and probabilities of getting lower yields are reduced when the year-to-year varying dynamic onset is used over the two drier locations under fully rainfed conditions. It is mainly due to earlier transplanting dates, avoiding the impact of drought experienced with early monsoon demise. However, no yield increases are observed over the two wetter locations. This study shows the potential benefits of generating “localized and translated” climate predictions.

Surrogate model for geological CO 2 storage and its use in hierarchical MCMC history matching - Yifu Han; François P. Hamon; Su Jiang; Louis J. Durlofsky (Advances in Water Resources, 2024)

Floral resource partitioning of coexisting bumble bees: Distinguishing species‐, colony‐, and individual‐level effects - Zhong‐Ming Ye; Yong‐Deng He; Pedro J. Bergamo; Michael C. Orr; Wen Huang; Xiao‐Fang Jin; Han‐Ning Lun; Qing‐Feng Wang; Chun‐Feng Yang (Ecology, 2024)
Resource partitioning is considered a key factor in alleviating competitive interactions, enabling coexistence among consumer species. However, most studies have focused on resource partitioning between species, ignoring the potentially critical role of intraspecific variation in resource use. We investigated floral resource partitioning across species, colonies, and individuals in a species‐rich bumblebee community in the diversification center of bumblebees. We used a total of 10,598 bumblebees belonging to 13 species across 5 years in the Hengduan Mountains of southwest China. First, we evaluated the influence of a comprehensive set of floral traits, including both those related to attractiveness (flower color and shape) and rewards (pollen, sugar ratio, nectar volume, sugar concentration, and amino acid content) on resource partitioning at the species level in bumblebee–plant networks. Then, we explored intraspecific resource partitioning on the colony and individual levels. Our results suggest that bumblebee species differ substantially in their use of the available floral resources, and that this mainly depends on flower attractiveness (floral color and shape). Interestingly, we also detected floral resource partitioning at the colony level within all commonest bumblebee species evaluated. In general, floral resource partitioning between bumblebee individuals decreased with species‐ and individual‐level variation in body size (intertegular span). These results suggest that bumblebee species may coexist via the flexibility in their preferences for specific floral traits, which filters up to support the co‐occurrence of high numbers of species and individuals in this global hotspot of species richness.

Insect root feeders incur negative density‐dependent damage across plant species in an alpine meadow - Lixuan Kou; Nan Yang; Han Yan; Karl J. Niklas; Shucun Sun (Ecology, 2024)
Although herbivores are well known to incur positive density‐dependent damage and mortality, thereby likely shaping plant community assembly, the response of belowground root feeders to changes in plant density has seldom been addressed. Locally rare plant species (with lower plant biomass per area) are often smaller with shallower roots than common species (with higher plant biomass per area) in competition‐intensive grasslands. Likewise, root feeders are often distributed in the upper soil layers. We hypothesized, therefore, that root feeders would incur negative density (biomass)‐dependent damage across plant species. To test this hypothesis, we investigated the diversity and abundance of plant and root feeder species in an alpine meadow and determined the diet of the root feeders using metabarcoding. Across all species, root feeder load decreased with increasing aboveground plant biomass, root biomass, and total plant biomass per area, indicating a negative density dependence of damage across plant species. Aboveground plant biomass per area increased with increasing individual plant biomass and root depth per area across species, suggesting that rare plant species were smaller in size and had shallower root systems compared to common plant species. Both root biomass per area and root feeder biomass per area decreased with soil depth, but the root feeder biomass decreased disproportionately faster compared to root biomass with increasing root depth. Root feeder load decreased with increasing root depth but was not correlated with the feeding preference of root feeder species. Moreover, the prediction derived from a random process incorporating vertical distributions of root biomass and root feeder biomass significantly accounted for interspecific variation in root feeder load. In conclusion, the data indicate that root feeders incur negative density‐dependent damage across plant species. On this basis, we suggest that manipulative experiments should be conducted to determine the effect of the negative density‐dependent damage on plant community structure and that different types of plant–animal interactions should be concurrently examined to fully understand the effect of plant density on overall herbivore damage across plant species.

A systematic review of Muskingum flood routing techniques - Aryan Salvati; Alireza Moghaddam Nia; Ali Salajegheh; Ataollah Shirzadi; Himan Shahabi; Ebrahim Ahmadisharaf; Dawei Han; John J Clague (Hydrological Sciences Journal, 2024)

Mutual facilitation between foundation species Mytilus edulis and Lanice conchilega promotes habitat heterogeneity on tidal flats - Janne Nauta; Kasper J. Meijer; Lissie W. de Groot; Valérie C. Reijers; Tjeerd J. Bouma; Daphne van der Wal; Han Olff; Sander J. Holthuijsen; Allert I. Bijleveld; Henk W. van der Veer; Oscar Franken; Laura L. Govers (Frontiers in Marine Science, 2024)
Foundation species that modify their habitat can facilitate other species, including other foundation species. Most studies focus solely on a single foundation species, overlooking such facilitation cascades. In this study, we investigated the interactions between the two coastal foundation species Mytilus edulis (blue mussel) and Lanice conchilega (sand mason worm). We investigated whether these species engage in facilitative interactions or if their association simply reflects a shared ecological niche on the soft-sediment intertidal flats of the Dutch Wadden Sea. To do so, we performed species distribution modeling, manipulative field experiments, and field surveys. We found a positive association between both foundation species, with a 2.45 times higher occurrence of both species compared to a random distribution. In addition, these species partially occupied the same ecological niche. We demonstrated that L. conchilega provided settlement substrate for M. edulis spat, increasing densities by 400 times compared to bare plots. Furthermore, M. edulis reefs facilitated L. conchilega occurrence in the wake of the reef. Biogenic reef development revealed that this interspecific facilitation resulted in spatial habitat heterogeneity. Therefore, we conclude that interspecific facilitation can significantly enhance the occurrence of these two important intertidal foundation species. Acknowledgment of such complex facilitation interactions has an untapped potential for improving the success of restoration and conservation programs.

A natural mutant kumquat fruit with abnormal oil glands shows lower volatile production, better fruit flavor and higher resistance to postharvest disease - Man Zhu; Yang Wang; Zhebin Zeng; Xi Wu; Jiacheng Teng; Jingzong Zhang; Qianrong Han; Qiaoli Ma; Chuanwu Chen; Yunjiang Cheng; Xiuxin Deng; Niels J. Nieuwenhuizen; et al. (Postharvest Biology and Technology, 2024)

Improving impact of heparan sulfate on the endothelial glycocalyx abnormalities in atherosclerosis as revealed by glycan-protein interactome - Qingqing Chen; Xiaohui Xu; Shaoshuai Xie; Anran Sheng; Naihan Han; Zhenyu Tian; Xiaowei Wang; Fuchuan Li; Robert J. Linhardt; Fuming Zhang; Lan Jin; Qunye Zhang; et al. (Carbohydrate Polymers, 2024)

Simulating behavior of perfluorooctane sulfonate (PFOS) in the mainstream of a river system with sluice regulations - Guoxiang Han; Shuai Song; Yonglong Lu; Meng Zhang; Di Du; Qiang Wu; Shengjie Yang; Rui Wang; Haotian Cui; Lu Yang; Ruoyu Mao; Bin Sun; et al. (Chemosphere, 2024)

Reaction pathways and Sb(III) minerals formation during the reduction of Sb(V) by Rhodoferax ferrireducens strain YZ-1 - Yidan Zhang; Maxim I. Boyanov; Edward J. O’Loughlin; Kenneth M. Kemner; Robert A. Sanford; Han-Suk Kim; Soo-Chan Park; Man Jae Kwon (Journal of Hazardous Materials, 2024)

Unraveling the impact of digital transformation on green innovation through microdata and machine learning - Yuangang Han; Zhentao Li; Tianchu Feng; Shilei Qiu; Jin Hu; Krishna Kumar Yadav; Ahmad J. Obaidullah (Journal of Environmental Management, 2024)

Deciphering temporal gene expression dynamics in multiple coral species exposed to heat stress: Implications for predicting resilience - Tingyu Han; Xin Liao; Zhuojun Guo; J.-Y. Chen; Chunpeng He; Zuhong Lu (Science of The Total Environment, 2024)

Application of Cartilage Extracellular Matrix to Enhance Therapeutic Efficacy of Methotrexate - Jeong-Woo Seo; Sung-Han Jo; Seon-Hwa Kim; Byeong-Hoon Choi; Hongsik Cho; James J. Yoo; Sang-Hyug Park (Tissue Engineering and Regenerative Medicine, 2024)

Effectiveness and potential mechanism of hydrothermal modification of attapulgite for cadmium passivation in soil - G. Ma; J. Ren; L. Tao; X. Han; C. Liao; Y. Zhou; J. Ding; Y. Zhou; K. Bi (International Journal of Environmental Science and Technology, 2024)

Temperature sensitivity of organic carbon decomposition in lake sediments is mediated by chemodiversity - Shuailong Wen; Ang Hu; Shuyu Jiang; Lei Han; Kyoung‐Soon Jang; Andrew J. Tanentzap; Jicheng Zhong; Jianjun Wang (Global Change Biology, 2024)
Organic carbon decomposition in lake sediments contributes substantially to the global carbon cycle and is strongly affected by temperature. However, the magnitude of temperature sensitivity ( Q 10 ) of decomposition and the underlying factors remain unclear at the continental scale. Carbon quality temperature (CQT) hypothesis asserts that less reactive and more recalcitrant molecules tend to have higher temperature sensitivities, but its support is challenged by complex composition of organic matter and environmental constraints. Here, we quantified Q 10 of the sediments across 50 freshwater ecosystems along a 3500 km north–south transect, and characterized the quality of sediment dissolved organic carbon with chemodiversity reflected in molecular richness, functional traits (i.e., molecular weight, bioavailability, etc.) and composition. We further included classic environmental variables, such as climatic, physicochemical and microbial factors, to explore how Q 10 is constrained by these factors or carbon quality. We found that Q 10 varied greatly across lakes, with the mean value of 1.78 ± 0.62, but showed nonsignificant latitudinal pattern. Q 10 was primarily predicted by chemodiversity and showed an increasing trend with the biochemical recalcitrance indicated by traits such as aromaticity and standard Gibb's Free Energy at both molecular and compositional levels. This suggests that carbon quality is the crucial determinant of Q 10 in lakes, supporting the CQT hypothesis. Moreover, Q 10 decreased linearly with the increase of molecular richness, implying that the resistance of decomposition to warming is associated with higher molecular diversity. Compared with the structural equation model containing only environmental variables, inclusion of chemodiversity increased 32.8% of the explained variation in Q 10 , and chemodiversity was the only driver showing direct effects. Collectively, this study illustrates the importance of chemodiversity in shaping the pattern of Q 10 , and has significant implications for accurately predicting the carbon turnover in lake ecosystems in the context of global warming.

Grassland sensitivity to drought is related to functional composition across E ast A sia and N orth A merica - Lin Song; Robert J. Griffin‐Nolan; Taofeek O. Muraina; Jiaqi Chen; Niwu Te; Yuan Shi; Kenneth D. Whitney; Bingchuan Zhang; Qiang Yu; Melinda D. Smith; Xiaoan Zuo; Zhengwen Wang; et al. (Ecology, 2024)
Plant traits can be helpful for understanding grassland ecosystem responses to climate extremes, such as severe drought. However, intercontinental comparisons of how drought affects plant functional traits and ecosystem functioning are rare. The Extreme Drought in Grasslands experiment (EDGE) was established across the major grassland types in East Asia and North America (six sites on each continent) to measure variability in grassland ecosystem sensitivity to extreme, prolonged drought. At all sites, we quantified community‐weighted mean functional composition and functional diversity of two leaf economic traits, specific leaf area and leaf nitrogen content, in response to drought. We found that experimental drought significantly increased community‐weighted means of specific leaf area and leaf nitrogen content at all North American sites and at the wetter East Asian sites, but drought decreased community‐weighted means of these traits at moderate to dry East Asian sites. Drought significantly decreased functional richness but increased functional evenness and dispersion at most East Asian and North American sites. Ecosystem drought sensitivity (percentage reduction in aboveground net primary productivity) positively correlated with community‐weighted means of specific leaf area and leaf nitrogen content and negatively correlated with functional diversity (i.e., richness) on an intercontinental scale, but results differed within regions. These findings highlight both broad generalities but also unique responses to drought of community‐weighted trait means as well as their functional diversity across grassland ecosystems.

Early-Life Social Determinants of SCA6 Age at Onset, Severity, and Progression - Tiffany X. Chen; Hannah L. Casey; Chi-Ying R. Lin; Theresa A. Boyle; Jeremy D. Schmahmann; Gilbert J. L’Italien; Sheng-Han Kuo; Christopher M. Gomez (The Cerebellum, 2024)
SCA6 patients with the same size CAG repeat allele can vary significantly in age at onset (AAO) and clinical progression. The specific external factors affecting SCA6 have yet to be investigated. We assessed the effect of early life events on AAO, severity, and progression in SCA6 patients using a social determinant of health approach. We performed a survey of biological and social factors in SCA6 patients enrolled in the SCA6 Network at the University of Chicago. AAO of ataxia symptoms and patient-reported outcome measure (PROM) of ataxia were used as primary outcome measures. Least absolute shrinkage and selection operation (LASSO) regressions were used to identify which early life factors are predictive of SCA6 AAO, severity, and progression. Multiple linear regression models were then used to assess the degree to which these determinants influence SCA6 health outcomes. A total of 105 participants with genetically confirmed SCA6 completed the assessments. SCA6 participants with maternal difficulty during pregnancy, active participation in school sports, and/or longer CAG repeats were determined to have earlier AAO. We found a 13.44-year earlier AAO for those with maternal difficulty in pregnancy than those without ( p = 0.008) and a 12.31-year earlier AAO for those active in school sports than those who were not ( p < 0.001). Higher education attainment was associated with decreased SCA6 severity and slower progression. Early life biological and social factors can have a strong influence on the SCA6 disease course, indicating that non-genetic factors can contribute significantly to SCA6 health outcomes.

Radiocarbon integrity of dissolved inorganic carbon (DIC) samples stored in plastic and glass bottles: implications for reliable groundwater age dating - David X. Soto; Luis J. Araguás-Araguás; Liang-Feng Han; Leonard I. Wassenaar (Isotopes in Environmental and Health Studies, 2024)

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

Facing a time crunch: Time poverty and travel behaviour in Canada - Sang-O Kim; Matthew Palm; Soojung Han; Nicholas J. Klein (Transportation Research Part D: Transport and Environment, 2024)

A mobilised bearing capacity approach to the performance-based design of unpaved roads - A.S. Lees; J. Han (Transportation Geotechnics, 2024)

Synergistic effect of climate change and water management: Historical and future soil salinity in the Kur-Araz lowland, Azerbaijan - Junho Han; Minhee Kim; Zaman Mammadov; Seoyeon Lee; Evert J. Elzinga; Garib Mammadov; Wonjae Hwang; Hee-Myong Ro (Science of The Total Environment, 2024)

Environmental forensics approach to source investigation in a mercury contaminated river: Insights from mercury stable isotopes - Young Gwang Kim; Sae Yun Kwon; Spencer J. Washburn; Yongseok Hong; Seung Hee Han; Mikyung Lee; Ji Hyoung Park (Journal of Hazardous Materials, 2024)

Abating ammonia emission from poultry manure by Pt/TiO2 modified corn straw - Yunhong Jiao; Jie Huang; Jing Hu; Anthony J. Weatherley; Wei Liu; Chaoyu Li; Zhiling Ma; Bing Han (Journal of Environmental Management, 2024)

Authigenic clay mineral constraints on spatiotemporal evolution of restricted, evaporitic conditions during deposition of the Ediacaran Doushantuo Formation - Shujun Han; Stefan C Löhr; April N Abbott; Andre Baldermann; Graham A. Shields; Huan Cui; Alan J Kaufman; Bo Chen; Bingsong Yu (Earth and Planetary Science Letters, 2024)

Comparison of PM2.5 components and secondary formation during the heavily polluted period of two megacities in China - Z. Ran; X. Wang; X. Yin; Y. Liu; M. Han; Y. Cheng; J. Han; T. Jin (International Journal of Environmental Science and Technology, 2024)

Comparative study of machine learning methods for modeling associations between risk factors and future dementia cases - Vaka Valsdóttir; María K. Jónsdóttir; Brynja Björk Magnúsdóttir; Milan Chang; Yi-Han Hu; Vilmundur Gudnason; Lenore J. Launer; Hlynur Stefánsson (GeroScience, 2023)

Multivariate investigation of aging in mouse models expressing the Alzheimer’s protective APOE2 allele: integrating cognitive metrics, brain imaging, and blood transcriptomics - Hae Sol Moon; Ali Mahzarnia; Jacques Stout; Robert J. Anderson; Madison Strain; Jessica T. Tremblay; Zay Yar Han; Andrei Niculescu; Anna MacFarlane; Jasmine King; Allison Ashley-Koch; Darin Clark; et al. (Brain Structure and Function, 2023)

Molecular characterization of four genes encoding abalone insulin-related peptides and their roles in regulation of hemolymph glucose in the Pacific abalone Haliotis discus hannai - Mi-Jin Choi; Young Dae Oh; J. Sook Chung; Jong-Myoung Kim; Han Kyu Lim (Aquaculture, 2023)

Polyoxygenated cyclohexene derivatives and other constituents of Uvaria rufa stem - Aleksandra Gurgul; Zhenlong Wu; Kyu-Yeon Han; Gauri Shetye; Kongmany Sydara; Onevilay Souliya; Jeremy J. Johnson; Chun-Tao Che (Phytochemistry, 2023)

Paleogene sediment provenance in the Gaize Basin: Implications for early Cenozoic paleogeography of central Tibet - Bowen Song; Kexin Zhang; Yi Wei; Gaolei Jiang; Tinglu Yang; Thomas J. Algeo; Jiaxuan Wang; Fang Han (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Paleozoic and Mesozoic magmatism in the Gaodi porphyry Mo-Cu deposit: Implications for the evolution of the Mongol-Okhotsk Ocean in the northern Great Xing'an Range, NE China - Jing Kan; Ke-Zhang Qin; Le Wang; Kai-Xuan Hui; Ri Han; Noreen J. Evans; Zhao-Jun Meng (Gondwana Research, 2023)

Pressurization-induced molten globule-like protein as a regulatory target for off-flavor controlling: Thermodynamic evidence and molecular modeling - Chuanhu Han; Yuanrong Zheng; Changyu Zhou; Yiqi Liang; Siqiang Huang; Yangying Sun; Jinxuan Cao; Jun He; Francisco J. Barba; Jiqiang Liu; Daodong Pan; Qiang Xia (Food Control, 2023)

Identification of a fundamental cryoinjury mechanism in MSCs and its mitigation through cell-cycle synchronization prior to freezing - Brian H. Johnstone; Dongsheng Gu; Chieh-Han Lin; Jianguang Du; Erik J. Woods (Cryobiology, 2023)

Designing ultrastable Pt/CeO2-Al2O3 nanosheet catalysts for three-way catalysts applications - Junjie Chen; Chih-Han Liu; Hien N. Pham; Todd J. Toops; Abhaya K. Datye; Eleni A. Kyriakidou (Chemical Engineering Journal, 2023)

Source apportionment of water-soluble oxidative potential of PM2.5 in a port city of Xiamen, Southeast China - Jia-Min Li; Si-Min Zhao; Si-Han Xiao; Xiang Li; Shui-Ping Wu; Jie Zhang; James J. Schwab (Atmospheric Environment, 2023)

Phytotoxicity induced by soil-applied hydrothermally-carbonised waste amendments: effect of reaction temperature, feedstock and soil nutrition - Henry Luutu; Michael T. Rose; Shane McIntosh; Lukas Van Zwieten; Han H. Weng; Matt Pocock; Terry J. Rose (Plant and Soil, 2023)

Extreme precipitation stable isotopic compositions reveal unexpected summer monsoon incursions in the Qilian Mountains - Liangju Zhao; Xiying Dong; Xiaohong Liu; Ninglian Wang; Christopher J. Eastoe; Na Wei; Cong Xie; Hang Liu; Chuntan Han; Ting Hua; Lixin Wang (Science of The Total Environment, 2023)

Connecting link between a sediment source and its deep-sea sink: Ilan Shelf offshore northeastern Taiwan - Ho-Han Hsu; Char-Shine Liu; John D. Milliman; Tzu-Ting Chen; Jih-Hsin Chang; J. Paul Liu; Chih-Chieh Su; Mei-Chi Fan (Marine and Petroleum Geology, 2023)

Spatially heterogenous seawater δ34S and global cessation of Ca-sulfate burial during the Toarcian oceanic anoxic event - Zhong Han; Xiumian Hu; Robert J. Newton; Tianchen He; Benjamin J.W. Mills; Hugh C. Jenkyns; Micha Ruhl; Robert A. Jamieson (Earth and Planetary Science Letters, 2023)

Stretchable and biodegradable triboelectric nanogenerator based on elastomeric nanocomposites - Heeseok Kang; Won Bae Han; Seung Min Yang; Gwan-Jin Ko; Yelynn Ryu; Joong Hoon Lee; Jeong-Woong Shin; Tae-Min Jang; Kaveti Rajaram; Sungkeun Han; Dong-Je Kim; Jun Hyeon Lim; et al. (Chemical Engineering Journal, 2023)

Green chemical and hybrid enzymatic pretreatments for lignocellulosic biorefineries: Mechanism and challenges - Rijuta Ganesh Saratale; Vinoth Kumar Ponnusamy; Grzegorz Piechota; Bartłomiej Igliński; S. Shobana; Jeong-Hoon Park; Ganesh Dattatraya Saratale; Han Seung Shin; J. Rajesh Banu; Vinod Kumar; Gopalakrishnan Kumar (Bioresource Technology, 2023)

Optimization of A2O–MBR–BAF–O3 combination process for domestic wastewater - L. Huang; J. Han; G. Wang; Y. Hou; Z. Li; F. Yi (International Journal of Environmental Science and Technology, 2023)

The PAVICS-Hydro platform: A virtual laboratory for hydroclimatic modelling and forecasting over North America - Richard Arsenault; David Huard; Jean-Luc Martel; Magali Troin; Juliane Mai; François Brissette; Christian Jauvin; Long Vu; James R. Craig; Trevor J. Smith; Travis Logan; Bryan A. Tolson; et al. (Environmental Modelling & Software, 2023)

Zirconium and neodymium isotopes record intensive felsic volcanism in South China region during the Permian-Triassic boundary crisis - Yu Jiao; Lian Zhou; Thomas J. Algeo; Lanping Feng; Jun Shen; Yating Hu; Jinhua Liu; Yan Han; Xin Hou (Chemical Geology, 2023)

Predicting the ripening time of ‘Hass’ and ‘Shepard’ avocado fruit by hyperspectral imaging - Yifei Han; Shahla Hosseini Bai; Stephen J. Trueman; Kourosh Khoshelham; Wiebke Kämper (Precision Agriculture, 2023)
Predicting the ripening time of avocado fruit accurately could improve fruit storage and decrease food waste. No reasonable method exists for predicting the postharvest ripening time of avocado fruit during transport, storage or retail display. Here, hyperspectral imaging ranging from 388 to 1005 nm with 462 bands was applied to 316 ‘Hass’ and 160 ‘Shepard’ mature, unripe avocado fruit to predict how many days it took for individual fruit to become ripe. Three models were developed using partial least squares regression (PLSR), deep convolutional neural network (DCNN) regression and DCNN classification. Our PLSR models provided coefficients of determination (R 2 ) of 0.76 and 0.50 and root mean squared errors (RMSE) of 1.20 and 1.13 days for ‘Hass’ and ‘Shepard’ fruit, respectively. The DCNN-based regression models produced similar results with R 2 of 0.77 and 0.59, and RMSEs of 1.43 and 0.94 days for ‘Hass’ and ‘Shepard’ fruit, respectively. The prediction accuracies and RMSEs from DCNN classification models, respectively, were 67.28% and 1.52 days for ‘Hass’ and 64.06% and 1.03 days for ‘Shepard’. Our study demonstrates that the spectral reflectance of the skin of mature, unripe ‘Hass’ and ‘Shepard’ fruit provides adequate information to predict ripening time and, thus, has the potential to improve postharvest processing and reduce postharvest losses of avocado fruit.

Cell-Free DNA as a Biomarker in a Rodent Model of Chlorpyrifos Poisoning Causing Mitochondrial Dysfunction - Shih-Han Kao; Frances S. Shofer; John C. Greenwood; Oladunni Alomaja; Abhay Ranganathan; Sarah Piel; Clementina Mesaros; Samuel S. Shin; Johannes K. Ehinger; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2023)

CHD7 variants associated with hearing loss and enlargement of the vestibular aqueduct - Isabelle Roux; Cristina Fenollar-Ferrer; Hyun Jae Lee; Parna Chattaraj; Ivan A. Lopez; Kyungreem Han; Keiji Honda; Carmen C. Brewer; John A. Butman; Robert J. Morell; Donna M. Martin; Andrew J. Griffith (Human Genetics, 2023)
Enlargement of the endolymphatic sac, duct, and vestibular aqueduct (EVA) is the most common inner ear malformation identified in patients with sensorineural hearing loss. EVA is associated with pathogenic variants in SLC26A4. However, in European–Caucasian populations, about 50% of patients with EVA carry no pathogenic alleles of SLC26A4 . We tested for the presence of variants in CHD7 , a gene known to be associated with CHARGE syndrome, Kallmann syndrome, and hypogonadotropic hypogonadism, in a cohort of 34 families with EVA subjects without pathogenic alleles of SLC26A4 . In two families, NM_017780.4: c.3553A > G [p.(Met1185Val)] and c.5390G > C [p.(Gly1797Ala)] were detected as monoallelic CHD7 variants in patients with EVA. At least one subject from each family had additional signs or potential signs of CHARGE syndrome but did not meet diagnostic criteria for CHARGE. In silico modeling of these two missense substitutions predicted detrimental effects upon CHD7 protein structure. Consistent with a role of CHD7 in this tissue, Chd7 transcript and protein were detected in all epithelial cells of the endolymphatic duct and sac of the developing mouse inner ear. These results suggest that some CHD7 variants can cause nonsyndromic hearing loss and EVA. CHD7 should be included in DNA sequence analyses to detect pathogenic variants in EVA patients. Chd7 expression and mutant phenotype data in mice suggest that CHD7 contributes to the formation or function of the endolymphatic sac and duct.

Afforestation triggers water mining and a single pulse of water for carbon trade-off in deep soil - Huijie Li; Han Li; Qifan Wu; Bingcheng Si; Esteban G. Jobbágy; Jeffrey J. McDonnell (Agriculture, Ecosystems & Environment, 2023)

Functional traits explain waterbirds' host status, subtype richness, and community‐level infection risk for avian influenza - Shenglai Yin; Ning Li; Wenjie Xu; Daniel J. Becker; Willem F. de Boer; Chi Xu; Taej Mundkur; Nicholas M. Fountain‐Jones; Chunlin Li; Guan‐zhu Han; Qiang Wu; Diann J. Prosser; et al. (Ecology Letters, 2023)
Species functional traits can influence pathogen transmission processes, and consequently affect species' host status, pathogen diversity, and community‐level infection risk. We here investigated, for 143 European waterbird species, effects of functional traits on host status and pathogen diversity (subtype richness) for avian influenza virus at species level. We then explored the association between functional diversity and HPAI H5Nx occurrence at the community level for 2016/17 and 2021/22 epidemics in Europe. We found that both host status and subtype richness were shaped by several traits, such as diet guild and dispersal ability, and that the community‐weighted means of these traits were also correlated with community‐level risk of H5Nx occurrence. Moreover, functional divergence was negatively associated with H5Nx occurrence, indicating that functional diversity can reduce infection risk. Our findings highlight the value of integrating trait‐based ecology into the framework of diversity–disease relationship, and provide new insights for HPAI prediction and prevention.

P26-12: Acute and subacute toxicity profiles in Sprague-Dawley (SD) rats treated with Piperis Longi Fructus (PLF) aqueous extract - Y.-B. Kim; W.-J. Im; K.-H. Han (Toxicology Letters, 2023)

P26-11: Acute and subacute toxicity profiles in Sprague-Dawley (SD) rats treated with Piperis Longi Fructus (PLF) Powder - K.-H. Han; W.-J. Im; Y.-B. Kim (Toxicology Letters, 2023)

P24-13: Round Robin Study in Korea on alternative test method for evaluating skin irritation potential of medical devices - J. Yi; Y.S. Park; J.E. Im; H.-W. Moon; J.H. Kim; K.J. Kim; H.S. Yoon; Y. Lee; H.J. Ko; I.S. Kim; J.S. Kim; J.-S. Han; et al. (Toxicology Letters, 2023)

P19-07: 13-week repeated-dose oral toxicity study in rats treated with a mixture of Cirsium japonicum and Brassica oleracea extracts - W.-J. Im; M.-H. Yang; H. Park; J.-S. Han; J.-W. Cho; M.H. Yoo; Y.-B. Kim (Toxicology Letters, 2023)

Hydrodynamics and sliding posture analysis of the Cambrian arthropod Ercaicunia multinodosa - Yu-Han Li; Zu-Peng Zhou; Da-You Zhai; Robert J. O'Flynn; Jun Tang; Jin-Wei Xu; Xu-Guang Zhou; Yu Liu (Palaeoworld, 2023)

Molecular defense responses to natural enemies determine seedling survival in a subtropical forest - Hui Shang; Yunquan Wang; Baocai Han; Franca J. Bongers; Xiangcheng Mi; Lei Chen; Yu Liang; Keping Ma (Forest Ecology and Management, 2023)

Are medication effects on subjective response to alcohol and cue-induced craving associated? A meta regression study - Lara A. Ray; Steven J. Nieto; Lindsay R. Meredith; Elizabeth Burnette; Suzanna Donato; Molly Magill; Han Du (Psychopharmacology, 2023)
Rationale Alcohol administration and cue-reactivity paradigms are frequently used to screen for the initial efficacy of medications for alcohol use disorder (AUD). While medication effects on the primary outcomes for these paradigms are assumed to be qualitatively related, there is a critical lack of quantitative evidence to support this hypothesis. Objectives The study aims to test the relationship between medication effect sizes on subjective response to alcohol administration and medication effect sizes for cue-induced craving to cue exposure, using meta-analysis. Methods Systematic literature searches were conducted to identify randomized trials, wherein AUD medications were tested using the alcohol administration and/or cue-reactivity paradigms. From these studies, descriptive statistics were collected to compute medication effect sizes on the primary outcomes for each respective paradigm. With medication as the unit of analysis, medication effect sizes in alcohol administration studies were compared with medication effect sizes in cue-reactivity studies using the Williamson-York regression which allows for meta-regression across independent samples. Results Medication effect sizes on alcohol-induced stimulation and alcohol-induced craving were not significantly associated with medication effect sizes on cue-induced alcohol craving ( k stimulation = 10 medications, $$\widehat{β }=0.272 \left(SE=0.263\right), p=0.150$$ β ^ = 0.272 SE = 0.263 , p = 0.150 and k craving = 11 medications, $$\widehat{β }=0.217$$ β ^ = 0.217 (SE = 0.237), $$p=0.181$$ p = 0.181 ), respectively. Medication effect sizes on alcohol-induced sedation were significantly associated with medication effects on cue-induced craving ( k = 10 medications, $$\widehat{β }=-0.600$$ β ^ = - 0.600 (SE = 0.258), $$p=0.010$$ p = 0.010 ), such that medications that increased alcohol-induced sedation were more likely to reduce cue-induced alcohol craving. Conclusions With the exception of alcohol-induced sedation, there is little quantitative evidence of medication effects on subjective response domains measured during alcohol administration parallel medication effects on cue-induced alcohol craving. To provide additional context to the current study, future work should examine whether cue-reactivity findings predict clinical trial outcomes.

RNA sequencing reveals a complete picture of a homozygous missense variant in a patient with VPS13D movement disorder: a case report and review of the literature - Elizabeth K. Baker; Jingfen Han; William A. Langley; Michael A. Reott; Barbara E. Hallinan; Robert J. Hopkin; Wenying Zhang (Molecular Genetics and Genomics, 2023)

Efficient denitrification by a salt-tolerant aerobic compound bacteria agent AHM M3: optimizing composition and reduction conditions - H. Ma; Y. Liu; X. Mu; J. Song; X. Su; Y. Wu; R. Han (International Journal of Environmental Science and Technology, 2023)

An evolving view on food viscosity regulating gastric emptying - Yangyi Jin; Peter J. Wilde; Yingying Hou; Yanping Wang; Jianzhong Han; Weilin Liu (Critical Reviews in Food Science and Nutrition, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Co-proliferation of antimicrobial resistance genes in tilapia farming ponds associated with use of antimicrobials - Min Zhou; Qi Li; Shen Yu; Han Han; Nicholas J. Osborne (Science of The Total Environment, 2023)

Fellowship of the Spring: An initiative to document and protect the world's oases - Roderick J. Fensham; Rouhollah Adinehvand; Sally Babidge; Marco Cantonati; Matthew Currell; Linda Daniele; Alper Elci; Diana M.P. Galassi; África de la Hera Portillo; Salah Hamad; Dongmei Han; Hussain Ali Jawadi; et al. (Science of The Total Environment, 2023)

Age-related reductions in within-individual variation increase the repeatability of mating behaviour - Chang S. Han; Niels J. Dingemanse (Behavioral Ecology and Sociobiology, 2023)

The AFB1 auxin receptor controls the cytoplasmic auxin response pathway in Arabidopsis thaliana - Shiv Mani Dubey; Soeun Han; Nathan Stutzman; Michael J. Prigge; Eva Medvecká; Matthieu Pierre Platre; Wolfgang Busch; Matyáš Fendrych; Mark Estelle (Molecular Plant, 2023)

Reduction in productivity of soybean plants infested with Neohyadatothrips variabilis (Thysanoptera: Thripidae) with and without soybean vein necrosis virus - Doris M. Lagos-Kutz; Michelle L. Pawlowski; Jaeyeong Han; Steven J. Clough; Glen L. Hartman (Phytoparasitica, 2023)
Soybean thrips, Neohyadatothrips variabilis (Beach), a vector of Soybean Vein Necrosis Virus (SVNV), has been recognized as a widespread pest of soybean [ Glycine max (L.) Merr.] in USA and Canada. Several experiments investigated the effect on soybean when infested with soybean thrips with and without SVNV. Experiment 1 compared soybean infested at V1 and V5 growth stages (GS) with soybean thrips without SVNV and noninfested plants. For plants infested at GS V1, plant height, number of seeds, and seed weights were reduced by 50, 80, and 75%, respectively. When plants were infested at GSs V1 and V5, the counts of soybean thrips peaked at 1,803 and 4,214 per plant 4 weeks after infestation (WAI), respectively. Experiment 2 used SVNV-infected soybean thrips and compared soybean infested versus control at GS V1 and V5. For plants infested at GS V1, plant height was reduced 77.8%, and plants died before setting pods. For plants infested at GS V5, height, number of seeds, and seed weights were reduced 56, 78, and 92%, respectively. When plants were infested at GSs V1 and V5, the counts of soybean thrips peaked at 282 and 883 per plant 2 WAI, respectively. Experiment 3, five soybean genotypes were infested with SVNV-infected thrips at GS V1. Number and weight of seeds per plant were higher and with lower visual disease ratings (progressive chlorosis, necrosis and rugosity) for the more resistant genotypes Merschman Kennedy and plant introduction (PI) 171451 than for the more susceptible genotypes: soybean breeding line LD12-12734a ( Rag1/2 ), cv Williamsfield Illini 3509N, and PI 417136.

Rebound effect of carbon emissions of new energy vehicle consumption: a case study of Beijing - J. Zhou; W. Fang; X. Han; Q. Sun; D. Liu; S. Liu (International Journal of Environmental Science and Technology, 2023)

Variation of the photosynthesis and respiration response of filamentous algae (Oedogonium) acclimated to averaged seasonal temperatures and light exposure levels - Sulochana Pitawala; Zlatan Trifunovic; Joel R. Steele; Han-Chung Lee; Nicholas D. Crosbie; Peter J. Scales; Gregory J.O. Martin (Algal Research, 2023)

Global leaf‐trait mapping based on optimality theory - Ning Dong; Benjamin Dechant; Han Wang; Ian J. Wright; Iain Colin Prentice (Global Ecology and Biogeography, 2023)
Aim Leaf traits are central to plant function, and key variables in ecosystem models. However recently published global trait maps, made by applying statistical or machine‐learning techniques to large compilations of trait and environmental data, differ substantially from one another. This paper aims to demonstrate the potential of an alternative approach, based on eco‐evolutionary optimality theory, to yield predictions of spatio‐temporal patterns in leaf traits that can be independently evaluated. Innovation Global patterns of community‐mean specific leaf area (SLA) and photosynthetic capacity ( V cmax ) are predicted from climate via existing optimality models. Then leaf nitrogen per unit area ( N area ) and mass ( N mass ) are inferred using their (previously derived) empirical relationships to SLA and V cmax . Trait data are thus reserved for testing model predictions across sites. Temporal trends can also be predicted, as consequences of environmental change, and compared to those inferred from leaf‐level measurements and/or remote‐sensing methods, which are an increasingly important source of information on spatio‐temporal variation in plant traits. Main conclusions Model predictions evaluated against site‐mean trait data from > 2,000 sites in the Plant Trait database yielded R 2 = 73% for SLA, 38% for N mass and 28% for N area . Declining species‐level N mass , and increasing community‐level SLA, have both been recently reported and were both correctly predicted. Leaf‐trait mapping via optimality theory holds promise for macroecological applications, including an improved understanding of community leaf‐trait responses to environmental change.

Calibration of high-fidelity hydrodynamic models utilizing on-site vessel response measurements - Gowtham Radhakrishnan; Xu Han; Bernt J. Leira; Zhen Gao; Svein Sævik (Ocean Engineering, 2023)

Signatures of midsummer droughts over Central America and Mexico - Zijie Zhao; Meng Han; Kai Yang; Neil J. Holbrook (Climate Dynamics, 2023)
The annual cycle of precipitation over most parts of Central America and southern Mexico is climatologically characterized by a robust bimodal distribution, normally termed as the midsummer drought (MSD), influencing a large range of agricultural economic and public insurances. Compared to studies focusing on mechanisms underpinning the MSD, less research has been undertaken related to its climatological signatures. This is due to a lack of generally accepted methods through which to detect and quantify the bimodal precipitation accurately. The present study focuses on characterizing the MSD climatological signatures over Central America and Mexico using daily precipitation observations between 1979 and 2017, aiming to provide a comprehensive analysis of MSD in fine scale over this region. This was completed using a new method of detection. The signatures were analyzed from three aspects, namely (1) climatological mean states and variability; (2) connections with large scale modes of climate variability (El Niño–Southern Oscillation (ENSO) and the Madden–Julian Oscillation (MJO)); and (3) the potential afforded by statistical modelling. The development of MSDs across the region is attributed to changes of surface wind–pressure composites, characterized by anomalously negative (positive) surface pressure and onshore (offshore) winds during the peak (trough) of precipitation. ENSO’s modulation of MSDs is also shown by modifying the surface wind–pressure patterns through MSD periods, inducing the intensified North Atlantic Subtropical High and associated easterlies from the Caribbean region, which induce relatively weak precipitation at corresponding time points and subsequently intensify the MSD magnitude and extend the MSD period. Building on previous research which showed MSDs tend to start/end in MJO phases 1 and 8, a fourth–order polynomial was used here to statistically model the precipitation time series during the rainy season. We show that the strength of the bimodal precipitation can be well modelled by the coefficient of the polynomial terms, and the intra-seasonal variability is largely covered by the MJO indices. Using two complete MJO cycles and the polynomial, the bimodal precipitation during the rainy season over Central America and Mexico is synoptically explained, largely contributing to our understanding of the MJO’s modulation on the MSD.

Detection of a mid-Holocene climate event at 7.2 ka BP based on an analysis of globally-distributed multi-proxy records - Mei Hou; Wenxiang Wu; David J. Cohen; Zhaoqi Zeng; Han Huang; Hongbo Zheng; Quansheng Ge (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Spinning in circles? A systematic review on the role of theory in social vulnerability, resilience and adaptation research - Christian Kuhlicke; Mariana Madruga de Brito; Bartosz Bartkowski; Wouter Botzen; Canay Doğulu; Sungju Han; Paul Hudson; Ayse Nuray Karanci; Christian J. Klassert; Danny Otto; Anna Scolobig; Thais Moreno Soares; et al. (Global Environmental Change, 2023)

Influence of formic acid esterified cellulose nanofibrils on compressive strength, resilience and thermal stability of polyvinyl alcohol-xylan hydrogel - Wei Fang; Tao Song; Lisheng Wang; Tingting Han; Zhouyang Xiang; Orlando J. Rojas (Carbohydrate Polymers, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Intraspecific trait variation and species turnover in successional tropical forests: assessing trait imputation for community-weighted means - J. Aaron Hogan; Han Xu; Christopher Baraloto (Plant Ecology, 2023)

An assessment model for mapping the susceptibility of deposits accumulation on insulators driven by remotely sensed data - G. Wen; G. Han; F. Zhou; L. Shen; Y. Ma; G. Qian; H. Pan; P. Kong; J. Luo (International Journal of Environmental Science and Technology, 2023)

Soil grit influences the effects of earthworms (Lumbricus terrestris) on seed damage - Shu Han Gan; Michael J. McTavish; Robert S. Bourchier; Sandy M. Smith (Applied Soil Ecology, 2023)

The Anthropocene as an epoch is distinct from all other concepts known by this term: a reply to Swindles et al. (2023) - Martin J. Head; Colin N. Waters; Jan A. Zalasiewicz; Anthony D. Barnosky; Simon D. Turner; Alejandro Cearreta; Reinhold Leinfelder; Francine M.G. McCarthy; Daniel de B. Richter; Neil L. Rose; Yoshiki Saito; Davor Vidas; et al. (Journal of Quaternary Science, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Where land meets sea: Intertidal areas as key‐habitats for sharks and rays - Guido Leurs; Brian O. Nieuwenhuis; Thije J. Zuidewind; Nadia Hijner; Han Olff; Laura L. Govers (Fish and Fisheries, 2023)
Intertidal habitats (i.e. marine habitats that are (partially) exposed during low tide) have traditionally been studied from a shorebird‐centred perspective. We show that these habitats are accessible and important to marine predators such as elasmobranchs (i.e. sharks and rays). Our synthesis shows that at least 43 shark and 45 ray species, of which 54.5% are currently threatened, use intertidal habitats. Elasmobranchs use intertidal habitats mostly for feeding and as refugia, but also for parturition and thermoregulation. However, the motivation of intertidal habitat use remains unclear due to limitations to observe elasmobranch behaviour in these dynamic habitats. We argue that elasmobranch predators can play an important role in intertidal food webs by feeding on shared resources during high tide (i.e. ‘high‐tide predators’), which are accessible and also consumed by terrestrial or avian predators during low tide (i.e. ‘low‐tide predators’). In addition, elasmobranchs are able to change the bio‐geomorphology of intertidal habitats by increasing habitat heterogeneity due to feeding activities and may also alter resource availability for other consumers. We discuss how the ecological role of elasmobranchs in intertidal habitats is being affected by the continued overexploitation of these species, and conversely, how the global loss of intertidal areas poses an additional threat to an already vulnerable taxonomic group. We conclude that studies on intertidal ecology should include both low‐tide (e.g. shorebirds) and high‐tide (e.g. elasmobranchs) predatory guilds and their ecological interactions. The global loss of elasmobranch predatory species and intertidal habitat provides additional compelling arguments for the conservation of these areas.

Transfer learning in a biomaterial fibrosis model identifies in vivo senescence heterogeneity and contributions to vascularization and matrix production across species and diverse pathologies - Christopher Cherry; James I. Andorko; Kavita Krishnan; Joscelyn C. Mejías; Helen Hieu Nguyen; Katlin B. Stivers; Elise F. Gray-Gaillard; Anna Ruta; Jin Han; Naomi Hamada; Masakazu Hamada; Ines Sturmlechner; et al. (GeroScience, 2023)

Impact of food viscosity on in vitro gastric emptying using dynamic and semi-dynamic models - Yangyi Jin; Peter J. Wilde; Chenping Li; Weiping Jin; Jianzhong Han; Weilin Liu (Food Hydrocolloids, 2023)

Catalytic modification of corn straw facilitates the remediation of Cd contaminated water and soil - Jie Huang; Yunhong Jiao; Anthony J. Weatherley; Alex Xiaofei Duan; Shutao Wang; Chaoyu Li; Zhiling Ma; Wei Liu; Bing Han (Journal of Hazardous Materials, 2023)

Response to Merritts et al. (2023): The Anthropocene is complex. Defining it is not - Colin N. Waters; Martin J. Head; Jan Zalasiewicz; Francine M.G. McCarthy; Scott L. Wing; Peter K. Haff; Mark Williams; Anthony D. Barnosky; Barbara Fiałkiewicz-Kozieł; Reinhold Leinfelder; J.R. McNeill; Neil L. Rose; et al. (Earth-Science Reviews, 2023)

Fitness consequences of oviposition choice by an herbivorous insect on a host plant colonized by an endophytic entomopathogenic fungus - Hui Zhu; Jun Fu; Han Wang; Michael J. Bidochka; Mingyi Duan; Wenjing Xu; Li Sui; Bingzhong Ren; Qiyun Li; Zhengkun Zhang (Journal of Pest Science, 2023)

Life cycle-carbon footprints for environmental performance/labeling of crop-based food products: analyses of complementary functional units and hotspots - N. C. O; S. C. Pak; R. J. Ri; H. I. Han (International Journal of Environmental Science and Technology, 2023)

Identification for discharged characteristics of fine particulate matter from coke chemical industry in northern China - J. Luo; X. Feng; H. Han; N. Wang (International Journal of Environmental Science and Technology, 2023)

Alteration in Cerebral Metabolism in a Rodent Model of Acute Sub-lethal Cyanide Poisoning - Oladunni Alomaja; Frances S. Shofer; John C. Greenwood; Sarah Piel; Carly Clayman; Clementina Mesaros; Shih-Han Kao; Samuel S. Shin; Johannes K. Ehinger; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2023)

The metamicrobiome: key determinant of the homeostasis of nutrient recycling - Inger K. de Jonge; Michiel P. Veldhuis; J. Hans C. Cornelissen; Matty P. Berg; Han Olff (Trends in Ecology & Evolution, 2023)

Sustainability assessment of feedstock powder reuse for Directed Laser Deposition - J. Joju; D. Verdi; W.S. Han; L.Y. Hang; N. Soh; C.C. Hampo; N. Liu; S.S. Yang (Journal of Cleaner Production, 2023)

Comparison of Prospective and Retrospective Gated 4D Flow Cardiac MR Image Acquisitions in the Carotid Bifurcation - Elliott R. Hurd; Mengjiao Han; Jason K. Mendes; J. Rock Hadley; Chris R. Johnson; Edward V. R. DiBella; John N. Oshinski; Lucas H. Timmins (Cardiovascular Engineering and Technology, 2023)

Responses of a semiarid grassland to recurrent drought are linked to community functional composition - Wentao Luo; Taofeek O. Muraina; Robert J. Griffin‐Nolan; Wang Ma; Lin Song; Wei Fu; Qiang Yu; Alan K. Knapp; Zhengwen Wang; Xingguo Han; Scott L. Collins (Ecology, 2023)
Recurrent droughts are an inevitable consequence of climate change, yet how grasslands respond to such events is unclear. We conducted a 6‐year rainfall manipulation experiment in a semiarid grassland that consisted of an initial 2‐year drought (2015–2016), followed by a recovery period (2017–2018) and, finally, a second 2‐year drought (2019–2020). In each year, we estimated aboveground net primary productivity (ANPP), species richness, community‐weighted mean (CWM) plant traits, and several indices of functional diversity. The initial drought led to reduced ANPP, which was primarily driven by limited growth of forbs in the first year and grasses in the second year. Total ANPP completely recovered as the rapid recovery of grass productivity compensated for the slow recovery of forb productivity. The subsequent drought led to a greater reduction in total ANPP than the initial drought due to the greater decline of both grass and forb productivity. The structural equation models revealed that soil moisture influenced ANPP responses directly during the initial drought, and indirectly during the subsequent drought by lowering functional diversity, which resulted in reduced total ANPP. Additionally, ANPP was positively influenced by CWM plant height and leaf nitrogen during the recovery period and recurrent drought, respectively. Overall, the greater impact of the second drought on ecosystem function than the initial drought, as well as the underlying differential mechanism, underscores the need for an understanding of how increased drought frequency may alter semiarid grassland functioning.

Rapid preparation of nickel fluoride motif via solution-free plasma route for high-energy aqueous hybrid supercapacitor - Nilesh R. Chodankar; Indrajit V. Bagal; Swati J. Patil; Seung-Kyu Hwang; Pragati A. Shinde; Amar M. Patil; Smita V. Karekar; Amal Al Ghaferi; Wenli Zhang; Sang-Wan Ryu; Yun Suk Huh; Young Kyu Han (Chemical Engineering Journal, 2023)

Thermally insulating and electroactive cellular nanocellulose composite cryogels from hybrid nanofiber networks - Yi Hu; Meilian Cao; Jianing Xu; Xueying Liu; Jiqing Lu; Jie Yan; Siqi Huan; Guangping Han; Long Bai; Wanli Cheng; Orlando J. Rojas (Chemical Engineering Journal, 2023)

Composites based on electrospun fibers modified with cellulose nanocrystals and SiO2 for selective oil/water separation - Dong Wang; Sameer Mhatre; Jingqian Chen; Xuetong Shi; Haiying Yang; Wanli Cheng; Yiying Yue; Guangping Han; Orlando J. Rojas (Carbohydrate Polymers, 2023)

Correction to: Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Probing the nature of soil organic matter - Zhe (Han) Weng; Johannes Lehmann; Lukas Van Zwieten; Stephen Joseph; Braulio S. Archanjo; Bruce Cowie; Lars Thomsen; Mark J. Tobin; Jitraporn Vongsvivut; Annaleise Klein; Casey L. Doolette; Helen Hou; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Duration- and sex-dependent neural circuit control of voluntary physical activity - Margaret K. Tanner; Jazmyne K. P. Davis; Jennifer Jaime; Nicolette A. Moya; Alyssa A. Hohorst; Kelsey Bonar; Kelsey A. Abrams; Nashra Jamil; Rebecca Han; Troy J. Hubert; Nadja Brown; Esteban C. Loetz; et al. (Psychopharmacology, 2022)

Characterization and thermal removal of organophosphorus pesticides in soils from a former agrochemical factory - W. Han; Y. Ye; S. Liu; J. Sima (International Journal of Environmental Science and Technology, 2022)

Genetic diversity, lineage divergence, and demography of Diaphanosoma dubium (Crustacea: Cladocera) on Hainan Island, China - Ping Liu; Xiaoli Zhang; Qi Huang; Eric Zeus C. Rizo; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2022)

Fossilized diatoms as indirect indicators of the origin of carbon stored in intertidal flats - El-Hacen M. El-Hacen; Ties Mens; Tjeerd J. Bouma; Theunis Piersma; Suzanne A.G. Leroy; Han Olff; Francesca Sangiorgi (Frontiers in Marine Science, 2022)
Coastal systems store enormous carbon quantities in their sediment, which originates from various autochthonous and allochthonous sources. Carbon fluxes in coastal ecosystems have a strong effect on the recipient food-webs and carbon emission offsets. Yet, the relative importance of autochthonous vs. allochthonous C inputs to coastal carbon budget is still challenging to identify. Here, we combine diatoms preserved in the sediment with geochemical analyses to identify the sources of carbon stored in Africa’s largest intertidal seagrass beds at Banc d’Arguin, Mauritania. The area lies between an active ocean upwelling and the ‘Sahara-dust hotspot’ systems. The extensive seagrass beds of the area are thus expected to receive C from these neighboring systems in addition to producing C in-situ . Three sediment cores (50 cm) were collected at three intertidal sites with different hydrodynamic regimes, and analyzed for diatom composition, total organic carbon (TOC), total nitrogen (TN), total phosphorus (TP), and carbon isotopic signatures (δ 13 C). Diatom taxa are grouped into three guilds: (1) benthic (epiphyte, epipelon, and epipsammon), (2) planktonic, and (3) freshwater. Benthic diatoms are considered to be autochthonous, while typical oceanic and freshwater diatoms are considered to be allochthonous. Benthic diatoms are the most diverse and abundant group, while allochthonous freshwater (i.e., dust imported) and typical upwelling (i.e., tidal imported) taxa ranked last in both abundance and species’ richness. Structure equation modelling shows that variation in the stored carbon is best explained by the total abundance of diatoms and guild composition. We conclude that the C stored in the intertidal seagrass beds of Banc d’Arguin is predominantly autochthonous. Our method provides an effective way to identify historical carbon sources in coastal systems.

The proposed Anthropocene Epoch/Series is underpinned by an extensive array of mid‐20 th century stratigraphic event signals - Martin J. Head; Jan A. Zalasiewicz; Colin N. Waters; Simon D. Turner; Mark Williams; Anthony D. Barnosky; Will Steffen; Michael Wagreich; Peter K. Haff; Jaia Syvitski; Reinhold Leinfelder; Francine M. G. Mccarthy; et al. (Journal of Quaternary Science, 2022)
The extensive array of mid‐20 th century stratigraphic event signals associated with the ‘Great Acceleration’ enables precise and unambiguous recognition of the Anthropocene as an epoch/series within the Geological Time Scale. A mid‐20 th century inception is consistent with Earth System science analysis in which the Anthropocene term and concept arose, and would reflect the reality that our planet has sharply exited the range of natural variability characterizing the Holocene Epoch/Series, which the Anthropocene would therefore terminate. An alternative, recently proposed ‘geological event’ approach to the Anthropocene is primarily an interdisciplinary concept, encompassing historical and socio‐cultural processes and their global environmental impacts over a diachronous timeframe that extends back at least many millennia. Resembling more closely a geological episode than an event , it would decouple the Anthropocene from its chronostratigraphic delineation and association with an abrupt planetary perturbation; but separately defined and differently named it might be usefully complementary. We recommend a clear separation of epochs , events and episodes . An epoch is a formal subdivision of the Geological Time Scale, and its correlation may be assisted by one or more events ; an event is usually, and particularly in the Quaternary, a brief incident or perturbation with a sedimentary expression; and an episode is a longer, internally complex time interval that may include several events and even extend across several epochs.

Pore development in terrestrial shale reservoirs: the Permian Lucaogou Formation, Junggar Basin, northwestern China - Y. Jin; J. Tian; C. Han; H. Liu; L. Dong; S. Dan (Australian Journal of Earth Sciences, 2022)

Pilot Study of an Encounter Decision Aid for Lung Cancer Screening - Mayuko Ito Fukunaga; Akshu Balwan; Jaclyn A. Janis; Caitlin Gutheil; Jason Yahwak; Paul K. J. Han (Journal of Cancer Education, 2022)

Factors associated with symptoms of poor mental health among women factory workers in China’s supply chain - K. K. Sznajder; S. D. Harlow; J. Wang; L. Tso; Y. Ashagre; C. Han (International Archives of Occupational and Environmental Health, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

The global biogeography of soil priming effect intensity - Chengjie Ren; Fei Mo; Zhenghu Zhou; Felipe Bastida; Manuel Delgado‐Baquerizo; Jieying Wang; Xinyi Zhang; Yiqi Luo; Timothy J. Griffis; Xinhui Han; Gehong Wei; Jun Wang; et al. (Global Ecology and Biogeography, 2022)
Aim Fresh carbon (C) inputs to the soil can have important consequences for the decomposition rates of soil organic matter (priming effect), thereby impacting the delicate global C balance at the soil–atmosphere interface. Yet, the environmental factors that control soil priming effect intensity remain poorly understood at a global scale. Location Global. Time period 1980–2020. Major taxa studied Soil priming effect intensity. Methods We conducted a global dataset of CO 2 effluxes in 711 pairwise soils with 13 C or 14 C simple C sources inputs and without C inputs from incubation experiments in which isotope‐labelled C was used to quantify fresh C‐induced rather than exudate‐induced priming. Results Soil priming effect intensity is predominantly positive. Soil texture and C content were identified as the most important factors associated with priming effects, with sandy soils from tropical and mid‐latitudes supporting the highest soil priming effect intensity, and soils with greater C content and fine textures from high latitudes maintaining the lowest soil priming effects. The negative association between C content and soil priming effect intensity was also indirectly driven by changing mean annual temperature, net primary productivity, and fungi : bacteria ratio. Using this information, we generated a global map of soil priming effect intensity, and found that the priming was lower at high latitudes and higher at lower latitudes. Main conclusions Global patterns of soil priming effect intensity can be predicted using environmental data, with soil texture and C content playing a predominant role in explaining in priming effects. These effects were also indirectly driven by climate, vegetation and soil microbial properties. We present the first global atlas of soil priming effect intensity and advance our knowledge on the potential mechanisms underlying soil priming effect intensity, which are integral to improving the climate change and soil C dynamics components of Earth System models.

Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2022)

Environmental analysis of methanol production from coke oven gas - D. Kang; J. Han (International Journal of Environmental Science and Technology, 2022)

Mechanical properties and fracture evolution process of Beishan granite under tensile state - C. S. Wang; J. F. Liu; Y. W. Zhao; S. J. Han (Bulletin of Engineering Geology and the Environment, 2022)

The role of context in identifying linkages between SDG 2 (food) and SDG 6 (water) - Han Su; Maarten S. Krol; Rick J. Hogeboom (Sustainability Science, 2022)
The Sustainable Development Goals (SDGs) of the United Nation’s Agenda 2030 are formulated to promote the development of integrated, multisectoral policies that explicitly consider linkages across SDGs. Although multiple recent studies have tried to identify linkages across SDGs, the role of contextual factors in identifying SDG linkages is neither well described nor understood. For the case of SDG 2 and SDG 6, this study aims to (i) identify linkages—at country and SDG target level—through the application of various quantitative and qualitative identification methods, and (ii) explore contextual factors to explain the differences across identified linkages. Hereto, we first conducted a text analysis of 195 Voluntary National Reviews (VNRs) reported by 159 countries from 2016 to 2020. Next, we synthesized linkages reported by previous qualitative studies and conducted a quantitative (correlation) analysis on the UN’s SDG database. Last, we compared identified linkages across methods, paying special attention to the role of context. From the text analysis, we identified 221 country-specific linkages between 25 SDG target pairs and observed that countries increasingly report SDG linkages in their VNRs over time. Comparing text analysis, existing qualitative studies, and our quantitative correlation analysis, we found substantial differences between the number and nature of linkages identified. These differences can be explained in part by methodological considerations, but to a significant extent also by contextual factors, such as project design, technology application, phase of interventions, and project scale. We conclude by discussing the strengths and limitations of the methods involved, and suggestions for future studies.

A New Berberine Preparation Protects Pancreatic Islet Cells from Apoptosis Mediated by Inhibition of Phospholipase A2/p38 MAPK Pathway - X. J. Bi; Y. Q. Lv; X. H. Yang; Y. Ge; H. Han; J. S. Feng; M. Zhang; L. Chen; M. Z. Xu; F. Y. Guan (Bulletin of Experimental Biology and Medicine, 2022)

Immunosuppression Induced by Brain-Specific HDAC6 Knockdown Improves Aging Performance in Drosophila melanogaster - Yingying Zhao; Hongwen Xuan; Chao Shen; Peiyi Liu; Jing-Dong J. Han; Wei Yu (Phenomics, 2022)

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Trametes suaveolens-derived biochar loaded on nanoscale zero-valent iron particles for the adsorption and reduction of Cr(VI) - W.-D. Wang; H.-T. Ma; W. Lin; P. Sun; L.-K. Zhang; J.-H. Han (International Journal of Environmental Science and Technology, 2022)

Chronic and intense droughts differentially influence grassland carbon-nutrient dynamics along a natural aridity gradient - Wentao Luo; Xiaoan Zuo; Robert J. Griffin-Nolan; Chong Xu; Jordi Sardans; Qiang Yu; Zhengwen Wang; Xingguo Han; Josep Peñuelas (Plant and Soil, 2022)

A hypotonic gel-forming eye drop provides enhanced intraocular delivery of a kinase inhibitor with melanin-binding properties for sustained protection of retinal ganglion cells - Yoo Chun Kim; Henry T. Hsueh; Matthew D. Shin; Cynthia A. Berlinicke; Hyounkoo Han; Nicole M. Anders; Avelina Hemingway; Kirby T. Leo; Renee Ti Chou; HyeYoung Kwon; Matthew B. Appell; Usha Rai; et al. (Drug Delivery and Translational Research, 2022)

Characterization of orexin input to dopamine neurons of the ventral tegmental area projecting to the medial prefrontal cortex and shell of nucleus accumbens - Imre Kalló; Azar Omrani; Frank J. Meye; Han de Jong; Zsolt Liposits; Roger A. H. Adan (Brain Structure and Function, 2022)
Orexin neurons are involved in homeostatic regulatory processes, including arousal and feeding, and provide a major input from the hypothalamus to the ventral tegmental area (VTA) of the midbrain. VTA neurons are a central hub processing reward and motivation and target the medial prefrontal cortex (mPFC) and the shell part of nucleus accumbens (NAcs). We investigated whether subpopulations of dopamine (DA) neurons in the VTA projecting either to the mPFC or the medial division of shell part of nucleus accumbens (mNAcs) receive differential input from orexin neurons and whether orexin exerts differential electrophysiological effects upon these cells. VTA neurons projecting to the mPFC or the mNAcs were traced retrogradely by Cav2-Cre virus and identified by expression of yellow fluorescent protein (YFP). Immunocytochemical analysis showed that a higher proportion of all orexin-innervated DA neurons projected to the mNAcs (34.5%) than to the mPFC (5.2%). Of all sampled VTA neurons projecting either to the mPFC or mNAcs, the dopaminergic (68.3 vs. 79.6%) and orexin-innervated DA neurons (68.9 vs. 64.4%) represented the major phenotype. Whole-cell current clamp recordings were obtained from fluorescently labeled neurons in slices during baseline periods and bath application of orexin A. Orexin similarly increased the firing rate of VTA dopamine neurons projecting to mNAcs (1.99 ± 0.61 Hz to 2.53 ± 0.72 Hz) and mPFC (0.40 ± 0.22 Hz to 1.45 ± 0.56 Hz). Thus, the hypothalamic orexin system targets mNAcs and to a lesser extent mPFC-projecting dopaminergic neurons of the VTA and exerts facilitatory effects on both clusters of dopamine neurons.

Climatic controls of Pinus pumila radial growth along an altitude gradient - Jingwen Yang; David J. Cooper; Xu Zhang; Wenqi Song; Zongshan Li; Yuandong Zhang; Huiying Zhao; Shijie Han; Xiaochun Wang (New Forests, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Moisture mediates temperature-growth couplings of high-elevation shrubs in the Tibetan plateau - Yang Han; Yafeng Wang; Bo Liu; Ru Huang; J. Julio Camarero (Trees, 2022)

Correction to: Profiling Basal Forebrain Cholinergic Neurons Reveals a Molecular Basis for Vulnerability Within the Ts65Dn Model of Down Syndrome and Alzheimer’s Disease - Melissa J. Alldred; Sai C. Penikalapati; Sang Han Lee; Adriana Heguy; Panos Roussos; Stephen D. Ginsberg (Molecular Neurobiology, 2022)

Evolution of the N-Terminal Regulation of Cardiac Troponin I for Heart Function of Tetrapods: Lungfish Presents an Example of the Emergence of Novel Submolecular Structure to Lead the Capacity of Adaptation - Monica Rasmussen; Han-Zhong Feng; J.-P. Jin (Journal of Molecular Evolution, 2022)

Current management of melanoma patients with nodal metastases - Dale Han; Alexander C. J. van Akkooi; Richard J. Straker; Adrienne B. Shannon; Giorgos C. Karakousis; Lin Wang; Kevin B. Kim; Douglas Reintgen (Clinical & Experimental Metastasis, 2022)

Integrated pest management of Tuta absoluta: practical implementations across different world regions - Nicolas Desneux; Peng Han; Ramzi Mansour; Judit Arnó; Thierry Brévault; Mateus R. Campos; Anais Chailleux; Raul N. C. Guedes; Javad Karimi; Kouassi Arthur J. Konan; Anne-violette Lavoir; María G. Luna; et al. (Journal of Pest Science, 2022)

Satellite All-sky Infrared Radiance Assimilation: Recent Progress and Future Perspectives - Jun Li; Alan J. Geer; Kozo Okamoto; Jason A. Otkin; Zhiquan Liu; Wei Han; Pei Wang (Advances in Atmospheric Sciences, 2022)
Satellite infrared (IR) sounder and imager measurements have become one of the main sources of data used by data assimilation systems to generate initial conditions for numerical weather prediction (NWP) models and atmospheric analysis/reanalysis. This paper reviews the development of satellite IR data assimilation in NWP in recent years, especially the assimilation of all-sky satellite IR observations. The major challenges and future directions are outlined and discussed.

The brown root rot fungus Phellinus noxius affects microbial communities in different root‐associated niches of Ficus trees - Tse‐Yen Liu; Chao‐Han Chen; Yu‐Liang Yang; Isheng J. Tsai; Ying‐Ning Ho; Chia‐Lin Chung (Environmental Microbiology, 2022)
Summary Brown root rot (BRR) caused by Phellinus noxius is a destructive tree disease in tropical and subtropical areas. To understand how BRR affects the composition of the plant rhizoplane‐enriched microbiota, the microbiomes within five root‐associated compartments (i.e., bulk soil, old/young root rhizosphere soil, old/young root tissue) of Ficus trees naturally infected by P. noxius were investigated. The level of P. noxius infection was determined by quantitative PCR. Illumina sequencing of the internal transcribed spacer and 16S rRNA revealed that P. noxius infection caused a significant reduction in fungal diversity in the bulk soil, the old root rhizosphere soil, and the old root tissue. Interestingly, Cosmospora was the only fungal genus positively correlated with P. noxius . The abundance and composition of dominant bacterial taxa such as Actinomadura , Bacillus , Rhodoplanes , and Streptomyces differed between BRR‐diseased and healthy samples. Furthermore, 838 isolates belonging to 26 fungal and 35 bacterial genera were isolated and tested for interactions with P. noxius . Antagonistic activities were observed for isolates of Bacillus , Pseudomonas , Aspergillus , Penicillium , and Trichoderma . Cellophane overlay and cellulose/lignin utilization assays suggested that Cosmospora could tolerate the secretions of P. noxius and that the degradation of lignin by P. noxius may create suitable conditions for Cosmorpora growth.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Toward a phylogeny and biogeography of Diaphanosoma (Crustacea: Cladocera) - Henri J. Dumont; Bo-Ping Han; Fei Fei Guo; Hua Chen; Dan Cheng; Ping Liu; Lei Xu; La-Orsri Sanoamuang; Arnola C. Rietzler; Shaolin Xu; Andy Vierstraete; Manuel Elias-Gutierrez (Aquatic Ecology, 2021)

Toward a phylogeny and biogeography of Diaphanosoma (Crustacea: Cladocera) - Henri J. Dumont; Bo-Ping Han; Fei Fei Guo; Hua Chen; Dan Cheng; Ping Liu; Lei Xu; La-Orsri Sanoamuang; Arnola C. Rietzler; Shaolin Xu; Andy Vierstraete; Manuel Elias-Gutierrez (Aquatic Ecology, 2021)

Development of microsatellite markers for Diaphanosoma dubium (Crustacea, Cladocera) and application to seasonal population dynamics - Ping Liu; Shao-Lin Xu; Jian Liao; Henri J. Dumont; Bo-Ping Han (Aquatic Ecology, 2021)

Profiling Basal Forebrain Cholinergic Neurons Reveals a Molecular Basis for Vulnerability Within the Ts65Dn Model of Down Syndrome and Alzheimer’s Disease - Melissa J. Alldred; Sai C. Penikalapati; Sang Han Lee; Adriana Heguy; Panos Roussos; Stephen D. Ginsberg (Molecular Neurobiology, 2021)

Stable isotopes (δ2H) in feathers identify non-breeding origins of the endangered Jankowski’s Bunting - Zheng Han; Hai-Tao Wang; Kevin J. Kardynal; Keith A. Hobson; Wei-Ping Shang; li-shi Zhang; Yun-lei Jiang; Frédéric Jiguet (Journal of Ornithology, 2021)

Plant traits and soil fertility mediate productivity losses under extreme drought in C 3 grasslands - Wentao Luo; Robert J. Griffin‐Nolan; Wang Ma; Bo Liu; Xiaoan Zuo; Chong Xu; Qiang Yu; Yahuang Luo; Pierre Mariotte; Melinda D. Smith; Scott L. Collins; Alan K. Knapp; et al. (Ecology, 2021)
Extreme drought decreases aboveground net primary production (ANPP) in most grasslands, but the magnitude of ANPP reductions varies especially in C 3 ‐dominated grasslands. Because the mechanisms underlying such differential ecosystem responses to drought are not well resolved, we experimentally imposed an extreme 4‐yr drought (2015–2018) in two C 3 grasslands that differed in aridity. These sites had similar annual precipitation and dominant grass species ( Leymus chinensis ) but different annual temperatures and thus water availability. Drought treatments differentially affected these two semiarid grasslands, with ANPP of the drier site reduced more than at the wetter site. Structural equation modeling revealed that community‐weighted means for some traits modified relationships between soil moisture and ANPP, often due to intraspecific variation. Specifically, drought reduced community mean plant height at both sites, resulting in a reduction in ANPP beyond that attributable to reduced soil moisture alone. Higher community mean leaf carbon content enhanced the negative effects of drought on ANPP at the drier site, and ANPP–soil‐moisture relationships were influenced by soil C:N ratio at the wetter site. Importantly, neither species richness nor functional dispersion were significantly correlated with ANPP at either site. Overall, as expected, soil moisture was a dominant, direct driver of ANPP response to drought, but differential sensitivity to drought in these two grasslands was also related to soil fertility and plant traits.

Mechanisms, physiology, and recent research progress of gastric emptying - Weilin Liu; Yangyi Jin; Peter J. Wilde; Yingying Hou; Yanping Wang; Jianzhong Han (Critical Reviews in Food Science and Nutrition, 2021)

Synthesis of a novel ZnFe2O4/porous biochar magnetic composite for Th(IV) adsorption in aqueous solutions - W. D. Wang; Y. X. Cui; L. K. Zhang; Y. M. Li; P. Sun; J. H. Han (International Journal of Environmental Science and Technology, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

The Internal Microenvironment of the Symbiotic Jellyfish Cassiopea sp. From the Red Sea - Silvia Arossa; Alan Barozzi; Matteo Callegari; Shannon G. Klein; Anieka J. Parry; Shiou-Han Hung; Alexandra Steckbauer; Manuel Aranda; Daniele Daffonchio; Carlos M. Duarte (Frontiers in Marine Science, 2021)
The characterization of the internal microenvironment of symbiotic marine invertebrates is essential for a better understanding of the symbiosis dynamics. Microalgal symbionts (of the family: Symbiodiniaceae) influence diel fluctuations of in host O 2 and pH conditions through their metabolic activities (i.e., photosynthesis and respiration). These variations may play an important role in driving oxygen budgets and energy demands of the holobiont and its responses to climate change. In situ measurements using microsensors were used to resolve the O 2 and pH diel fluctuations in the oral arms of non-calcifying cnidarian model species Cassiopea sp. (the “upside-down jellyfish”), which has an obligatory association with Symbiodiniaceae. Before sunrise, the internal O 2 and pH levels were substantially lower than those in ambient seawater conditions (minimum average levels: 61.92 ± 5.06 1SE μmol O 2 L –1 and 7.93 ± 0.02 1SE pH units, respectively), indicating that conditions within Cassiopea’s oral arms were acidified and hypoxic relative to the surrounding seawater. Measurements performed during the afternoon revealed hyperoxia (maximum average levels: 546.22 ± 16.45 1SE μmol O 2 L –1 ) and internal pH similar to ambient levels (8.61 ± 0.02 1SE pH units). The calculated gross photosynthetic rates of Cassiopea sp. were 0.04 ± 0.013 1SE nmol cm –2 s –1 in individuals collected at night and 0.08 ± 0.02 1SE nmol cm –2 s –1 in individuals collected during the afternoon.

Genetic diversity and population genetic structure in native Ethiopian donkeys (Equus asinus) inferred from equine microsatellite markers - E. Kefena; S. Rosenbom; A. Beja-Pereira; M. Yusuf Kurtu; J. L. Han; T. Dessie (Tropical Animal Health and Production, 2021)

Drought tolerance in selected aerobic and upland rice varieties is driven by different metabolic and antioxidative responses - Giovanni Melandri; Hamada AbdElgawad; Kristýna Floková; Diaan C. Jamar; Han Asard; Gerrit T. S. Beemster; Carolien Ruyter-Spira; Harro J. Bouwmeester (Planta, 2021)
Main conclusions Sugar-mediated osmotic acclimation and a strong antioxidative response reduce drought-induced biomass loss at the vegetative stage in rice. Abstract A clear understanding of the physiological and biochemical adaptations to water limitation in upland and aerobic rice can help to identify the mechanisms underlying their tolerance to low water availability. In this study, three indica rice varieties-IR64 (lowland), Apo (aerobic), and UPL Ri-7 (upland)-, that are characterized by contrasting levels of drought tolerance, were exposed to drought at the vegetative stage. Drought-induced changes in biomass, leaf metabolites and oxidative stress markers/enzyme activities were analyzed in each variety at multiple time points. The two drought-tolerant varieties, Apo and UPL Ri-7 displayed a reduced water use in contrast to the susceptible variety IR64 that displayed high water consumption and consequent strong leaf dehydration upon drought treatment. A sugar-mediated osmotic acclimation in UPL Ri-7 and a strong antioxidative response in Apo were both effective in limiting the drought-induced biomass loss in these two varieties, while biomass loss was high in IR64, also after recovery. A qualitative comparison of these results with the ones of a similar experiment conducted in the field at the reproductive stage showed that only Apo, which also in this stage showed the highest antioxidant power, was able to maintain a stable grain yield under stress. Our results show that different metabolic and antioxidant adaptations confer drought tolerance to aerobic and upland rice varieties in the vegetative stage. The effectiveness of these adaptations differs between developmental stages. Unraveling the genetic control of these mechanisms might be exploited in breeding for new rice varieties adapted to water-limited environments.

Diabetes Mellitus/Poststroke Hyperglycemia: a Detrimental Factor for tPA Thrombolytic Stroke Therapy - Yinghua Jiang; Ning Liu; Jinrui Han; Yadan Li; Pierce Spencer; Samuel J. Vodovoz; Ming-Ming Ning; Gregory Bix; Prasad V. G. Katakam; Aaron S. Dumont; Xiaoying Wang (Translational Stroke Research, 2021)

Exploring Health Literacy and the Correlates of Pap Testing Among African Immigrant Women: Findings from the AfroPap Study - Joycelyn Cudjoe; Chakra Budhathoki; Debra Roter; Joseph J. Gallo; Phyllis Sharps; Hae-Ra Han (Journal of Cancer Education, 2021)

Impact of tibetan plateau snow cover on tropical cyclogenesis via the Madden–Julian oscillation during the following boreal summer - Xiang Han; Haikun Zhao; Philip J. Klotzbach; Liguang Wu; Graciela B. Raga (Climate Dynamics, 2021)

Application of two-level design method on subway tunnel crossing active fault: a case study on Urumqi subway tunnel intersected by reverse fault dislocation - S. An; L. J. Tao; X. C. Han; Y. Zhang (Bulletin of Engineering Geology and the Environment, 2021)

Conservation Implications of Sabellaria spinulosa Reef Patches in a Dynamic Sandy-Bottom Environment - Karin J. van der Reijden; Leo Koop; Sebastiaan Mestdagh; Mirjam Snellen; Peter M. J. Herman; Han Olff; Laura L. Govers (Frontiers in Marine Science, 2021)
Biogenic reefs form biodiversity hotspots and are key components of marine ecosystems, making them priority habitats for nature conservation. However, the conservation status of biogenic reefs generally depends on their size and stability. Dynamic, patchy reefs may therefore be excluded from protection. Here, we studied epibenthos and epifauna density, richness, and community composition of patchy, dynamic Sabellaria spinulosa (ross worm) reefs in the North Sea. This study was conducted by comparing boxcore (endobenthos) and video transect (epifauna) data from two research campaigns in 2017 and 2019 to the Brown Bank area on the Dutch Continental Shelf, where S. spinulosa reefs were first discovered in 2017. The Brown Bank area is characterized by dynamic, migratory bedforms at multiple scales which potentially affect biogenic reef stability. We showed that S. spinulosa habitats had a patchy distribution and alternated with habitats comprised of plain sand. Average S. spinulosa habitat patch size was 5.57 ± 0.99 m and 3.94 ± 0.22 m in 2017 and 2019, respectively (mean ± SE), which especially in 2019 closely resembled the small-scale megaripple bedforms. Contrary to the endobenthos communities that were unaffected by S. spinulosa , epifauna density and species richness were at least two times higher in S. spinulosa habitats compared to sandy habitats, resulting in different community compositions between the two habitat types. We showed that S. spinulosa persisted in the area for almost 2 years. Although the stability of individual patches remained unclear, we demonstrated that even patchy biogenic reefs may promote density and local biodiversity of mobile, epibenthic species, very likely as a result of increased habitat heterogeneity provided by reef habitat patches. This indicates that patchy biogenic reefs that occur in dynamic environments may also have high ecological value and their conservation status should be (re)considered to ensure their protection.

ValSten: a new wild species derived allotetraploid for increasing genetic diversity of the peanut crop (Arachis hypogaea L.) - Dongying Gao; Ana C. G. Araujo; Eliza F. M. B. Nascimento; M. Carolina Chavarro; Han Xia; Scott A. Jackson; David J. Bertioli; Soraya C. M. Leal-Bertioli (Genetic Resources and Crop Evolution, 2021)
Introgression of desirable traits from wild relatives plays an important role in crop improvement, as wild species have important characters such as high resistance to pests and pathogens. However, use of wild peanut relatives is challenging because almost all wild species are diploid and sexually incompatible with cultivated peanut, which is tetraploid (AABB genome type; 2 n = 4x = 40). To overcome the ploidy barrier, we used 2 wild species to make a tetraploid with the same allotetraploid genome composition as cultivated peanut. Crosses were made between 2 diploid wild species, Arachis valida Krapov. and W.C. Greg. (BB genome; 2 n = 2x = 20) and Arachis stenosperma Krapov. and W.C. Greg. (AA genome; 2 n = 2x = 20). Cuttings from the diploid F 1 AB hybrid were treated with colchicine to induce chromosome doubling thus generating an induced allotetraploid. Chromosome counts confirmed polyploidy (AABB genome; 2 n = 4x = 40). We named the new allotetraploid ValSten. Plants had well-developed fertile pollen, produced abundant seed and were sexually compatible with cultivated peanut. ValSten exhibits the same high resistance to early and late leaf spot and rust as its diploid parents. Notably, we observed morphological variations, including flower width and branch angles in the earliest generation (S 0 ) of allotetraploids. A SNP array was used to genotype 47 S 0 allotetraploids. The great majority of markers showed the additive allelic state from both parents (AABB). However, some loci were AAAA or BBBB, indicating homeologous recombination. ValSten provides a new, vigorous, highly fertile, disease resistant germplasm for peanut research and improvement.

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

To the light side: molecular diversity and morphology of stomatopod larvae and juveniles (Crustacea: Malacostraca: Stomatopoda) from crustose coralline algal reefs in Taiwan - Kingsley J. H. Wong; Yao-Feng Tsao; Pei-Chen Tsai; Wei-Peng Hsieh; Han-Ru Li; Ryuji J. Machida; Benny K. K. Chan (Marine Biodiversity, 2021)

NABat: A top-down, bottom-up solution to collaborative continental-scale monitoring - Brian E. Reichert; Mylea Bayless; Tina L. Cheng; Jeremy T. H. Coleman; Charles M. Francis; Winifred F. Frick; Benjamin S. Gotthold; Kathryn M. Irvine; Cori Lausen; Han Li; Susan C. Loeb; Jonathan D. Reichard; et al. (Ambio, 2021)
Collaborative monitoring over broad scales and levels of ecological organization can inform conservation efforts necessary to address the contemporary biodiversity crisis. An important challenge to collaborative monitoring is motivating local engagement with enough buy-in from stakeholders while providing adequate top-down direction for scientific rigor, quality control, and coordination. Collaborative monitoring must reconcile this inherent tension between top-down control and bottom-up engagement. Highly mobile and cryptic taxa, such as bats, present a particularly acute challenge. Given their scale of movement, complex life histories, and rapidly expanding threats, understanding population trends of bats requires coordinated broad-scale collaborative monitoring. The North American Bat Monitoring Program (NABat) reconciles top-down, bottom-up tension with a hierarchical master sample survey design, integrated data analysis, dynamic data curation, regional monitoring hubs, and knowledge delivery through web-based infrastructure. NABat supports collaborative monitoring across spatial and organizational scales and the full annual lifecycle of bats.

Industrial Fishing Near West African Marine Protected Areas and Its Potential Effects on Mobile Marine Predators - Guido Leurs; Karin J. van der Reijden; Sidi Yahya Cheikhna Lemrabott; Iça Barry; Diosnes Manuel Nonque; Han Olff; Samuel Ledo Pontes; Aissa Regalla; Laura L. Govers (Frontiers in Marine Science, 2021)
Marine Protected Areas (MPAs) are increasingly implemented to facilitate the conservation of marine biodiversity and key habitats. However, these areas are often less effective to conserve mobile marine species like elasmobranchs (i.e., sharks and rays). Industrial fishing near MPA borders possibly impacts vulnerable species utilizing these protected areas. Hence, we aimed to study spatiotemporal patterns of industrial fisheries near MPAs, in relation to the bycatch of elasmobranchs. Specifically, we analyzed the spatiotemporal fishing effort within the West African region, mapped fishing effort in the direct vicinity of the Parc National du Banc d’Arguin (PNBA, Mauritania) and the Bijagós Archipelago (BA, Guinea Bissau), and compared the seasonal overlap between elasmobranch bycatch and fishing effort near these MPAs. We combined Automatic Identification System (AIS) data and local fisheries observer data, and determined fishing effort for each gear type and compared this with bycatch of elasmobranchs. We found that industrial fishing effort was dominated by trawling, drifting longlines, and fixed gear types. Although no industrial fishing was observed within both MPAs, 72 and 78% of the buffer zones surrounding the MPAs were fished for the Banc d’Arguin and Bijagós, respectively. Within the Banc d’Arguin buffer zone, trawling and drifting longlines dominated, with longlines mainly being deployed in fall. In the Bijagós buffer zone, trawling and fixed gears were most prevalent. Fisheries observer data for Mauritania showed that elasmobranch catches increased during the most recent sampling years (2016–2018). Elasmobranch catches within the waters of Guinea Bissau peaked in 2016 and decreased in the following two years. Seasonal patterns in elasmobranch bycatch within the waters of both countries are likely caused by increased catches of migratory species. Catches of rays peaked in May and June for Mauritania, and in October for Guinea Bissau. Shark catches were highest in February and July in Mauritanian waters, and in May and October in the waters of Guinea Bissau. Our study indicates that industrial fisheries near the border of ecologically important MPAs may have potentially major implications for ecosystem functioning by the removal of (migratory) predatory species.

Evidence of elemental homeostasis in fine root and leaf tissues of saplings across a fertility gradient in tropical montane forest in Hainan, China - J. Aaron Hogan; Oscar J. Valverde-Barrantes; Wenguang Tang; Qiong Ding; Han Xu; Christopher Baraloto (Plant and Soil, 2021)

Slingshot spiders build tensed, underdamped webs for ultrafast launches and speedy halts - Elio J. Challita; Symone L. M. Alexander; Sarah I. Han; Todd A. Blackledge; Jonathan A. Coddington; Sunghwan Jung; M. Saad Bhamla (Journal of Comparative Physiology A, 2021)

The macroecology and evolution of avian competence for Borrelia burgdorferi - Daniel J. Becker; Barbara A. Han (Global Ecology and Biogeography, 2021)
Aim Prediction of novel reservoirs of zoonotic pathogens would be improved by the identification of interspecific drivers of host competence (i.e., the ability to transmit pathogens to new hosts or vectors). Tick‐borne pathogens can provide a useful model system, because larvae become infected only when feeding on a competent host during their first blood meal. For tick‐borne diseases, competence has been studied best for Borrelia burgdorferi sensu lato ( Bb sl), which causes Lyme borreliosis. Major reservoirs include several small mammal species, but birds might play an under‐recognized role in human risk given their ability to disperse infected ticks across large spatial scales. Here, we provide a global synthesis of the ecological and evolutionary factors that determine the ability of bird species to infect larval ticks with Bb sl. Location Global. Time period 1983–2019. Major taxa studied Birds. Methods We compiled a dataset of Bb sl competence across 183 bird species and applied meta‐analysis, phylogenetic factorization and boosted regression trees to describe spatial and temporal patterns in competence, characterize its phylogenetic distribution across birds, reconstruct its evolution and evaluate the trait profiles associated with competent avian species. Results Half of the sampled bird species show evidence of competence for Bb sl. Competence displays moderate phylogenetic signal, has evolved multiple times across bird species and is pronounced in the genus Turdus . Trait‐based analyses distinguished competent birds with 80% accuracy and showed that such species have low baseline corticosterone, exist on both ends of the pace‐of‐life continuum, breed and winter at high latitudes and have broad migratory movements into their breeding range. We used these trait profiles to predict various likely but unsampled competent species, including novel concentrations of avian reservoirs within the Neotropics. Main conclusion Our results can generate new hypotheses for how birds contribute to the dynamics of tick‐borne pathogens and help to prioritize surveillance of likely but unsampled competent birds. Our findings also emphasize that birds display under‐recognized variation in their contributions to enzootic cycles of Bb sl and the broader need to consider competence in ecological and predictive studies of multi‐host pathogens.

Long‐term, amplified responses of soil organic carbon to nitrogen addition worldwide - Chonghua Xu; Xia Xu; Chenghui Ju; Han Y. H. Chen; Brian J. Wilsey; Yiqi Luo; Wei Fan (Global Change Biology, 2021)
Soil organic carbon (SOC) is the largest carbon sink in terrestrial ecosystems and plays a critical role in mitigating climate change. Increasing reactive nitrogen (N) in ecosystems caused by anthropogenic N input substantially affects SOC dynamics. However, uncertainties remain concerning the effects of N addition on SOC in both organic and mineral soil layers over time at the global scale. Here, we analysed a large empirical data set spanning 60 years across 369 sites worldwide to explore the temporal dynamics of SOC to N addition. We found that N addition significantly increased SOC across the globe by 4.2% (2.7%–5.8%). SOC increases were amplified from short‐ to long‐term N addition durations in both organic and mineral soil layers. The positive effects of N addition on SOC were independent of ecosystem types, mean annual temperature and precipitation. Our findings suggest that SOC increases largely resulted from the enhanced plant C input to soils coupled with reduced C loss from decomposition and amplification was associated with reduced microbial biomass and respiration under long‐term N addition. Our study suggests that N addition will enhance SOC sequestration over time and contribute to future climate change mitigation.

Fatigue-Damage Evolution Characteristics of Interbeded Marble Subjected to Dynamic Uniaxial Cyclic Loads - Y. Wang; S. H. Gao; J. Q. Han (Geotechnical and Geological Engineering, 2021)

Nano-selenium Supplementation Increases Selenoprotein (Sel) Gene Expression Profiles and Milk Selenium Concentration in Lactating Dairy Cows - Liqiang Han; Kun Pang; Tong Fu; Clive J. C. Phillips; Tengyun Gao (Biological Trace Element Research, 2021)
Supplementation with selenium is common for dairy cows, but the importance of selenium source is not clear. This study aimed to compare nano-selenium (Nano-Se) and sodium selenite supplements for dairy cows on lactation performance, milk Se levels and selenoprotein (Sel) gene expression. Twelve multiparous Holstein cows were randomly divided into two groups: a control group fed a basal diet plus 0.30 mg Se/kg of DM as sodium selenite or Nano-Se for 30 days. Dry matter intake, milk yield and composition were not affected by dietary Se source ( P > 0.05); however, the milk total Se levels and milk glutathione peroxidase (GSH-Px) activities were higher with Nano-Se supplementation than sodium selenite ( P < 0.05). At the end of the experiment, Nano-Se supplementation significantly increased plasma Se levels and GSH-Px activity, compared with the sodium selenite supplement. The mRNA expression levels of glutathione peroxidase 1, 2 and 4; thioredoxin reductase 2 and 3; and selenoproteins W, T, K and F were markedly upregulated ( P < 0.05) in the mammary gland of the Nano-Se group. Thus, the source of selenium plays an important role in the antioxidant status and in particular the Sel gene expression in the mammary glands of dairy cows, both being stimulated by nano sources.

Dissociable dopaminergic and pavlovian influences in goal-trackers and sign-trackers on a model of compulsive checking in OCD - D. M. Eagle; C. Schepisi; S. Chugh; S. Desai; S. Y. S. Han; T. Huang; J. J. Lee; C. Sobala; W. Ye; A. L. Milton; T. W. Robbins (Psychopharmacology, 2020)
Rationale Checking is a functional behaviour that provides information to guide behaviour. However, in obsessive-compulsive disorder (OCD), checking may escalate to dysfunctional levels. The processes underpinning the transition from functional to dysfunctional checking are unclear but may be associated with individual differences that support the development of maladaptive behaviour. We examined one such predisposition, sign-tracking to a pavlovian conditioned stimulus, which we previously found associated with dysfunctional checking. How sign-tracking interacts with another treatment with emerging translational validity for OCD-like checking, chronic administration of the dopamine D 2 receptor agonist quinpirole, is unknown. Objectives We tested how functional and dysfunctional checking in the rat observing response task (ORT) was affected by chronic quinpirole administration in non-autoshaped controls and autoshaped animals classified as sign-trackers or goal-trackers. Methods Sign-trackers or goal-trackers were trained on the ORT before the effects of chronic quinpirole administration on checking were assessed. Subsequently, the effects on checking of different behavioural challenges, including reward omission and the use of unpredictable reinforcement schedules, were tested. Results Prior autoshaping increased checking. Sign-trackers and goal-trackers responded differently to quinpirole sensitization, reward omission and reinforcement uncertainty. Sign-trackers showed greater elevations in dysfunctional checking, particularly during uncertainty. By contrast, goal-trackers predominantly increased functional checking responses, possibly in response to reduced discrimination accuracy in the absence of cues signalling which lever was currently active. Conclusions The results are discussed in terms of how pavlovian associations influence behaviour that becomes compulsive in OCD and how this may be dependent on striatal dopamine D 2 receptors.

Improving the Diagnostic Ability of the Sleep Apnea Screening System Based on Oximetry by Using Physical Activity Data - Cheng-Han Wu; Jui-Hsuan Lee; Terry B. J. Kuo; Chun-Ting Lai; Lieber P. H. Li; Cheryl C. H. Yang (Journal of Medical and Biological Engineering, 2020)

Geomechanical and Ultrasonic Characteristics of Black Shale During Triaxial Deformation Revealed Using Real-Time Ultrasonic Detection Dependence Upon Bedding Orientation and Confining Pressure - Y. Wang; J. Q. Han (Geotechnical and Geological Engineering, 2020)

Dietary exposure assessment of cadmium, arsenic, and lead in market rice from Sri Lanka - Lin Liu; Jialiang Han; Xiaohang Xu; Zhidong Xu; Kasun S. Abeysinghe; Anjana J. Atapattu; P. Mangala C. S. De Silva; Qinhui Lu; Guangle Qiu (Environmental Science and Pollution Research, 2020)

Removal of indoor odors via phytoremediation: interaction between aromatic hydrocarbon odorants decreases toluene removal - Kwang Jin Kim; Seung Won Han; Jihye Yoon; Nara Jeong; Soo Jin You; Eun Ha Yoo; Hyo Won Seo; Su Yeon Jo; Stanley J. Kays (Air Quality, Atmosphere & Health, 2020)

Zooplankton in a continuous waterscape: environmental and spatial factors shaping spring zooplankton community structure in a large canyon reservoir at the tropic of cancer - Eric Zeus C. Rizo; Ping Liu; Haiyu Niu; Yang Yang; Qiuqi Lin; Rey Donne S. Papa; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2020)

Horizon slices of bandwidth-extended seismic data: optimizing thin bed interpretation from spectral decomposition - Hyeonju Kim; Gwang H. Lee; Han-J. Kim; John D. Pigott (Geosciences Journal, 2020)

Multiomic immune clockworks of pregnancy - Laura S. Peterson; Ina A. Stelzer; Amy S. Tsai; Mohammad S. Ghaemi; Xiaoyuan Han; Kazuo Ando; Virginia D. Winn; Nadine R. Martinez; Kevin Contrepois; Mira N. Moufarrej; Stephen Quake; David A. Relman; et al. (Seminars in Immunopathology, 2020)
Preterm birth is the leading cause of mortality in children under the age of five worldwide. Despite major efforts, we still lack the ability to accurately predict and effectively prevent preterm birth. While multiple factors contribute to preterm labor, dysregulations of immunological adaptations required for the maintenance of a healthy pregnancy is at its pathophysiological core. Consequently, a precise understanding of these chronologically paced immune adaptations and of the biological pacemakers that synchronize the pregnancy “immune clock” is a critical first step towards identifying deviations that are hallmarks of peterm birth. Here, we will review key elements of the fetal, placental, and maternal pacemakers that program the immune clock of pregnancy. We will then emphasize multiomic studies that enable a more integrated view of pregnancy-related immune adaptations. Such multiomic assessments can strengthen the biological plausibility of immunological findings and increase the power of biological signatures predictive of preterm birth

2DNEMM: a numerical environmental multimedia modeling method for landfill case study - J Dong; Z Chen; Y Han; J Guo; K Wang (International Journal of Environmental Science and Technology, 2020)

A Modified Creep Model for Cyclic Characterization of Rock Salt Considering the Effects of the Mean Stress, Half-Amplitude and Cycle Period - Yue Han; Hongling Ma; Chunhe Yang; Nan Zhang; J. J. K. Daemen (Rock Mechanics and Rock Engineering, 2020)

Carbapenem-resistant Enterobacteriaceae in patients with bacteraemia at tertiary hospitals in South Africa, 2015 to 2018 - O. Perovic; H. Ismail; V. Quan; C. Bamford; T. Nana; V. Chibabhai; P. Bhola; P. Ramjathan; K. Swe Swe-Han; J. Wadula; A. Whitelaw; M. Smith; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Glycosaminoglycan remodeling during chondrogenic differentiation of human bone marrow−/synovial-derived mesenchymal stem/stromal cells under normoxia and hypoxia - João C. Silva; Xiaorui Han; Teresa P. Silva; Ke Xia; Paiyz E. Mikael; Joaquim M. S. Cabral; Frederico Castelo Ferreira; Robert J. Linhardt (Glycoconjugate Journal, 2020)

Characterization of functional transposable element enhancers in acute myeloid leukemia - Yingying Zeng; Yaqiang Cao; Rivka Sukenik Halevy; Picard Nguyen; Denghui Liu; Xiaoli Zhang; Nadav Ahituv; Jing-Dong J. Han (Science China Life Sciences, 2020)

Acclimation of leaf respiration consistent with optimal photosynthetic capacity - Han Wang; Owen K. Atkin; Trevor F. Keenan; Nicholas G. Smith; Ian J. Wright; Keith J. Bloomfield; Jens Kattge; Peter B. Reich; I. Colin Prentice (Global Change Biology, 2020)
Plant respiration is an important contributor to the proposed positive global carbon‐cycle feedback to climate change. However, as a major component, leaf mitochondrial (‘dark’) respiration ( R d ) differs among species adapted to contrasting environments and is known to acclimate to sustained changes in temperature. No accepted theory explains these phenomena or predicts its magnitude. Here we propose that the acclimation of R d follows an optimal behaviour related to the need to maintain long‐term average photosynthetic capacity ( V cmax ) so that available environmental resources can be most efficiently used for photosynthesis. To test this hypothesis, we extend photosynthetic co‐ordination theory to predict the acclimation of R d to growth temperature via a link to V cmax , and compare predictions to a global set of measurements from 112 sites spanning all terrestrial biomes. This extended co‐ordination theory predicts that field‐measured R d and V cmax accessed at growth temperature ( R d,tg and V cmax,tg ) should increase by 3.7% and 5.5% per degree increase in growth temperature. These acclimated responses to growth temperature are less steep than the corresponding instantaneous responses, which increase 8.1% and 9.9% per degree of measurement temperature for R d and V cmax respectively. Data‐fitted responses proof indistinguishable from the values predicted by our theory, and smaller than the instantaneous responses. Theory and data are also shown to agree that the basal rates of both R d and V cmax assessed at 25°C ( R d,25 and V cmax,25 ) decline by ~4.4% per degree increase in growth temperature. These results provide a parsimonious general theory for R d acclimation to temperature that is simpler—and potentially more reliable—than the plant functional type‐based leaf respiration schemes currently employed in most ecosystem and land‐surface models.

The effect of enrichment media on the stimulation of native ureolytic bacteria in calcareous sand - Y.-J. Wang; X.-L. Han; N.-J. Jiang; J. Wang; J. Feng (International Journal of Environmental Science and Technology, 2020)

Abnormal expression of chondroitin sulfate sulfotransferases in the articular cartilage of pediatric patients with Kashin–Beck disease - Jian Lei; Siqi Yan; Yuan Zhou; Liyun Wang; Jinghua Zhang; Xiong Guo; Mikko J. Lammi; Jing Han; Chengjuan Qu (Histochemistry and Cell Biology, 2020)

Carbon content in airway macrophages and genomic instability in Chinese carbon black packers - Wenting Cheng; Yuansheng Liu; Jinglong Tang; Huawei Duan; Xiaoran Wei; Xiao Zhang; Shanfa Yu; Matthew J. Campen; Wei Han; Nathaniel Rothman; Steven A. Belinsky; Qing Lan; et al. (Archives of Toxicology, 2020)

Role of Adult Tissue-Derived Pluripotent Stem Cells in Bone Regeneration - Liudmila Leppik; K. Sielatycka; D. Henrich; Z. Han; H. Wang; M. J. Eischen-Loges; K. M. C. Oliveira; M. B. Bhavsar; M. Z. Ratajczak; J. H. Barker (Stem Cell Reviews and Reports, 2020)
Background Bone marrow-derived mononuclear cells (BM-MNC) consist of a heterogeneous mix of mesenchymal stem cells (MSC), hematopoietic progenitor cells (HPC), endothelial progenitor cells (EPC), monocytes, lymphocytes and pluripotent stem cells. Whereas the importance of MSC and EPC has been well documented in bone healing and regeneration studies, the role of pluripotent stem cells is still poorly understood. In the present study we evaluated if and how Very Small Embryonic Like cells (VSEL), isolated from rat BM-MNC, contribute to bone healing. Methods Large bone defects were made in the femurs of 38 Sprague Dawley female rats and treated with β-TCP scaffold granules seeded with male VSEL; BM-MNC, VSEL-depleted BM-MNC or scaffold alone, and bone healing was evaluated at 8 weeks post-surgery. Results Bone healing was significantly increased in defects treated with VSEL and BM-MNC, compared to defects treated with VSEL-depleted BM-MNC. Donor cells were detected in new bone tissue, in all the defects treated with cells, and in fibrous tissue only in defects treated with VSEL-depleted BM-MNC. The number of CD68+ cells was the highest in the VSEL-depleted group, whereas the number of TRAP positive cells was the lowest in this group. Conclusions Based on the results, we can conclude that VSEL play a role in BM-MNC induced bone formation. In our rat femur defect model, in defects treated with VSEL-depleted BM-MNC, osteoclastogenesis and bone formation were decreased, and foreign body reaction was increased.

Front Cover - Wei Wang; Jie Wang; Francis M. P. Choi; Ping Ding; Xiao‐xu Li; Guo‐dong Han; Meng‐wen Ding; Minquan Guo; Xiong‐wei Huang; Wei‐xiang Duan; Zhi‐yuan Cheng; Zhi‐yuan Chen; et al. (Global Ecology and Biogeography, 2020)

Global warming and artificial shorelines reshape seashore biogeography - Wei Wang; Jie Wang; Francis M. P. Choi; Ping Ding; Xiao‐xu Li; Guo‐dong Han; Meng‐wen Ding; Minquan Guo; Xiong‐wei Huang; Wei‐xiang Duan; Zhi‐yuan Cheng; Zhi‐yuan Chen; et al. (Global Ecology and Biogeography, 2020)
Aim Rapid anthropogenic warming coupled with changes in land use is altering the distributions of species, with consequences for ecosystem functioning and services. It is crucial to evaluate species range shifts based on understanding of the interaction of temperature with non‐climatic factors such as habitat availability and dispersal potential. Here, we aim to investigate roles of environmental temperature, habitat availability and population connectivity on the distributions of hard‐shore intertidal animals. We further examine potential roles of extensive artificial seawall construction in enabling poleward expansion of species in China, thus reshaping coastal biogeography. Location Chinese coast. Time period 2013–2017. Major taxa studied Intertidal invertebrates. Methods We took an integrative approach encompassing distributional ecology, thermal physiology, molecular genetics, heat budget modelling and larval dispersal to elucidate how interacting multiple drivers, including temperature, habitat availability and larval dispersal, determine distributions of hard‐shore invertebrates, focusing on what sets their range edges at a boundary between biogeographic provinces. Results Our results untangle the complex interactions of global climate change with the impacts of regional scale coastal development. Temperature, larval transport and habitat availability are the major proximate factors controlling the range limits of coastal marine species. The artificial shorelines provide suitable habitats for hard‐shore species on the Yangtze River Delta, and minimum temperature in winter is an important factor setting the new northern range limit of these hard‐shore species along the Chinese coast. Main conclusions In the face of global warming and global sprawl of marine hard infrastructure, species distributions, community structures and biogeographic patterns are experiencing dramatic changes. The combined influence of multiple human stressors including climate change and artificial shorelines can be evaluated by using a multidisciplinary framework, including ecological distribution, physiological sensitivity of species to these stressors, and the role of dispersal in maintaining population connectivity.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Subpopulations of hyphae secrete proteins or resist heat stress in Aspergillus oryzae colonies - Martin Tegelaar; Robert‐Jan Bleichrodt; Benjamin Nitsche; Arthur F. J. Ram; Han A. B. Wösten (Environmental Microbiology, 2020)
Summary Hyphae at the outer part of colonies of Aspergillus niger and Aspergillus oryzae are heterogeneous with respect to transcriptional and translational activity. This heterogeneity is maintained by Woronin body mediated closure of septal pores that block interhyphal mixing of cytoplasm. Indeed, heterogeneity between hyphae is abolished in Δ hexA strains that lack Woronin bodies. The subpopulation of hyphae with high transcriptional and translational activity secretes enzymes that degrade the substrate resulting in breakdown products that serve as nutrients. The role of hyphae with low transcriptional and translational activity was not yet known. Here, we show that this subpopulation is more resistant to environmental stress in A . oryzae , in particular to temperature stress, when compared to hyphae with high transcriptional and translational activity. Notably, all hyphae of the Δ hexA strain of A . oryzae were sensitive to heat stress explained by the reduced heterogeneity in this strain. Together, we show that different subpopulations of hypha secrete proteins and resist heat stress showing the complexity of a fungal mycelium.

Current Opinions and Consensus for Studying Tremor in Animal Models - Sheng-Han Kuo; Elan D. Louis; Phyllis L. Faust; Adrian Handforth; Su-youne Chang; Billur Avlar; Eric J. Lang; Ming-Kai Pan; Lauren N. Miterko; Amanda M. Brown; Roy V. Sillitoe; Collin J. Anderson; et al. (The Cerebellum, 2019)

Ecosystem engineering creates a new path to resilience in plants with contrasting growth strategies - Laura M. Soissons; Marieke M. van Katwijk; Baoquan Li; Qiuying Han; Tom Ysebaert; Peter M. J. Herman; Tjeerd J. Bouma (Oecologia, 2019)

Novel ablation technique shows no sperm priming response by male eastern mosquitofish to cues of female availability - Meng-Han Joseph Chung; Michael D. Jennions; Rebecca J. Fox (Behavioral Ecology and Sociobiology, 2019)

Multiple mineralization events of the Paleozoic Tuwu porphyry copper deposit, Eastern Tianshan: evidence from geology, fluid inclusions, sulfur isotopes, and geochronology - Yunfeng Wang; Huayong Chen; Michael J. Baker; Jinsheng Han; Bing Xiao; Juntao Yang; Fred Jourdan (Mineralium Deposita, 2019)

COL4A1 mutations as a potential novel cause of autosomal dominant CAKUT in humans - Thomas M. Kitzler; Ronen Schneider; Stefan Kohl; Caroline M. Kolvenbach; Dervla M. Connaughton; Rufeng Dai; Nina Mann; Makiko Nakayama; Amar J. Majmundar; Chen-Han W. Wu; Jameela A. Kari; Sherif M. El Desoky; et al. (Human Genetics, 2019)

Long term experimental drought alters community plant trait variation, not trait means, across three semiarid grasslands - Wentao Luo; Xiaoan Zuo; Robert J. Griffin-Nolan; Chong Xu; Wang Ma; Lin Song; Kenny Helsen; Yingchao Lin; Jiangping Cai; Qiang Yu; Zhengwen Wang; Melinda D. Smith; et al. (Plant and Soil, 2019)

An improved supported vector regression algorithm with application to predict aftershocks - Maofa Wang; J. Shen; Z. A. Pan; D. L. Han (Journal of Seismology, 2019)

A multi-channel chemical sensor and its application in detecting hydrothermal vents - Zhen Cai; A J Mur Luis; Jiwan Han; Kui Wang; Huawei Qin; Ying Ye (Acta Oceanologica Sinica, 2019)

Increased Diagnostic Yield of Spastic Paraplegia with or Without Cerebellar Ataxia Through Whole-Genome Sequencing - Aryun Kim; Kishore R. Kumar; Ryan L. Davis; Amali C. Mallawaarachchi; Velimir Gayevskiy; Andre E. Minoche; Zachary Walls; Han-Joon Kim; Mihee Jang; Mark J. Cowley; Ji-Hyun Choi; Chaewon Shin; et al. (The Cerebellum, 2019)

Seagrass Sensitivity to Collapse Along a Hydrodynamic Gradient: Evidence from a Pristine Subtropical Intertidal Ecosystem - El-Hacen M. El-Hacen; Tjeerd J. Bouma; Laura L. Govers; Theunis Piersma; Han Olff (Ecosystems, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Local Application of Autologous Platelet-Rich Fibrin Patch (PRF-P) Suppresses Regulatory T Cell Recruitment in a Murine Glioma Model - Wojciech K. Panek; Katarzyna C. Pituch; Jason Miska; Julius W. Kim; Aida Rashidi; Deepak Kanojia; Aurora Lopez-Rosas; Yu Han; Dou Yu; Catalina Lee Chang; J. Robert Kane; Peng Zhang; et al. (Molecular Neurobiology, 2019)

A Sustained Ocean Observing System in the Indian Ocean for Climate Related Scientific Knowledge and Societal Needs - J. C. Hermes; Y. Masumoto; L. M. Beal; M. K. Roxy; J. Vialard; M. Andres; H. Annamalai; S. Behera; N. D’Adamo; T. Doi; M. Feng; W. Han; et al. (Frontiers in Marine Science, 2019)

Rapid identification of a candidate nicosulfuron sensitivity gene (Nss) in maize (Zea mays L.) via combining bulked segregant analysis and RNA-seq - Xiaomin Liu; Bo Bi; Xian Xu; Binghua Li; Shengmin Tian; Jianping Wang; Hui Zhang; Guiqi Wang; Yujun Han; J. Scott McElroy (Theoretical and Applied Genetics, 2019)

Correction to: Mowing mitigates the negative impacts of N addition on plant species diversity - Guo-Jiao Yang; Xiao-Tao Lü; Carly J. Stevens; Guang-Ming Zhang; Hong-Yi Wang; Zheng-Wen Wang; Zi-Jia Zhang; Zhuo-Yi Liu; Xing-Guo Han (Oecologia, 2019)

A high production of flavonoids and anthraquinones via adventitious root culture of Oplopanax elatus and evaluating antioxidant activity - L. Han; X. C. Piao; J. Jiang; X. L. Jiang; C. R. Yin; M. L. Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Network structure and input integration in competing firing rate models for decision-making - Victor J. Barranca; Han Huang; Genji Kawakita (Journal of Computational Neuroscience, 2019)

Compositional and structural analysis of glycosaminoglycans in cell-derived extracellular matrices - João C. Silva; Marta S. Carvalho; Xiaorui Han; Ke Xia; Paiyz E. Mikael; Joaquim M. S. Cabral; Frederico Castelo Ferreira; Robert J. Linhardt (Glycoconjugate Journal, 2019)

Mowing mitigates the negative impacts of N addition on plant species diversity - Guo-Jiao Yang; Xiao-Tao Lü; Carly J. Stevens; Guang-Ming Zhang; Hong-Yi Wang; Zheng-Wen Wang; Zi-Jia Zhang; Zhuo-Yi Liu; Xing-Guo Han (Oecologia, 2019)

High frequency and diversity of parechovirus A in a cohort of Malawian children - Lieke Brouwer; Eveliina Karelehto; Alvin X. Han; Xiomara V. Thomas; Andrea H. L. Bruning; Job C. J. Calis; Michaël Boele van Hensbroek; Brenda M. Westerhuis; Darsha Amarthalingam; Sylvie M. Koekkoek; Sjoerd P. H. Rebers; Kamija S. Phiri; et al. (Archives of Virology, 2019)

Global photosynthetic capacity is optimized to the environment - Nicholas G. Smith; Trevor F. Keenan; I. Colin Prentice; Han Wang; Ian J. Wright; Ülo Niinemets; Kristine Y. Crous; Tomas F. Domingues; Rossella Guerrieri; F. Yoko Ishida; Jens Kattge; Eric L. Kruger; et al. (Ecology Letters, 2019)

The impact of spike-frequency adaptation on balanced network dynamics - Victor J. Barranca; Han Huang; Sida Li (Cognitive Neurodynamics, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Fronto-parietal numerical networks in relation with early numeracy in young children - Han Zhang; Chong-Yaw Wee; Joann S. Poh; Qiang Wang; Lynette P. Shek; Yap-Seng Chong; Marielle V. Fortier; Michael J. Meaney; Birit F. P. Broekman; Anqi Qiu (Brain Structure and Function, 2019)

Amyloid-β Increases Tau by Mediating Sirtuin 3 in Alzheimer’s Disease - Junxiang Yin; Pengcheng Han; Melissa Song; Megan Nielsen; Thomas G. Beach; Geidy E. Serrano; Winnie S. Liang; Richard J. Caselli; Jiong Shi (Molecular Neurobiology, 2018)

Fluorescent reporter transgenic mice for in vivo live imaging of angiogenesis and lymphangiogenesis - Susan J. Doh; Michael Yamakawa; Samuel M. Santosa; Mario Montana; Kai Guo; Joseph R. Sauer; Nicholas Curran; Kyu-Yeon Han; Charles Yu; Masatsugu Ema; Mark I. Rosenblatt; Jin-Hong Chang; et al. (Angiogenesis, 2018)

Litter quality, dispersal and invasion drive earthworm community dynamics and forest soil development - Katalin Szlavecz; Chih-Han Chang; Michael J. Bernard; Scott L. Pitz; Lijun Xia; Yini Ma; Melissa K. McCormick; Timothy Filley; Stephanie A. Yarwood; Ian D. Yesilonis; Csaba Csuzdi (Oecologia, 2018)

Shake table tests on RC frame infilled by slitted masonry panels - Terry Y. P. Yuen; Han-hui Zhang; J. S. Kuang; Qunxian Huang (Bulletin of Earthquake Engineering, 2018)

Fecal pollution: new trends and challenges in microbial source tracking using next‐generation sequencing - Tatsuya Unno; Christopher Staley; Clairessa M. Brown; Dukki Han; Michael J. Sadowsky; Hor‐Gil Hur (Environmental Microbiology, 2018)
Summary In this minireview, we expand upon traditional microbial source tracking (MST) methods by discussing two recently developed, next‐generation‐sequencing (NGS)‐based MST approaches to identify sources of fecal pollution in recreational waters. One method defines operational taxonomic units (OTUs) that are specific to a fecal source, e.g., humans and animals or shared among multiple fecal sources to determine the magnitude and likely source association of fecal pollution. The other method uses SourceTracker, a program using a Bayesian algorithm, to determine which OTUs have contributed to an environmental community based on the composition of microbial communities in multiple fecal sources. Contemporary NGS‐based MST tools offer a promising avenue to rapidly characterize fecal source contributions for water monitoring and remediation efforts at a broader and more efficient scale than previous molecular MST methods. However, both NGS methods require optimized sequence processing methodologies (e.g. quality filtering and clustering algorithms) and are influenced by primer selection for amplicon sequencing. Therefore, care must be taken when extrapolating data or combining datasets. Furthermore, traditional limitations of library‐dependent MST methods, including differential decay of source material in environmental waters and spatiotemporal variation in source communities, remain to be fully understood. Nevertheless, increasing use of these methods, as well as expanding fecal taxon libraries representative of source communities, will help improve the accuracy of these methods and provide promising tools for future MST investigations.

Unexpected dietary preferences of Eurasian Spoonbills in the Dutch Wadden Sea: spoonbills mainly feed on small fish not shrimp - Jeltje Jouta; Petra de Goeij; Tamar Lok; Estefania Velilla; Cornelis J. Camphuysen; Mardik Leopold; Henk W. van der Veer; Han Olff; Otto Overdijk; Theunis Piersma (Journal of Ornithology, 2018)

Winter hatching in New England populations of invasive pheretimoid earthworms Amynthas agrestis and Amynthas tokioensis: a limit on population growth, or aid in peripheral expansion? - Josef H. Görres; Samantha T. Connolly; Chih-Han Chang; Nell R. Carpenter; Erin L. Keller; Maryam Nouri-Aiin; Joseph J. Schall (Biological Invasions, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Improved soil water deficit estimation through the integration of canopy temperature measurements into a soil water balance model - Ming Han; Huihui Zhang; José L. Chávez; Liwang Ma; Thomas J. Trout; Kendall C. DeJonge (Irrigation Science, 2018)

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

Linking muscle metabolism and functional variation to field swimming performance in bluegill sunfish (Lepomis macrochirus) - David J. Ellerby; Shauna Cyr; Angela X. Han; Mika Lin; Lloyd A. Trueblood (Journal of Comparative Physiology B, 2018)

Thermal reaction norms of a subtropical and a tropical species of Diaphanosoma (cladocera) explain their distribution - Franja Pajk; Jiexiang Zhang; Bo‐Ping Han; Henri J. Dumont (Limnology and Oceanography, 2018)
Species distribution boundaries are often associated with aspects of climate and modified by competitive interactions. In the tropical region, Diaphanosoma is the most diverse genus of Cladocera. Diaphanosoma dubium is widely distributed in China, whereas the tropical Diaphanosoma excisum is restricted to the islands off the south China coast. The mean temperature of the coldest month at the northern limit of its distribution is 15°C. We studied the effect of temperature (10–40°C) on life history traits of clones from 16 populations of D. dubium and D. excisum in life‐table experiments in order to determine if their thermal performance curves (TPCs) explain their distribution and to estimate the extent and mode of genetic variation in their TPCs. Our results show that both species have higher optimum temperatures ( T o ∼ 33°C), critical thermal minimum (CT min = 10–15°C), and maximum (CT max = 39–40°C) than temperate cladocerans. Clones of D. excisum had narrower TPCs and higher T o than D. dubium clones, in accordance with predictions based on changes of temperature distributions with latitude. Significant levels of genetic variation in TPCs were present in both species. D. excisum had higher fitness than D. dubium at all temperatures above 15°C. However, at 15°C and below, D. dubium fitness was higher. Negative r at 15°C and below in combination with competition with the more cold‐adapted D. dubium exclude D. excisum from mainland China. TPCs of interacting species may be the basis of predicting future species distributions as temperature increases change the balance of biotic interactions.

Heterotopic Purkinje Cells: a Comparative Postmortem Study of Essential Tremor and Spinocerebellar Ataxias 1, 2, 3, and 6 - Elan D. Louis; Sheng-Han Kuo; William J. Tate; Geoffrey C. Kelly; Jesus Gutierrez; Etty P. Cortes; Jean-Paul G. Vonsattel; Phyllis L. Faust (The Cerebellum, 2018)

Phage Application for the Protection from Acute Hepatopancreatic Necrosis Disease (AHPND) in Penaeus vannamei - Jin Woo Jun; Jee Eun Han; Sib Sankar Giri; Kathy F. J. Tang; Xiaohui Zhou; Luis Fernando Aranguren; Hyoun Joong Kim; Saekil Yun; Cheng Chi; Sang Guen Kim; Se Chang Park (Indian Journal of Microbiology, 2018)

The FlbA-regulated predicted transcription factor Fum21 of Aspergillus niger is involved in fumonisin production - David Aerts; Esther E. Hauer; Robin A. Ohm; Mark Arentshorst; Wieke R. Teertstra; Christopher Phippen; Arthur F. J. Ram; Jens C. Frisvad; Han A. B. Wösten (Antonie van Leeuwenhoek, 2018)

Relative impacts of light, temperature, and reactive oxygen on thaumarchaeal ammonia oxidation in the North Pacific Ocean - Rachel E. A. Horak; Wei Qin; Anthony D. Bertagnolli; Alexa Nelson; Katherine R. Heal; Hantten Han; Maija Heller; Andrew J. Schauer; Wade H. Jeffrey; E. Virginia Armbrust; James W. Moffett; Anitra E. Ingalls; et al. (Limnology and Oceanography, 2018)
Thaumarchaeota are implicated as the major ammonia oxidizers in the ocean. However, the influence of various abiotic factors in determining their distribution and activity in the upper ocean remain largely unclear. Here, we examined the influence of light, hydrogen peroxide (H 2 O 2 ), and temperature on ammonia oxidation rates for communities dominated by Thaumarchaeota at the nitrite maximum across two North Pacific transects. In situ ammonia oxidation was almost exclusively driven by Thaumarchaeota , as inferred from ammonia monooxygenase subunit A ( amoA ) genes, amoA transcripts, and inhibitor studies. A major shift in population structure near the eastern North Pacific Subtropical Front was revealed by sequence variation of amoA genes, showing different Thaumarchaeota community structure in oligotrophic gyre and temperate regions. While the most dominant OTUs were closely related, we found significant differences in physiological responses to light and temperature of incubation. At four stations in different biogeochemical regimes, the impact of sunlight intensity and temperature on activity was evaluated using 15 ‐spiked whole seawater collected from the nitrite maximum and incubated at different depths on a free floating in situ array. Ammonia oxidation was usually completely inhibited by PAR at the surface and 21–45% inhibited at 1% surface PAR, whereas a temperature effect on ammonia oxidation was observed at only two of four stations. While inhibition due to H 2 O 2 cannot be ruled out in surface waters, our findings show that below the mixed layer, photoinhibition, and not H 2 O 2 toxicity, had a greater influence on ammonia oxidation.

iDNA at Sea: Recovery of Whale Shark (Rhincodon typus) Mitochondrial DNA Sequences from the Whale Shark Copepod (Pandarus rhincodonicus) Confirms Global Population Structure - Mark Meekan; Christopher M. Austin; Mun H. Tan; Nu-Wei V. Wei; Adam Miller; Simon J. Pierce; David Rowat; Guy Stevens; Tim K. Davies; Alessandro Ponzo; Han Ming Gan (Frontiers in Marine Science, 2017)

The persistent prevalence and evolution of cross-family recombinant coronavirus GCCDC1 among a bat population: a two-year follow-up - Joseph O. Obameso; Hong Li; Hao Jia; Min Han; Shiyan Zhu; Canping Huang; Yuhui Zhao; Min Zhao; Yu Bai; Fei Yuan; Honglan Zhao; Xia Peng; et al. (Science China Life Sciences, 2017)

Conserved peptides enhance immune efficiency of inactive vaccines against emerging avian influenza viruses in chicken - Jin Xiao; Lei Zhang; Zhenbao Wang; Wangzhen Xiang; Ping Lu; Yingze Zhao; Min Han; Airong Ma; Peng Qi; Ming Wang; George F. Gao; William J. Liu (Science China Life Sciences, 2017)

China in action: national strategies to combat against emerging infectious diseases - Min Han; Jinhui Gu; George F. Gao; William J. Liu (Science China Life Sciences, 2017)

An Experimental Study of Dependence of Optimum TBM Cutter Spacing on Pre-set Penetration Depth in Sandstone Fragmentation - D. Y. Han; P. Cao; J. Liu; J. B. Zhu (Rock Mechanics and Rock Engineering, 2017)

Spatial heterogeneity and long-term dynamics of cladoceran ephippia in a monsoonal reservoir, driven by hydrology and eutrophication - Lei Xu; Shaolin Xu; Xiaoyu Han; Sijia Li; Henri J. Dumont; Bo-Ping Han (Journal of Paleolimnology, 2017)

Fungal Denitrification Activity in Vertical Flow Constructed Wetlands as Impacted by Plant Species Richness, Carbon, Nitrogen and pH Amendments - W. L. Liu; C. B. Zhang; W. J. Han; M. Guan; S. Y. Liu; Y. Ge; J. Chang (Bulletin of Environmental Contamination and Toxicology, 2017)

Rapid recovery of nuclear and mitochondrial genes by genome skimming from Northern Hemisphere freshwater crayfish - Frederic Grandjean; Mun Hua Tan; Han Ming Gan; Yin Peng Lee; Tadashi Kawai; Robert J. Distefano; Martin Blaha; Angela J. Roles; Christopher M. Austin (Zoologica Scripta, 2017)
Molecular phylogenetics has benefited tremendously from the advent of next‐generation sequencing, enabling quick and cost‐effective recovery of whole mitogenomes via an approach referred to as ‘genome skimming’. Recently, genome skimming has been utilised to recover highly repetitive nuclear genes such as 18S and 28S ribosomal RNA genes that are useful for inferring deeper evolutionary relationships. To address some outstanding issues in the relationships among Northern Hemisphere freshwater crayfish (Astacoidea), we sequenced the partial genome of crayfish species from Asian, North American and European genera and report the successful recovery of whole mitogenome sequences in addition to three highly repetitive nuclear genes, namely histone H3, 18S and 28S ribosomal RNA . Consistent with some previous studies using short mt DNA and nuclear gene fragments, phylogenetic analyses based on the concatenation of recovered mitochondrial and/or nuclear sequences recovered the Asian cambarid lineage as basal to all astacids and North American cambarids, which conflicts with the current taxonomic classification based on morphological and reproduction‐related characters. Lastly, we show that complete H3, 18S and 28S ribosomal RNA genes can also be consistently recovered from a diverse range of animal taxa, demonstrating the potential wide utility of genome skimming for nuclear markers.

Comparative and population genomic landscape of Phellinus noxius : A hypervariable fungus causing root rot in trees - Chia‐Lin Chung; Tracy J. Lee; Mitsuteru Akiba; Hsin‐Han Lee; Tzu‐Hao Kuo; Dang Liu; Huei‐Mien Ke; Toshiro Yokoi; Marylette B. Roa; Mei‐Yeh J. Lu; Ya‐Yun Chang; Pao‐Jen Ann; et al. (Molecular Ecology, 2017)
The order Hymenochaetales of white rot fungi contain some of the most aggressive wood decayers causing tree deaths around the world. Despite their ecological importance and the impact of diseases they cause, little is known about the evolution and transmission patterns of these pathogens. Here, we sequenced and undertook comparative genomic analyses of Hymenochaetales genomes using brown root rot fungus Phellinus noxius , wood‐decomposing fungus Phellinus lamaensis, laminated root rot fungus Phellinus sulphurascens and trunk pathogen Porodaedalea pini . Many gene families of lignin‐degrading enzymes were identified from these fungi, reflecting their ability as white rot fungi. Comparing against distant fungi highlighted the expansion of 1,3‐beta‐glucan synthases in P. noxius , which may account for its fast‐growing attribute. We identified 13 linkage groups conserved within Agaricomycetes, suggesting the evolution of stable karyotypes. We determined that P. noxius has a bipolar heterothallic mating system, with unusual highly expanded ~60 kb A locus as a result of accumulating gene transposition. We investigated the population genomics of 60 P. noxius isolates across multiple islands of the Asia Pacific region. Whole‐genome sequencing showed this multinucleate species contains abundant poly‐allelic single nucleotide polymorphisms with atypical allele frequencies. Different patterns of intra‐isolate polymorphism reflect mono‐/heterokaryotic states which are both prevalent in nature. We have shown two genetically separated lineages with one spanning across many islands despite the geographical barriers. Both populations possess extraordinary genetic diversity and show contrasting evolutionary scenarios. These results provide a framework to further investigate the genetic basis underlying the fitness and virulence of white rot fungi.

Signatures of polygenic adaptation associated with climate across the range of a threatened fish species with high genetic connectivity - Katherine A. Harrisson; Stephen J. Amish; Alexandra Pavlova; Shawn R. Narum; Marina Telonis‐Scott; Meaghan L. Rourke; Jarod Lyon; Zeb Tonkin; Dean M. Gilligan; Brett A. Ingram; Mark Lintermans; Han Ming Gan; et al. (Molecular Ecology, 2017)
Adaptive differences across species’ ranges can have important implications for population persistence and conservation management decisions. Despite advances in genomic technologies, detecting adaptive variation in natural populations remains challenging. Key challenges in gene–environment association studies involve distinguishing the effects of drift from those of selection and identifying subtle signatures of polygenic adaptation. We used paired‐end restriction site‐associated DNA sequencing data (6,605 biallelic single nucleotide polymorphisms; SNP s) to examine population structure and test for signatures of adaptation across the geographic range of an iconic Australian endemic freshwater fish species, the Murray cod Maccullochella peelii . Two univariate gene–association methods identified 61 genomic regions associated with climate variation. We also tested for subtle signatures of polygenic adaptation using a multivariate method (redundancy analysis; RDA ). The RDA analysis suggested that climate (temperature‐ and precipitation‐related variables) and geography had similar magnitudes of effect in shaping the distribution of SNP genotypes across the sampled range of Murray cod. Although there was poor agreement among the candidate SNP s identified by the univariate methods, the top 5% of SNP s contributing to significant RDA axes included 67% of the SNP s identified by univariate methods. We discuss the potential implications of our findings for the management of Murray cod and other species generally, particularly in relation to informing conservation actions such as translocations to improve evolutionary resilience of natural populations. Our results highlight the value of using a combination of different approaches, including polygenic methods, when testing for signatures of adaptation in landscape genomic studies.

Design, synthesis, antitumor evaluation, 3D-QSAR and molecular docking studies of novel 4-aminoacridone compounds - Lin Tian; Chang J. Feng; Tong X. Li; Zhao Li; Wei H. Yang; Xiang E. Han (Medicinal Chemistry Research, 2017)

Widespread generalist clones are associated with range and niche expansion in allopolyploids of Pacific Northwest Hawthorns ( Crataegus L.) - J. M. Coughlan; S. Han; S. Stefanović; T. A. Dickinson (Molecular Ecology, 2017)
Range and niche expansion are commonly associated with transitions to asexuality, polyploidy and hybridity (allopolyploidy) in plants. The ability of asexual polyploids to colonize novel habitats may be due to widespread generalist clones, multiple ecologically specialized clones, or may be a neutral by‐product of multiple, independent origins of asexual polyploids throughout the range. We have quantified niche size and divergence for hawthorns of the Pacific Northwest using data from herbarium vouchers with known cytotypes. We find that all polyploid niches diverge from that of the diploid range, and allopolyploids have the broadest niches. Allotetraploids have the largest niche and the widest geographic distribution. We then assessed the genetic mechanism of range expansion by surveying the ecological and geographic distribution of genotypes within each cytotype from sites in which fine‐scale habitat assessments were completed. We find no isolation by either geographic or ecological distance in allopolyploids, suggesting high dispersal and colonization ability. In contrast, autotriploids and diploids show patterns of isolation by geographic distance. We also compared the geographic and ecological distributions of clonal genotypes with those of randomly drawn sites of the most widespread cytotype. We found that most clones are geographically widespread and occur in a variety of habitats. We interpret these findings to suggest that patterns of range and niche expansion in Pacific Northwest Hawthorns may stem from these widespread, ecologically generalist clones of hybrid origin.

Erratum to: Local Interleukin-18 System in the Basolateral Amygdala Regulates Susceptibility to Chronic Stress - Tae-Kyung Kim; Ji-Eun Kim; Juli Choi; Jin-Young Park; Jung-Eun Lee; Eun-Hwa Lee; Yunjin Lee; Bo Yeon Kim; Young J. Oh; Pyung-Lim Han (Molecular Neurobiology, 2017)

Local Interleukin-18 System in the Basolateral Amygdala Regulates Susceptibility to Chronic Stress - Tae-Kyung Kim; Ji-Eun Kim; Juli Choi; Jin-Young Park; Jung-Eun Lee; Eun-Hwa Lee; Yunjin Lee; Bo Yeon Kim; Young J. Oh; Pyung-Lim Han (Molecular Neurobiology, 2017)

Identifying functional groups and ecological roles of tropical and subtropical freshwater Cladocera in Asia - Eric Zeus C. Rizo; Yangliang Gu; Rey Donne S. Papa; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2017)

Soil Organic Carbon Dynamics Responses to Soil Fertility in the Agricultural Regions of China - D. L. Han; X. P. Zhu; H. T. Jia; P. J. Yu (Agricultural Research, 2017)

Cerebellar Pathology in Familial vs. Sporadic Essential Tremor - Elan D. Louis; Sheng-Han Kuo; Jie Wang; William J. Tate; Ming-Kai Pan; Geoffrey C. Kelly; Jesus Gutierrez; Etty P. Cortes; Jean-Paul G. Vonsattel; Phyllis L. Faust (The Cerebellum, 2017)

Study on the application of an activator for steel slag powder–cement in muddy soil - Y. K. Wu; X. S. Hu; R. Hu; T. Han; J. L. Yu (European Journal of Environmental and Civil Engineering, 2017)

Phosphodiesterase-5 inhibitors and their analogues as adulterants of herbal and food products: analysis of the Malaysian market, 2014–16 - Nur Baizura Bujang; Chin Fei Chee; Choon Han Heh; Noorsaadah Abd. Rahman; Michael J. C. Buckle (Food Additives & Contaminants: Part A, 2017)

Site Selection: a Case Study in the Identification of Optimal Cysteine Engineered Antibody Drug Conjugates - L. Nathan Tumey; Fengping Li; Brian Rago; Xiaogang Han; Frank Loganzo; Sylvia Musto; Edmund I. Graziani; Sujiet Puthenveetil; Jeffrey Casavant; Kimberly Marquette; Tracey Clark; Jack Bikker; et al. (The AAPS Journal, 2017)

Effect of Microneedle Type on Transdermal Permeation of Rizatriptan - Chandrateja Uppuluri; Ashraf Sultana Shaik; Tao Han; Atul Nayak; Karthik J. Nair; Benjamin R. Whiteside; Buchi N. Nalluri; Diganta B. Das (AAPS PharmSciTech, 2017)

Metabolites from the co-culture of nigranoic acid and Umbelopsis dimorpha SWUKD3.1410, an endophytic fungus from Kadsura angustifolia - L. Wang; D. Qin; K. Zhang; Q. Huang; S. Liu; M. J. Han; J. Y. Dong (Natural Product Research, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Combined iron and magnesium isotope geochemistry of pyroxenite xenoliths from Hannuoba, North China Craton: implications for mantle metasomatism - Xin Miao Zhao; Hui Hui Cao; Xue Mi; Noreen J. Evans; Yu Han Qi; Fang Huang; Hong Fu Zhang (Contributions to Mineralogy and Petrology, 2017)

Global Mammal Parasite Database version 2.0 - Patrick R. Stephens; Paula Pappalardo; Shan Huang; James E. Byers; Maxwell J. Farrell; Alyssa Gehman; Ria R. Ghai; Sarah E. Haas; Barbara Han; Andrew W. Park; John P. Schmidt; Sonia Altizer; et al. (Ecology, 2017)
Illuminating the ecological and evolutionary dynamics of parasites is one of the most pressing issues facing modern science, and is critical for basic science, the global economy, and human health. Extremely important to this effort are data on the disease‐causing organisms of wild animal hosts (including viruses, bacteria, protozoa, helminths, arthropods, and fungi). Here we present an updated version of the Global Mammal Parasite Database, a database of the parasites of wild ungulates (artiodactyls and perissodactyls), carnivores, and primates, and make it available for download as complete flat files. The updated database has more than 24,000 entries in the main data file alone, representing data from over 2700 literature sources. We include data on sampling method and sample sizes when reported, as well as both “reported” and “corrected” (i.e., standardized) binomials for each host and parasite species. Also included are current higher taxonomies and data on transmission modes used by the majority of species of parasites in the database. In the associated metadata we describe the methods used to identify sources and extract data from the primary literature, how entries were checked for errors, methods used to georeference entries, and how host and parasite taxonomies were standardized across the database. We also provide definitions of the data fields in each of the four files that users can download.

Cerebellar Pathology in Early Onset and Late Onset Essential Tremor - Sheng-Han Kuo; Jie Wang; William J. Tate; Ming-Kai Pan; Geoffrey C. Kelly; Jesus Gutierrez; Etty P. Cortes; Jean-Paul G. Vonsattel; Elan D. Louis; Phyllis L. Faust (The Cerebellum, 2017)

Response of plant functional traits to species origin and adaptive reproduction in weeds - J. H. Liu; X. H. Yong; Q. Han; A. Ali; Y. J. Wang (Plant Biosystems, 2017)

The Next Decade of Big Data in Ecosystem Science - S. L. LaDeau; B. A. Han; E. J. Rosi-Marshall; K. C. Weathers (Ecosystems, 2017)

Sequence variants of the LCORL gene and its association with growth and carcass traits in Qinchuan cattle in China - Y. J. HAN; Y. CHEN; Y. LIU; X. L. LIU (Journal of Genetics, 2017)

CRIM1 is necessary for coronary vascular endothelial cell development and homeostasis - Swati Iyer; Yash Chhabra; Tracey J. Harvey; Richard Wang; Han Sheng Chiu; A. G. Smith; Walter G. Thomas; David J. Pennisi; Michael Piper (Journal of Molecular Histology, 2017)

Anchoring climate change communications - Adam J. L. Harris; Han-Hui Por; Stephen B. Broomell (Climatic Change, 2017)

Termites promote resistance of decomposition to spatiotemporal variability in rainfall - Michiel P. Veldhuis; Francisco J. Laso; Han Olff; Matty P. Berg (Ecology, 2017)
The ecological impact of rapid environmental change will depend on the resistance of key ecosystems processes, which may be promoted by species that exert strong control over local environmental conditions. Recent theoretical work suggests that macrodetritivores increase the resistance of African savanna ecosystems to changing climatic conditions, but experimental evidence is lacking. We examined the effect of large fungus‐growing termites and other non‐fungus‐growing macrodetritivores on decomposition rates empirically with strong spatiotemporal variability in rainfall and temperature. Non‐fungus‐growing larger macrodetritivores (earthworms, woodlice, millipedes) promoted decomposition rates relative to microbes and small soil fauna (+34%) but both groups reduced their activities with decreasing rainfall. However, fungus‐growing termites increased decomposition rates strongest (+123%) under the most water‐limited conditions, making overall decomposition rates mostly independent from rainfall. We conclude that fungus‐growing termites are of special importance in decoupling decomposition rates from spatiotemporal variability in rainfall due to the buffered environment they create within their extended phenotype (mounds), that allows decomposition to continue when abiotic conditions outside are less favorable. This points at a wider class of possibly important ecological processes, where soil‐plant‐animal interactions decouple ecosystem processes from large‐scale climatic gradients. This may strongly alter predictions from current climate change models.

Structuraland antigenic analysis of a new Rhoptry Pseudokinase Gene (ROP54) in Toxoplasma gondii - Jian Zhou; Gang Lu; Lin Wang; Aihua H. Zhou; Yali L. Han; Jingjing J. Guo; Pengxia X. Song; Huaiyu Y. Zhou; Hua Cong; Ming Hou; Shenyi Y. He (Acta Parasitologica, 2017)
is defined as an obligate intracellular apicomplexan parasite and influences approximatelyone-third of the human all over the world. ROP54 protein is expressed in the rhoptry of

Mapping Purkinje Cell Placement Along the Purkinje Cell Layer: an Analysis of Postmortem Tissue from Essential Tremor Patients vs. Controls - Elan D. Louis; Daniel Rabinowitz; Matthew Choe; William J. Tate; Geoffrey C. Kelly; Sheng-Han Kuo; Phyllis L. Faust (The Cerebellum, 2016)

Nitrogen deposition promotes phosphorus uptake of plants in a semi-arid temperate grassland - Min Long; Hong-Hui Wu; Melinda D. Smith; Kimberly J. La Pierre; Xiao-Tao Lü; Hai-Yang Zhang; Xing-Guo Han; Qiang Yu (Plant and Soil, 2016)

Microstructure and Ultrastructure Alterations in the Pallium of Immature Mice Exposed to Cadmium - X. F. Yang; Q. G. Han; D. Y. Liu; H. T. Zhang; G. Y. Fan; J. Y. Ma; Z. L. Wang (Biological Trace Element Research, 2016)

A retinoic acid receptor β2 agonist reduces hepatic stellate cell activation in nonalcoholic fatty liver disease - Steven E. Trasino; Xiao-Han Tang; Jose Jessurun; Lorraine J. Gudas (Journal of Molecular Medicine, 2016)

Outbreak of hirame rhabdovirus infection in cultured spotted sea bass Lateolabrax maculatus on the western coast of Korea - H‐G Seo; J W Do; S H Jung; H‐J Han (Journal of Fish Diseases, 2016)
In this study, we determined the cause of a disease outbreak in spotted sea bass, Lateolabrax maculatus reared in culture cages on the western coast of Korea in 2013. The major signs in the diseased fish exhibited were haemorrhaging on the membranes of the abdomen, gastrointestinal organs and opercular gills, as well as an enlarged spleen. No external morphological signs of infection were visible, except for a darkening in colour. No parasites or pathological bacteria were isolated from the diseased fish; however, epithelioma papulosum cyprini ( EPC ) cells inoculated with tissue homogenates from the diseased fish showed cytopathic effects ( CPE s). Virus particles in the EPC cells were bullet‐shaped, 185–225 nm long and 70–80 nm wide, characteristic of Rhabdoviridae. Polymerase chain reaction analyses of homogenized tissues from the diseased fish and supernatants of cell cultures with CPE s indicated specific, 553‐bp‐long fragments corresponding to the matrix protein gene of the hirame rhabdovirus ( HIRRV ). Phylogenetically, the HIRRV phosphoprotein gene of spotted sea bass was more closely related to phosphoproteins from Chinese and Polish HIRRV strains than from other Korean strains. To our knowledge, this is the first report of HIRRV infection in cultured spotted sea bass.

Phosphorus accumulates faster than nitrogen globally in freshwater ecosystems under anthropogenic impacts - Zhengbing Yan; Wenxuan Han; Josep Peñuelas; Jordi Sardans; James J. Elser; Enzai Du; Peter B. Reich; Jingyun Fang (Ecology Letters, 2016)
Combined effects of cumulative nutrient inputs and biogeochemical processes that occur in freshwater under anthropogenic eutrophication could lead to myriad shifts in nitrogen (N):phosphorus (P) stoichiometry in global freshwater ecosystems, but this is not yet well‐assessed. Here we evaluated the characteristics of N and P stoichiometries in bodies of freshwater and their herbaceous macrophytes across human‐impact levels, regions and periods. Freshwater and its macrophytes had higher N and P concentrations and lower N : P ratios in heavily than lightly human‐impacted environments, further evidenced by spatiotemporal comparisons across eutrophication gradients. N and P concentrations in freshwater ecosystems were positively correlated and N : P was negatively correlated with population density in China. These results indicate a faster accumulation of P than N in human‐impacted freshwater ecosystems, which could have large effects on the trophic webs and biogeochemical cycles of estuaries and coastal areas by freshwater loadings, and reinforce the importance of rehabilitating these ecosystems.

Experimental Investigation on Mechanical Behavior and Permeability Evolution of a Porous Limestone Under Compression - B. Han; S. Y. Xie; J. F. Shao (Rock Mechanics and Rock Engineering, 2016)

Response of herbivore functional groups to sequential perturbations in Moorea, French Polynesia - Xueying Han; Thomas C. Adam; Russell J. Schmitt; Andrew J. Brooks; Sally J. Holbrook (Coral Reefs, 2016)

Synthesis and accumulation of glutenin subunits during grain development in bread wheat as revealed by reversed-phase ultra-performance liquid chromatography (RP-UPLC) - J. Zhou; W. Liu; C. Han; H. Cao; Y. Xu; W. Zhang; Y. Yan (Cereal Research Communications, 2016)

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Effects of functional diversity loss on ecosystem functions are influenced by compensation - Qingmin Pan; Dashuan Tian; Shahid Naeem; Karl Auerswald; James J. Elser; Yongfei Bai; Jianhui Huang; Qibing Wang; Hong Wang; Jianguo Wu; Xingguo Han (Ecology, 2016)
Understanding the impacts of biodiversity loss on ecosystem functioning and services has been a central issue in ecology. Experiments in synthetic communities suggest that biodiversity loss may erode a set of ecosystem functions, but studies in natural communities indicate that the effects of biodiversity loss are usually weak and that multiple functions can be sustained by relatively few species. Yet, the mechanisms by which natural ecosystems are able to maintain multiple functions in the face of diversity loss remain poorly understood. With a long‐term and large‐scale removal experiment in the Inner Mongolian grassland, here we showed that losses of plant functional groups ( PFG s) can reduce multiple ecosystem functions, including biomass production, soil NO 3 ‐N use, net ecosystem carbon exchange, gross ecosystem productivity, and ecosystem respiration, but the magnitudes of these effects depended largely on which PFG s were removed. Removing the two dominant PFG s (perennial rhizomatous grasses and perennial bunchgrasses) simultaneously resulted in dramatic declines in all examined functions, but such declines were circumvented when either dominant PFG was present. We identify the major mechanism for this as a compensation effect by which each dominant PFG can mitigate the losses of others. This study provides evidence that compensation ensuing from PFG losses can mitigate their negative consequence, and thus natural communities may be more resilient to biodiversity loss than currently thought if the remaining PFG s have strong compensation capabilities. On the other hand, ecosystems without well‐developed compensatory functional diversity may be much more vulnerable to biodiversity loss.

The distribution and elevated solubility of lead, arsenic and cesium in contaminated paddy soil enhanced with the electrokinetic field - X. Mao; F. X. Han; X. Shao; K. Guo; J. McComb; S. Njemanze; Z. Arslan; Z. Zhang (International Journal of Environmental Science and Technology, 2016)

An atypical 12q24.31 microdeletion implicates six genes including a histone demethylase KDM2B and a histone methyltransferase SETD1B in syndromic intellectual disability - Jonathan D. J. Labonne; Kang-Han Lee; Shigeki Iwase; Il-Keun Kong; Michael P. Diamond; Lawrence C. Layman; Cheol-Hee Kim; Hyung-Goo Kim (Human Genetics, 2016)

Biocontrol potential of antagonist Bacillus subtilis Tpb55 against tobacco black shank - T. Han; C. You; L. Zhang; C. Feng; C. Zhang; J. Wang; F. Kong (BioControl, 2016)

Understanding super-enhancers - Hao Cheng; Xiaoyang Dou; Jing-Dong J. Han (Science China Life Sciences, 2016)

First comprehensive multi-tissue transcriptome of Cherax quadricarinatus (Decapoda: Parastacidae) reveals unexpected diversity of endogenous cellulase - Mun Hua Tan; Han Ming Gan; Huan You Gan; Yin Peng Lee; Larry J. Croft; Mark B. Schultz; Adam D. Miller; Christopher M. Austin (Organisms Diversity & Evolution, 2016)

Survivin silencing and TRAIL expression using oncolytic adenovirus increase anti-tumorigenic activity in gemcitabine-resistant pancreatic cancer cells - Zhezhu Han; Seungha Lee; Suyeon Je; Chi-Yong Eom; Hye Jin Choi; Jae J. Song; Joo-Hang Kim (Apoptosis, 2016)

Colored Sticky Traps to Selectively Survey Thrips in Cowpea Ecosystem - L D Tang; H Y Zhao; B L Fu; Y Han; K Liu; J H Wu (Neotropical Entomology, 2016)

Exercise protects against PCB-induced inflammation and associated cardiovascular risk factors - Margaret O. Murphy; Michael C. Petriello; Sung Gu Han; Manjula Sunkara; Andrew J. Morris; Karyn Esser; Bernhard Hennig (Environmental Science and Pollution Research, 2016)

Stress-Induced Increases in Levels of Caspases in the Prefrontal Cortex in a Rat Model of PTSD - J. H. Zhang; M. Li; F. Han; Yu X. Shi (Neurophysiology, 2016)

Bacterial biogeography influenced by shelf–basin exchange in the Arctic surface sediment at the C hukchi B orderland - Dukki Han; Seung‐Il Nam; Ho Kyung Ha; Hyoungjun Kim; Michael J. Sadowsky; Yoo Kyung Lee; Hor‐Gil Hur (Environmental Microbiology, 2016)
Summary It has been known that continental shelves around the A rctic O cean play a major role in the ventilation of the deep basins as a consequence of shelf–basin exchange. In the present study, we found that bacterial assemblage of the surface sediment was different from that of seawater while seawater harboured local bacterial assemblages in response to the A rctic hydrography. This finding suggests that the Arctic seafloor sediments may have distinctive bacterial biogeography. Moreover, the distribution of bacterial assemblages and physicochemical properties in surface sediments changed gradually from the A rctic continental shelf to deep‐sea basin. Based on the results, bacterial biogeography in the A rctic seafloor sediments may be influenced by winnowing and re‐deposition of surface sediments through the sediment gravity flow. The present study offers a deeper understanding of shelf convection and its role for the construction of bacterial assemblages in the A rctic O cean.

Belowground competition among invading detritivores - Chih‐Han Chang; Katalin Szlavecz; Timothy Filley; Jeffrey S. Buyer; Michael J. Bernard; Scott L. Pitz (Ecology, 2016)
The factors regulating soil animal communities are poorly understood. Current theory favors niche complementarity and facilitation over competition as the primary forms of non‐trophic interspecific interaction in soil fauna; however, competition has frequently been suggested as an important community‐structuring factor in earthworms, ecosystem engineers that influence belowground processes. To date, direct evidence of competition in earthworms is lacking due to the difficulty inherent in identifying a limiting resource for saprophagous animals. In the present study, we offer the first direct evidence of interspecific competition for food in this dominant soil detritivore group by combining field observations with laboratory mesocosm experiments using 13 C and 15 N double‐enriched leaf litter to track consumption patterns. In our experiments, the Asian invasive species Amynthas hilgendorfi was a dominant competitor for leaf litter against two European species currently invading the temperate deciduous forests in North America. This competitive advantage may account for recent invasion success of A. hilgendorfi in forests with established populations of European species, and we hypothesize that specific phenological differences play an important role in determining the outcome of the belowground competition. In contrast, Eisenoides lonnbergi , a common native species in the Eastern United States, occupied a unique trophic position with limited interactions with other species, which may contribute to its persistence in habitats dominated by invasive species. Furthermore, our results supported neither the hypothesis that facilitation occurs between species of different functional groups nor the hypothesis that species in the same group exhibit functional equivalency in C and N translocation in the soil. We propose that species identity is a more powerful approach to understand earthworm invasion and its impacts on belowground processes.

Antithetical effects of nitrogen and water availability on community similarity of semiarid grasslands: evidence from a nine-year manipulation experiment - Zhuwen Xu; Haiyan Ren; Jiangping Cai; Ruzhen Wang; Peng He; Mai-He Li; Bernard J. Lewis; Xingguo Han; Yong Jiang (Plant and Soil, 2015)

Scaffolding during the cell cycle by A-kinase anchoring proteins - B. Han; W. J. Poppinga; M. Schmidt (Pflügers Archiv - European Journal of Physiology, 2015)

Cognition and Depression Following Deep Brain Stimulation of the Subthalamic Nucleus and Globus Pallidus Pars Internus in Parkinson’s Disease: A Meta-Analysis - Hannah L. Combs; Bradley S. Folley; David T. R. Berry; Suzanne C. Segerstrom; Dong Y. Han; Amelia J. Anderson-Mooney; Brittany D. Walls; Craig van Horne (Neuropsychology Review, 2015)

Speciation processes in putative island endemic sister bat species: false impressions from mitochondrial DNA and microsatellite data - Hao‐Chih Kuo; Shiang‐Fan Chen; Yin‐Ping Fang; James A. Cotton; Joe D. Parker; Gábor Csorba; Burton K. Lim; Judith L. Eger; Chia‐Hong Chen; Cheng‐Han Chou; Stephen J. Rossiter (Molecular Ecology, 2015)
Cases of geographically restricted co‐occurring sister taxa are rare and may point to potential divergence with gene flow. The two bat species Murina gracilis and Murina recondita are both endemic to Taiwan and are putative sister species. To test for nonallopatric divergence and gene flow in these taxa, we generated sequences using Sanger and next‐generation sequencing, and combined these with microsatellite data for coalescent‐based analyses. Mt DNA phylogenies supported the reciprocally monophyletic sister relationship between M. gracilis and M. recondita ; however, clustering of microsatellite genotypes revealed several cases of species admixture suggesting possible introgression. Sequencing of microsatellite flanking regions revealed that admixture signatures stemmed from microsatellite allele homoplasy rather than recent introgressive hybridization, and also uncovered an unexpected sister relationship between M. recondita and the continental species Murina eleryi , to the exclusion of M. gracilis . To dissect the basis of these conflicts between nc DNA and mt DNA , we analysed sequences from 10 anonymous nc DNA loci with * beast and isolation‐with‐migration and found two distinct clades of M. eleryi , one of which was sister to M. recondita . We conclude that Taiwan was colonized by the ancestor of M. gracilis first, followed by the ancestor of M. recondita after a period of allopatric divergence. After colonization, the mitochondrial genome of M. recondita was replaced by that of the resident M. gracilis . This study illustrates how apparent signatures of sympatric divergence can arise from complex histories of allopatric divergence, colonization and hybridization, thus highlighting the need for rigorous analyses to distinguish between such scenarios.

Vegetation, fire, and climate history during the last 18 500 cal a BP in south‐western Yunnan Province, China - Xiayun Xiao; J. I. Shen; Simon G. Haberle; Yong Han; Bin Xue; Enlou Zhang; Sumin Wang; Guobang Tong (Journal of Quaternary Science, 2015)
High‐resolution pollen and charcoal records from Qinghai Lake in south‐western China are presented. The records reveal variations in vegetation, fire and climate history since 18 500 cal a BP. The results show that seven significant vegetation changes are recorded, which are responses to climate changes and/or fire events. Frequent and intensive fires occurred during the periods 17 900–15 000, 13 000–11 500 and 4280–980 cal a BP, corresponding to relatively dry climatic conditions. Combined with the climatic record from Tiancai Lake, the regional climatic changes since 18 500 cal a BP in western Yunnan Province are reconstructed. Namely, the Heinrich Event 1, the Bølling–Allerød warm period and the Younger Dryas event during the last deglaciation are ubiquitous in western Yunnan Province. The start of the Holocene is recorded at 11 500 cal a BP. The Holocene climatic optimum occurred between 8450 and 4280 cal a BP. After 4280 cal a BP, the climate deteriorated, accompanied by evidence for human impact. Based on this study, we consider that vegetation and climatic changes since 18 500 cal a BP in south‐western Yunnan Province are primarily driven by September and average summer solar insolation, with some associated influence from regional sea‐surface temperature and sea‐level rise.

Tuna and swordfish catch in the U.S. northwest Atlantic longline fishery in relation to mesoscale eddies - Ango C. Hsu; Andre M. Boustany; Jason J. Roberts; Jui‐Han Chang; Patrick N. Halpin (Fisheries Oceanography, 2015)

Effect of a Rho Kinase Inhibitor on Cognitive Impairment Induced by Chronic Cerebral Hypoperfusion in Rats - Q. Zhang; J.-J. Zhang; Zh.-M. Han (Neurophysiology, 2015)

QTL mapping of adult-plant resistance to stripe rust in wheat line P9897 - X. L. Zhou; D. J. Han; X. M. Chen; J. M. Mu; W. B. Xue; Q. D. Zeng; Q. L. Wang; L. L. Huang; Z. S. Kang (Euphytica, 2015)

Expression profile analysis of hippocampal CA1 pyramidal neurons in aged Ts65Dn mice, a model of Down syndrome (DS) and Alzheimer’s disease (AD) - Melissa J. Alldred; Sang Han Lee; Eva Petkova; Stephen D. Ginsberg (Brain Structure and Function, 2015)

Wood–Plastic Composite Technology - Douglas J. Gardner; Yousoo Han; Lu Wang (Current Forestry Reports, 2015)

Structural and stratigraphic characteristics on distal parts of the outer fold and thrust belt of southern Niger Delta, Nigeria - E. K. Nyantakyi; Tao Li; WangShui Hu; J. K. Borkloe; Songze Li; M. Han Cheng (Arabian Journal of Geosciences, 2015)

Identification of QTL for adult plant resistance to stripe rust in Chinese wheat landrace Caoxuan 5 - X. L. Zhou; Y. Zhang; Q. D. Zeng; X. M. Chen; D. J. Han; L. L. Huang; Z. S. Kang (Euphytica, 2015)

The Domain II S4-S5 Linker in Nav1.9: A Missense Mutation Enhances Activation, Impairs Fast Inactivation, and Produces Human Painful Neuropathy - Chongyang Han; Yang Yang; Bianca T. A. de Greef; Janneke G. J. Hoeijmakers; Monique M. Gerrits; Camiel Verhamme; Jian Qu; Giuseppe Lauria; Ingemar S. J. Merkies; Catharina G. Faber; Sulayman D. Dib-Hajj; Stephen G. Waxman (NeuroMolecular Medicine, 2015)

Purification and characterization of a novel α-glucosidase from Malbranchea cinnamomea - Q. J. Yan; P. Han; S. Q. Yang; Z. Q. Jiang (Biotechnology Letters, 2015)

Profiling the Role of Deacylation-Reacylation in the Lymphatic Transport of a Triglyceride-Mimetic Prodrug - Sifei Han; Luojuan Hu; Tim Quach; Jamie S. Simpson; Natalie L. Trevaskis; Christopher J. H. Porter (Pharmaceutical Research, 2015)

Application of a high-surface-area schwertmannite in the removal of arsenate and arsenite - J. Song; S.-Y. Jia; H.-T. Ren; S.-H. Wu; X. Han (International Journal of Environmental Science and Technology, 2015)

Sensitivity of Alternaria solani to boscalid and control of boscalid resistance with commonly-used fungicides in Shanxi, China - X. J. Shi; L. Ren; Y. Q. Song; J. C. Han; H. P. Liu; Y. J. Zhang (Australasian Plant Pathology, 2015)

Influence of Constant Temperature on Development and Reproduction of Encarsia guadeloupae Viggiani (Hymenoptera: Aphelinidae), a Parasitoid of the Spiraling Whitefly Aleurodicus dispersus Russell (Hemiptera: Aleyrodidae) - J Y Chen; L M Niu; L Li; D Y Han; Y G Fu (Neotropical Entomology, 2015)

Hymenoscyphus fraxineus and two new Hymenoscyphus species identified in Korea - A. Gross; J. G. Han (Mycological Progress, 2015)

Response of a phytoplanktonic assemblage to copper and zinc enrichment in microcosm - Lalit K. Pandey; T. Han; J. P. Gaur (Ecotoxicology, 2015)

Understanding the Microbial Internal Storage Turnover in Wastewater Treatment: Retrospect, Prospect, and Challenge - Bing-Jie Ni; Han-Qing Yu; Raymond J. Zeng (Critical Reviews in Environmental Science and Technology, 2015)

Social stress and escalated drug self-administration in mice I. Alcohol and corticosterone - Kevin J. Norman; Jacob A. Seiden; Jacob A. Klickstein; Xiao Han; Lara S. Hwa; Joseph F. DeBold; Klaus A. Miczek (Psychopharmacology, 2015)

Gastric cancer in three relatives of a patient with a biallelic IL12RB1 mutation - Ingrid P. Vogelaar; Rachel S. van der Post; Esther van de Vosse; J. Han J. M. van Krieken; Nicoline Hoogerbrugge; Marjolijn J. L. Ligtenberg; Encarna Gómez García (Familial Cancer, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Functionality and prevalence of trehalose‐based oligosaccharides as novel compatible solutes in ascospores of N eosartorya fischeri ( A spergillus fischeri ) and other fungi - Timon T. Wyatt; M. Richard van Leeuwen; Elena A. Golovina; Folkert A. Hoekstra; Eric J. Kuenstner; Edward A. Palumbo; Nicole L. Snyder; Cobus Visagie; Alex Verkennis; John E. Hallsworth; Han A.B. Wösten; Jan Dijksterhuis (Environmental Microbiology, 2015)
Summary Ascospores of N eosartorya , B yssochlamys and T alaromyces can be regarded as the most stress‐resistant eukaryotic cells. They can survive exposure at temperatures as high as 85° C for 100 min or more. N eosartorya fischeri ascospores are more viscous and more resistant to the combined stress of heat and desiccation than the ascospores of T alaromyces macrosporus which contain predominantly trehalose. These ascospores contain trehalose‐based oligosaccharides ( TOS ) that are novel compatible solutes, which are accumulated to high levels. These compounds are also found in other members of the genus N eosartorya and in some other genera within the order Eurotiales that also include B yssochlamys and T alaromyces . The presence of oligosaccharides was observed in species that had a relatively high growth temperature. TOS glasses have a higher glass transition temperature ( T g ) than trehalose, and they form a stable glass with crystallizing molecules, such as mannitol. Our data indicate that TOS are important for prolonged stabilization of cells against stress. The possible unique role of these solutes in protection against dry heat conditions is discussed.

Characterization of the microbial community in different types of Daqu samples as revealed by 16S rRNA and 26S rRNA gene clone libraries - Xiao-Wei Zheng; Zheng Yan; M. J. Robert Nout; Teun Boekhout; Bei-Zhong Han; Marcel H. Zwietering; Eddy J. Smid (World Journal of Microbiology and Biotechnology, 2015)

Effect of repeated exposures and sociality on novel food acceptance and consumption by orangutans - Madeleine E. Hardus; Adriano R. Lameira; Serge A. Wich; Han de Vries; Rachmad Wahyudi; Robert W. Shumaker; Steph B. J. Menken (Primates, 2015)

RA induces differentiation of multipotent P19 cells towards male germ cell - Lei Zhang; Jiangjing Tang; Christopher J Haines; Huai Feng; Xiaoming Teng; Yibing Han (In Vitro Cellular & Developmental Biology - Animal, 2015)

Polarization of excitation light influences molecule counting in single-molecule localization microscopy - Ye Chen; Han Lin; Mandy J. Ludford-Menting; Andrew H. Clayton; Min Gu; Sarah M. Russell (Histochemistry and Cell Biology, 2015)

Effects of experimentally-enhanced precipitation and nitrogen on resistance, recovery and resilience of a semi-arid grassland after drought - Zhuwen Xu; Haiyan Ren; Jiangping Cai; Ruzhen Wang; Mai-He Li; Shiqiang Wan; Xingguo Han; Bernard J. Lewis; Yong Jiang (Oecologia, 2014)

Evaluating the causal basis of ecological success within the scleractinia: an integral projection model approach - Peter J. Edmunds; Scott C. Burgess; Hollie M. Putnam; Marissa L. Baskett; Lorenzo Bramanti; Nick S. Fabina; Xueying Han; Michael P. Lesser; Joshua S. Madin; Christopher B. Wall; Denise M. Yost; Ruth D. Gates (Marine Biology, 2014)

Health Literacy and Pap Testing in Insured Women - K. M. Mazor; A. E. Williams; D. W. Roblin; B. Gaglio; S. L. Cutrona; M. E. Costanza; P. K. J. Han; J. L. Wagner; H. Fouayzi; T. S. Field (Journal of Cancer Education, 2014)

Characterization and molecular mapping of stripe rust resistance gene Yr61 in winter wheat cultivar Pindong 34 - X. L. Zhou; D. J. Han; X. M. Chen; H. L. Gou; S. J. Guo; L. Rong; Q. L. Wang; L. L. Huang; Z. S. Kang (Theoretical and Applied Genetics, 2014)

Screening survey of co-production of fusaric acid, fusarin C, and fumonisins B1, B2 and B3 by Fusarium strains grown in maize grains - Z. Han; E. K. Tangni; B. Huybrechts; F. Munaut; J. Scauflaire; A. Wu; A. Callebaut (Mycotoxin Research, 2014)

Impact of ubiquitous computing technologies on changing travel and land use patterns - S. H. Lee; Y. T. Leem; J. H. Han (International Journal of Environmental Science and Technology, 2014)

Limited diagnostic value of microsatellite instability associated pathology features in colorectal cancer - Paul G. van Putten; Margot G. F. van Lier; Mariska Hage; Katharina Biermann; Reinier H. van Rijssel; Pieter J. Westenend; Hans Morreau; Ewout W. Steyerberg; Winand N. M. Dinjens; Ernst J. Kuipers; Monique E. van Leerdam; J. Han van Krieken (Familial Cancer, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Optimization of sono-assisted dilute sulfuric acid process for simultaneous pretreatment and saccharification of rice straw - M. S. U. Rehman; I. Kim; K. H. Kim; J.-I. Han (International Journal of Environmental Science and Technology, 2014)

Keratinocyte growth factor and thiazolidinediones and linolenic acid differentiate characterized mammary fat pad adipose stem cells isolated from prepubertal Korean black goat to epithelial and adipogenic lineage - A. M. M. T Reza; S. Shiwani; N. K. Singh; J. D. Lohakare; S. J. Lee; D. K. Jeong; J. Y. Han; D. Rengaraj; B. W. Lee (In Vitro Cellular & Developmental Biology - Animal, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

A genome-wide association study of severe teenage acne in European Americans - Mingfeng Zhang; Abrar A. Qureshi; David J. Hunter; Jiali Han (Human Genetics, 2014)

Molecular mapping of a stripe rust resistance gene in wheat cultivar Wuhan 2 - X. L. Zhou; D. J. Han; H. L. Gou; Q. L. Wang; Q. D. Zeng; F. P. Yuan; G. M. Zhan; L. L. Huang; Z. S. Kang (Euphytica, 2014)
Stripe rust (or yellow rust), caused by Puccinia striiformis f. sp. tritici , is one of the most destructive diseases of wheat worldwide. Growing resistant cultivars is the best approach to control the disease. To identify and map genes for stripe rust resistance in wheat cultivar ‘Wuhan 2', an F 2 population was developed from a cross between the cultivar and susceptible cultivar Mingxian 169. The parents, 179 F 2 plants and their derived F 2:3 lines were evaluated for responses to Chinese races CYR30 and CYR31 of the pathogen in a greenhouse. A recessive gene for resistance was identified. DNA bulked segregant analysis was applied and resistance gene analog polymorphism (RGAP) and simple sequence repeat (SSR) techniques were used to identify molecular markers linked to the resistance gene. A genetic map consisting of five RGAP and six SSR markers was constructed. The recessive gene, designated Yrwh2 , was located on the short arm of chromosome 3B and flanked by SSR markers Xwmc540 and Xgwm566 at 5.9 and 10.0 cM, respectively. The chromosomal location of the resistance gene and its close marker suggest that the locus is different from previously reported stripe rust resistance genes Yr30 , QYr.ucw - 3BS , Yrns - B1 , YrRub and QYrex.wgp - 3BL previously mapped to chromosome 3B. Yrwh2 and its closely linked markers are potentially useful for developing stripe rust resistance wheat cultivars if used in combination with other genes.

The physiological and nutritional responses of seven different citrus rootstock seedlings to boron deficiency - Gao F. Zhou; Shu A. Peng; Yong Z. Liu; Qing J. Wei; Jia Han; Md. Zahidul Islam (Trees, 2014)

Molecular characterisation and evolution of HMW glutenin subunit genes in Brachypodium distachyon L. - Saminathan Subburaj; Guanxing Chen; Caixia Han; Dongwen Lv; Xiaohui Li; Friedrich J. Zeller; Sai L. K. Hsam; Yueming Yan (Journal of Applied Genetics, 2014)

The value of multiple earthquake missions: the EEFIT L’Aquila Earthquake experience - T. Rossetto; D. D’Ayala; F. Gori; R. Persio; J. Han; V. Novelli; S. M. Wilkinson; D. Alexander; M. Hill; S. Stephens; S. Kontoe; G. Elia; et al. (Bulletin of Earthquake Engineering, 2014)

A Novel Approach to Evaluate the Pharmacokinetic Biocomparability of a Monoclonal Antibody Derived from Two Different Cell Lines Using Simultaneous Crossover Design - Chao Han; Thomas S. McIntosh; Brian J. Geist; Trina Jiao; Thomas A. Puchalski; Kenneth M. Goldberg; Tong-Yuan Yang; Charles E. Pendley; Honghui Zhou; Hugh M. Davis (The AAPS Journal, 2014)

NtERF32: a non-NIC2 locus AP2/ERF transcription factor required in jasmonate-inducible nicotine biosynthesis in tobacco - Marta T. Sears; Hongbo Zhang; Paul J. Rushton; Martin Wu; Shengcheng Han; Anthony J. Spano; Michael P. Timko (Plant Molecular Biology, 2014)

CXCR4 pathway associated with family history of melanoma - Wen-Qing Li; Jiali Han; Hans R. Widlund; Mick Correll; Yaoyu E. Wang; John Quackenbush; Martin C. Mihm; Alvaro Laga Canales; Shaowei Wu; Todd Golub; Yujin Hoshida; David J. Hunter; et al. (Cancer Causes & Control, 2014)

Retrospective serosurveillance of bovine norovirus (GIII.2) and nebovirus in cattle from selected feedlots and a veal calf farm in 1999 to 2001 in the United States - Christopher Thomas; Kwonil Jung; Myung-Guk Han; Armando Hoet; Kelly Scheuer; Qiuhong Wang; Linda J. Saif (Archives of Virology, 2014)

Isolation and characterization of two VpYABBY genes from wild Chinese Vitis pseudoreticulata - J. Xiang; R. Q. Liu; T. M. Li; L. J. Han; Y. Zou; T. F. Xu; J. Y. Wei; Y. J. Wang; Y. Xu (Protoplasma, 2013)

Challenge of weed risk assessment (WRA) for ecological restoration in China: The case of Rhus typhina L. and the new officially released weed risk assessment system - G. M. Wang; J. C. Yang; C. D. Jiang; G. M. Jiang; J. B. Yu; H. B. Shao; G. X. Han; Y. J. Gao (Plant Biosystems, 2013)

Effects of connectivity, dispersal directionality and functional traits on the metacommunity structure of river benthic diatoms - Jing Liu; Janne Soininen; Bo‐Ping Han; Steven A. J. Declerck (Journal of Biogeography, 2013)
Aim Dendritic ecological networks ( DEN s), such as river systems, combine features that challenge the traditional conceptual views and empirical approaches applied to metacommunities. As a result of their dendritic branching geometry and stream flow directionality, they are strongly hierarchical and asymmetrical. We analysed the metacommunity structure of benthic diatoms in a large‐scale river system with the aim of evaluating the importance of potential causal influences. Furthermore, we hypothesized that metacommunities of diatoms that are strongly attached to their substrata show a different spatial structure than metacommunities of other, more weakly attached diatoms. Location The study was carried out in the Dong River, a 32,275 km 2 subtropical river network located in southern China. Methods We surveyed benthic diatom communities during three seasons (dry, intermediate and wet). Using partial redundancy analysis, we partitioned community variation among environmental models and different spatial eigenfunction models to evaluate the influence of alternative dispersal pathways (overland versus water course dispersal), stream directionality, man‐made dams and diatom functional traits on diatom metacommunity structure. Results Models based on hydrological connections and water directionality represent spatial patterns better than overland distances, suggesting that the dynamics of benthic diatom metacommunities are mainly confined to the river network and influenced by the prevailing water flow. We found significant effects of man‐made dams on the spatial structure of important limnological variables and diatom metacommunity structure. The metacommunity of strongly attached diatoms also showed a weaker signature of flow directionality than that of other growth forms, especially in seasons with high water levels. Main conclusions We conclude that the consideration of among‐site connectivity, flow directionality and species traits is key to a better understanding of the spatial ecology of passively dispersing microbial organisms in river systems.

Genetic variations in the myostatin gene (MSTN) in New Zealand sheep breeds - J. Han; R. H. Forrest; J. G. H. Hickford (Molecular Biology Reports, 2013)

Non-trophic Interactions Control Benthic Producers on Intertidal Flats - Serena Donadi; Joëlle Westra; Ellen J. Weerman; Tjisse van der Heide; Els M. van der Zee; Johan van de Koppel; Han Olff; Theunis Piersma; Henk W. van der Veer; Britas Klemens Eriksson (Ecosystems, 2013)

Microbial diversity and dynamics of microbial communities during back-slop soaking of soybeans as determined by PCR–DGGE and molecular cloning - Yinzhuo Yan; Judith Wolkers-Rooijackers; M. J. Robert Nout; Beizhong Han (World Journal of Microbiology and Biotechnology, 2013)

Diabetes and prostate cancer screening in black and white men - Maureen Sanderson; Jay H. Fowke; Loren Lipworth; Xijing Han; Flora Ukoli; Ann L. Coker; William J. Blot; Margaret K. Hargreaves (Cancer Causes & Control, 2013)

More breast cancer patients prefer BRCA-mutation testing without prior face-to-face genetic counseling - Aisha S. Sie; Wendy A. G. van Zelst-Stams; Liesbeth Spruijt; Arjen R. Mensenkamp; Marjolijn J. L. Ligtenberg; Han G. Brunner; Judith B. Prins; Nicoline Hoogerbrugge (Familial Cancer, 2013)

Modelling the dispersal of C alanus finmarchicus on the N ewfoundland S helf: implications for the analysis of population dynamics from a high frequency monitoring site - Pierre Pepin; Guoqi Han; Erica J. Head (Fisheries Oceanography, 2013)
We investigated the drift of passive particles on the N ewfoundland S helf and western L abrador S ea using numerical simulations to assess the possible sources of plankton collected at a high frequency sampling site (S27; 47.55°N, 52.59°W) located near the coast of N ewfoundland, C anada. We also summarized data detailing the seasonal stage succession of C alanus finmarchicus at that site, as well as along three oceanographic sections sampled in the spring, summer and autumn across the adjacent continental shelf. Simulations indicated that the L abrador and N ewfoundland S helves represent the major sources of particles transiting through the S 27 site, with relatively minor contributions from the western L abrador S ea which are significant during a few months each year. The latter point may be affected by uncertainty in the representation of cross‐shelf transport associated with seasonal or short‐term variations in atmospheric and oceanic forcing, which may also affect the strength and location of bifurcation of the inner branch of the L abrador C urrent around the G rand B anks. Nevertheless, our results indicated that drift along the inner shelf is likely to be the primary source of copepods collected at S 27 throughout most of the year. This in turn suggested that there may be a higher degree of connectivity between conditions in coastal areas of N ewfoundland and those in B affin B ay and west G reenland than with the southern half of the L abrador S ea.

Electrospun Rapamycin-Eluting Polyurethane Fibers for Vascular Grafts - Jingjia Han; Shady Farah; Abraham J. Domb; Peter I. Lelkes (Pharmaceutical Research, 2013)

Biosorption of methylene blue from aqueous solutions by Typha angustata phytomass - M. Saif Ur Rehman; J.-I. Han (International Journal of Environmental Science and Technology, 2013)

Pathogenesis of type 1 (European genotype) porcine reproductive and respiratory syndrome virus in male gonads of infected boar - K. Han; H. W. Seo; Y. Oh; I. Kang; C. Park; J. H. Han; S.-H. Kim; C. Chae (Veterinary Research Communications, 2013)

Herbivore trampling as an alternative pathway for explaining differences in nitrogen mineralization in moist grasslands - Maarten Schrama; Pieter Heijning; Jan P. Bakker; Harm J. van Wijnen; Matty P. Berg; Han Olff (Oecologia, 2013)

Separating nitrogen fertilizer and irrigation water application in an alternating furrow irrigation system for maize production - Kun Han; Chunju Zhou; Na Li; John P. Schmidt; Curtis J. Dell; Linquan Wang (Nutrient Cycling in Agroecosystems, 2013)

Reconstructing the origin and dispersal patterns of village chickens across E ast A frica: insights from autosomal markers - J. M. Mwacharo; K. Nomura; H. Hanada; J. L. Han; T. Amano; O. Hanotte (Molecular Ecology, 2013)
Unravelling the genetic history of any livestock species is central to understanding the origin, development and expansion of agricultural societies and economies. Domestic village chickens are widespread in Africa. Their close association with, and reliance on, humans for long‐range dispersal makes the species an important biological marker in tracking cultural and trading contacts between human societies and civilizations across time. Archaezoological and linguistic evidence suggest a complex history of arrival and dispersion of the species on the continent, with mitochondrial DNA (mt DNA ) D‐loop analysis revealing the presence of five distinct haplogroups in East African village chickens. It supports the importance of the region in understanding the history of the species and indirectly of human interactions. Here, through a detailed analysis of 30 autosomal microsatellite markers genotyped in 657 village chickens from four East African countries (Kenya, Uganda, Ethiopia and Sudan), we identify three distinct autosomal gene pools ( I , II and III ). Gene pool I is predominantly found in Ethiopia and Sudan, while II and III occur in both Kenya and Uganda. A gradient of admixture for gene pools II and III between the Kenyan coast and Uganda's hinterland ( P = 0.001) is observed, while gene pool I is clearly separated from the other two. We propose that these three gene pools represent genetic signatures of separate events in the history of the continent that relate to the arrival and dispersal of village chickens and humans across the region. Our results provide new insights on the history of chicken husbandry which has been shaped by terrestrial and maritime contacts between ancient and modern civilizations in Asia and East Africa.

A new caryolane sesquiterpene from Heteropappus altaicus (Willd.) Novopokr. - H. Huang; X.J. Gao; J. Liu; S. Li; Y.F. Han; B.C. Zhou; M. Xia (Natural Product Research, 2013)

Study of chloropropanols in soy sauce by gas chromatography-triple quadrupole mass spectrometry with coupled column separation without derivatisation - X.-M. Xu; H.-W. Wu; H.-L. He; B.-F. Huang; J.-L. Han; Y.-P. Ren (Food Additives & Contaminants: Part A, 2013)

Understanding human diseases with high-throughput quantitative measurement and analysis of molecular signatures - Li Yang; Gang Wei; Kun Tang; Christine Nardini; Jing-Dong J. Han (Science China Life Sciences, 2013)

Comparison of wavelet estimation methods - Bo Y. Yi; Gwang H. Lee; Han-Joon Kim; Hyeong-Tae Jou; Dong G. Yoo; Byong J. Ryu; Keumsuk Lee (Geosciences Journal, 2013)

Socioecological correlates of inter-individual variation in orangutan diets at Ketambe, Sumatra - Madeleine E. Hardus; Han de Vries; David F. Dellatore; Adriano R. Lameira; Steph B. J. Menken; Serge A. Wich (Behavioral Ecology and Sociobiology, 2013)

Absence of induced resistance in Agaricus bisporus against Lecanicillium fungicola - Roeland L. Berendsen; Niek Schrier; Stefanie I. C. Kalkhove; Luis G. Lugones; Johan J. P. Baars; Carolien Zijlstra; Marjanne de Weerdt; Han A. B. Wösten; Peter A. H. M. Bakker (Antonie van Leeuwenhoek, 2013)

Simultaneous analysis of 17 diuretics in dietary supplements by HPLC and LC-MS/MS - H. Woo; J.W. Kim; K.M. Han; J.H. Lee; I.S. Hwang; J.H. Lee; J. Kim; S.J. Kweon; S. Cho; K.R. Chae; S.Y. Han; J. Kim (Food Additives & Contaminants: Part A, 2013)

Effect of cholesterol on lipogenesis and VLDL–TG assembly and secretion in goose primary hepatocytes - C. C. Han; J. W. Wang; Z. X. Pan; H. Tang; S. X. Xiang; J. Wang; L. Li; F. Xu; S. H. Wei (Molecular and Cellular Biochemistry, 2013)

Choice of microsatellite markers for identifying homozygosity of mitotic gynogenetic diploids in Japanese flounder Paralichthys olivaceus - Y. X. Liu; H. Z. Han; Q. L. Wang; L. Jiang; S. L. Wang; X. Y. Zhang; Y. Liu; Y. F. Wang; Y. J. Liu; H. J. Liu (Journal of Fish Biology, 2013)
A set of 72 microsatellite markers distributed evenly among 24 linkage groups were selected from the published genetic linkage maps of Japanese flounder Paralichthys olivaceus . In two normal diploid full‐sib families, the test for Mendelian inheritance showed that genotypic segregation deviations were not significant at all analysed loci. To estimate microsatellite‐centromere map distances, four meiotic gynogenetic diploid lines were produced by the activation of eggs using UV irradiated sperm of red seabream Pagrus major and cold‐shock treatment to block the extrusion of the second polar body. Under the assumption of complete interference, 21 markers were located in the centromeric region, 39 in the telomeric region and the rest in the intermediate region of linkage groups. A total of 192 mitotic gynogenetic diploids from one spawn were identified by these markers. Genotype analysis showed that the number of homozygous individuals decreased as microsatellite‐centromere map distance increased on each linkage group.

Cross‐habitat interactions among bivalve species control community structure on intertidal flats - Serena Donadi; Tjisse van der Heide; Els M. van der Zee; Johan S. Eklöf; Johan van de Koppel; Ellen J. Weerman; Theunis Piersma; Han Olff; Britas Klemens Eriksson (Ecology, 2013)
Increasing evidence shows that spatial interactions between sedentary organisms can structure communities and promote landscape complexity in many ecosystems. Here we tested the hypothesis that reef‐forming mussels ( Mytilus edulis L.), a dominant intertidal ecosystem engineer in the Wadden Sea, promote abundances of the burrowing bivalve Cerastoderma edule L. (cockle) in neighboring habitats at relatively long distances coastward from mussel beds. Field surveys within and around three mussel beds showed a peak in cockle densities at 50–100 m toward the coast from the mussel bed, while cockle abundances elsewhere in the study area were very low. Field transplantation of cockles showed higher survival of young cockles (2–3 years old) and increased spat fall coastward of the mussel bed compared to within the bed and to areas without mussels, whereas growth decreased within and coastward of the mussel bed. Our measurements suggest that the observed spatial patterns in cockle numbers resulted from (1) inhibition effects by the mussels close to the beds due to preemptive algal depletion and deteriorated sediment conditions and (2) facilitation effects by the mussels farther away from the beds due to reduction of wave energy. Our results imply that these spatial, scale‐dependent interactions between reef‐forming ecosystem engineers and surrounding communities of sedentary benthic organisms can be an important determinant of the large‐scale community structure in intertidal ecosystems. Understanding this interplay between neighboring communities of sedentary species is therefore essential for effective conservation and restoration of soft‐bottom intertidal communities.

Classification of Surface EMGs Using Wavelet Packet Energy Analysis and a Genetic Algorithm-Based Support Vector Machine - Y. Rong; D. Hao; X. Han; Y. Zhang; J. Zhang; Y. Zeng (Neurophysiology, 2013)

CSF biomarker associations with change in hippocampal volume and precuneus thickness: implications for the Alzheimer’s pathological cascade - Nikki H. Stricker; Hiroko H. Dodge; N. Maritza Dowling; S. Duke Han; Elena A. Erosheva; William J. Jagust (Brain Imaging and Behavior, 2012)

Water Maze Spatial Learning Enhances Social Recognition Ability in Aged Rats - Q. Zeng; J. Han; B. Wang; Sh. An; Y. Duan; S. Dong; J. Ma; L. Yang; X. Cao (Neurophysiology, 2012)

Massive invasion of Arctodiaptomus dorsalis (Copepoda, Calanoida, Diaptomidae) in Philippine lakes: a threat to Asian zooplankton biodiversity? - Rey Donne S. Papa; Huiming Li; Dino T. Tordesillas; Boping Han; Henri J. Dumont (Biological Invasions, 2012)

Testing the metabolic theory of ecology - Charles A. Price; Joshua S Weitz; Van M. Savage; James Stegen; Andrew Clarke; David A. Coomes; Peter S. Dodds; Rampal S. Etienne; Andrew J. Kerkhoff; Katherine McCulloh; Karl J. Niklas; Han Olff; et al. (Ecology Letters, 2012)
The metabolic theory of ecology (MTE) predicts the effects of body size and temperature on metabolism through considerations of vascular distribution networks and biochemical kinetics. MTE has also been extended to characterise processes from cellular to global levels. MTE has generated both enthusiasm and controversy across a broad range of research areas. However, most efforts that claim to validate or invalidate MTE have focused on testing predictions. We argue that critical evaluation of MTE also requires strong tests of both its theoretical foundations and simplifying assumptions. To this end, we synthesise available information and find that MTE's original derivations require additional assumptions to obtain the full scope of attendant predictions. Moreover, although some of MTE's simplifying assumptions are well supported by data, others are inconsistent with empirical tests and even more remain untested. Further, although many predictions are empirically supported on average, work remains to explain the often large variability in data. We suggest that greater effort be focused on evaluating MTE's underlying theory and simplifying assumptions to help delineate the scope of MTE, generate new theory and shed light on fundamental aspects of biological form and function.

Co-expression of soybean Dicer-like genes in response to stress and development - Shaun J. Curtin; Michael B. Kantar; Han W. Yoon; Adam M. Whaley; Jessica A. Schlueter; Robert M. Stupar (Functional & Integrative Genomics, 2012)

Targeting CreERT2 expression to keratin 8-expressing murine simple epithelia using bacterial artificial chromosome transgenesis - Li Zhang; Boyu Zhang; Sang Jun Han; Amy N. Shore; Jeffrey M. Rosen; Francesco J. DeMayo; Li Xin (Transgenic Research, 2012)

Specific herbivore‐induced volatiles defend plants and determine insect community composition in the field - Y. Xiao; Q. Wang; M. Erb; T. C. J. Turlings; L. Ge; L. Hu; J. Li; X. Han; T. Zhang; J. Lu; G. Zhang; Y. Lou (Ecology Letters, 2012)
In response to insect attack, plants release complex blends of volatile compounds. These volatiles serve as foraging cues for herbivores, predators and parasitoids, leading to plant‐mediated interactions within and between trophic levels. Hence, plant volatiles may be important determinants of insect community composition. To test this, we created rice lines that are impaired in the emission of two major signals, S‐ linalool and ( E )‐β‐caryophyllene. We found that inducible S‐ linalool attracted predators and parasitoids as well as chewing herbivores, but repelled the rice brown planthopper Nilaparvata lugens , a major pest. The constitutively produced ( E )‐β‐caryophyllene on the other hand attracted both parasitoids and planthoppers, resulting in an increased herbivore load. Thus, silencing either signal resulted in specific insect assemblages in the field, highlighting the importance of plant volatiles in determining insect community structures. Moreover, the results imply that the manipulation of volatile emissions in crops has great potential for the control of pest populations.

Prolonged exclusive breastfeeding, autumn birth and increased gestational age are associated with lower risk of fever in children with hand, foot, and mouth disease - Q. Zhu; Y. Li; N. Li; Q. Han; Z. Liu; Z. Li; J. Qiu; G. Zhang; F. Li; N. Tian (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Non-steroidal anti-inflammatory drugs, acetaminophen, and risk of skin cancer in the Nurses’ Health Study - J. M. Jeter; J. Han; M. E. Martinez; D. S. Alberts; A. A. Qureshi; D. Feskanich (Cancer Causes & Control, 2012)

Familial gastric cancer: guidelines for diagnosis, treatment and periodic surveillance - Irma Kluijt; Rolf H. Sijmons; Nicoline Hoogerbrugge; John T. Plukker; Daphne de Jong; J. Han van Krieken; Richard van Hillegersberg; Marjolijn Ligtenberg; Eveline Bleiker; Anemieke Cats (Familial Cancer, 2012)

Agronomic Considerations for Sweet Sorghum Biofuel Production in the South-Central USA - K. J. Han; W. D. Pitman; M. W. Alison; D. L. Harrell; H. P. Viator; M. E. McCormick; K. A. Gravois; M. Kim; D. F. Day (BioEnergy Research, 2012)

Modeling of Spatiotemporal Thermal Response to CO2 Injection in Saline Formations: Interpretation for Monitoring - Weon Shik Han; Kue-Young Kim; Eungyu Park; Brian J. McPherson; Si-Yong Lee; Myong-Ho Park (Transport in Porous Media, 2012)

Erratum to: Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Multi-scale Structural and Tensile Mechanical Response of Annulus Fibrosus to Osmotic Loading - Woojin M. Han; Nandan L. Nerurkar; Lachlan J. Smith; Nathan T. Jacobs; Robert L. Mauck; Dawn M. Elliott (Annals of Biomedical Engineering, 2012)

China’s wastewater discharge standards in urbanization - Wen-Wei Li; Guo-Ping Sheng; Raymond J. Zeng; Xian-Wei Liu; Han-Qing Yu (Environmental Science and Pollution Research, 2012)

Elevated skin autofluorescence is strongly associated with foot ulcers in patients with diabetes: a cross-sectional, observational study of Chinese subjects - Hang Hu; Chun-mao Han; Xin-lei Hu; Wan-lan Ye; Wen-juan Huang; Andries J. Smit (Journal of Zhejiang University-SCIENCE B, 2012)

Isolation and Characterization of a Lytic Myoviridae Bacteriophage PAS-1 with Broad Infectivity in Aeromonas salmonicida - J. H. Kim; J. S. Son; Y. J. Choi; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; D. H. Kang; C. Oh; S. J. Heo; S. C. Park (Current Microbiology, 2012)

Mechanisms to prevent caspase activation in rotenone-induced dopaminergic neurodegeneration: role of ATP depletion and procaspase-9 degradation - HeeWon Kang; Baek-Soo Han; Su-Jeong Kim; Young J. Oh (Apoptosis, 2012)

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

Use of total precipitable water classification of a priori error and quality control in atmospheric temperature and water vapor sounding retrieval - Eun-Han Kwon; Jun Li; Jinlong Li; B. J. Sohn; Elisabeth Weisz (Advances in Atmospheric Sciences, 2012)

Application of tyramide signal amplification‐fluorescence in situ hybridisation and flow cytometry to detection of Heterosigma akashiwo (Raphidophyceae) in natural waters - J Lee; T Katano; M Chang; M‐S Han (New Zealand Journal of Marine and Freshwater Research, 2012)
We developed protocols to analyse the cell cycle of Heterosigma akashiwo in the natural phytoplankton assemblage using tyramide signal amplification‐fluorescence in situ hybridisation (TSA‐FISH) and flow cytometry. We determined the optimum probe and formamide concentrations for the species‐specific TSA‐FISH probe to be 0.5 ng µL −1 and 40%, respectively. The probe did not hybridise to non‐target phytoplankton including Chattonella sp., which is closely related to Heterosigma and has high sequence similarity to it. We could successfully identify G1‐ and G2‐phase cells and the diel cell cycle of H. akashiwo not only in the laboratory but also in the field after TSA‐FISH. These results demonstrate that TSA‐FISH for H. akashiwo in natural coastal waters could serve as a powerful tool for understanding their bloom mechanism using flow cytometry.

Complete genomic sequence of a T4-like bacteriophage, phiAS4, infecting Aeromonas salmonicida subsp. salmonicida - J. H. Kim; J. S. Son; Y. J. Choi; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; S. C. Park (Archives of Virology, 2012)

Genomic sequence of infectious hypodermal and hematopoietic necrosis virus (IHHNV) KLV-2010-01 originating from the first Korean outbreak in cultured Litopenaeus vannamei - J. H. Kim; H. K. Kim; V. G. Nguyen; B. K. Park; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; S. C. Park (Archives of Virology, 2012)

Specimen‐Based Modeling, Stopping Rules, and the Extinction of the Ivory‐Billed Woodpecker - NICHOLAS J. GOTELLI; ANNE CHAO; ROBERT K. COLWELL; WEN‐HAN HWANG; GARY R. GRAVES (Conservation Biology, 2012)
Assessing species survival status is an essential component of conservation programs. We devised a new statistical method for estimating the probability of species persistence from the temporal sequence of collection dates of museum specimens. To complement this approach, we developed quantitative stopping rules for terminating the search for missing or allegedly extinct species. These stopping rules are based on survey data for counts of co‐occurring species that are encountered in the search for a target species. We illustrate both these methods with a case study of the Ivory‐billed Woodpecker ( Campephilus principalis ), long assumed to have become extinct in the United States in the 1950s, but reportedly rediscovered in 2004. We analyzed the temporal pattern of the collection dates of 239 geo‐referenced museum specimens collected throughout the southeastern United States from 1853 to 1932 and estimated the probability of persistence in 2011 as −5 , with a probable extinction date no later than 1980. From an analysis of avian census data (counts of individuals) at 4 sites where searches for the woodpecker were conducted since 2004, we estimated that at most 1–3 undetected species may remain in 3 sites (one each in Louisiana, Mississippi, Florida). At a fourth site on the Congaree River (South Carolina), no singletons (species represented by one observation) remained after 15,500 counts of individual birds, indicating that the number of species already recorded (56) is unlikely to increase with additional survey effort. Collectively, these results suggest there is virtually no chance the Ivory‐billed Woodpecker is currently extant within its historical range in the southeastern United States. The results also suggest conservation resources devoted to its rediscovery and recovery could be better allocated to other species. The methods we describe for estimating species extinction dates and the probability of persistence are generally applicable to other species for which sufficient museum collections and field census results are available.

Sensitivity Study of Simulation Parameters Controlling CO2 Trapping Mechanisms in Saline Formations - Weon Shik Han; Kue-Young Kim; Richard P. Esser; Eungyu Park; Brian J. McPherson (Transport in Porous Media, 2011)

Translocation and oligomerization of Bax is regulated independently by activation of p38 MAPK and caspase-2 during MN9D dopaminergic neurodegeneration - Chang-Ki Oh; Baek-Soo Han; Won-Seok Choi; Moussa B. H. Youdim; Young J. Oh (Apoptosis, 2011)

Prevalence and different characteristics of two serotypes of Streptococcus parauberis isolated from the farmed olive flounder, Paralichthys olivaceus (Temminck and Schlegel), in Korea - S Y Han; B K Kang; B J Kang; S P Shin; B H Soen; J M Kim; J H Kim; C H Choresca; J E Han; J W Jun; S C Park (Journal of Fish Diseases, 2011)
The prevalence of two serotypes of Streptococcus parauberis isolated from the olive flounder, Paralichthys olivaceus , was evaluated in a total of 29 isolates between 2003 and 2010 in Korea. Streptococcus parauberis isolates were divided into two serologically distinct types (serotype 1 and serotype 2), except for one strain (S1091), using an agglutination assay with rabbit antiserum, and serotype 1 was identified as the dominant type (24 of 29 isolates) in this study. To identify the characteristics of the two serotypes of S. parauberis , we conducted a biochemical test using the API 20 Strep kit, a transmission electron microscopy (TEM) assay, sequence analysis of 16S‐23S rRNA intergenic spacer region (ISR) and a pathogenicity test. In TEM, both serotypes possessed polysaccharide capsule layers around the cell surface when bacterial cells were treated with a homologous serotype of rabbit antiserum. However, we were unable to discriminate serotype‐specific biochemical characteristics and genetic characteristics of 16S‐23S rRNA ISR between the two serotypes. In the pathogenicity test, the serotype 1 strains induced significantly higher mortality than the serotype 2 strains in olive flounder when experimentally inoculated via the intraperitoneal route.

Individual and combined effects of multiple pathogens on Pacific treefrogs - John M. Romansic; Pieter T. J. Johnson; Catherine L. Searle; James E. Johnson; Tate S. Tunstall; Barbara A. Han; Jason R. Rohr; Andrew R. Blaustein (Oecologia, 2011)

Species-level correlates of susceptibility to the pathogenic amphibian fungus Batrachochytrium dendrobatidis in the United States - Betsy A. Bancroft; Barbara A. Han; Catherine L. Searle; Lindsay M. Biga; Deanna H. Olson; Lee B. Kats; Joshua J. Lawler; Andrew R. Blaustein (Biodiversity and Conservation, 2011)

Increase in Rubisco activity and gene expression due to elevated temperature partially counteracts ultraviolet radiation–induced photoinhibition in the marine diatom Thalassiosira weissflogii - E. Walter Helbling; Anita G. J. Buma; Peter Boelen; Han J. van der Strate; M. Valeria Fiorda Giordanino; Virginia E. Villafañe (Limnology and Oceanography, 2011)
We performed outdoor experiments to evaluate the effect of temperature on photoinhibition properties in the cosmopolitan diatom Thalassiosira weissflogii . Cultures were exposed to solar radiation with or without ultraviolet radiation (UVR, 280–400 nm), UV‐A (320–400 nm), and UV‐B (280–320 nm) at both 20°C and 25°C. Four possible cellular mechanisms involved in UVR stress were simultaneously addressed: carbon incorporation, chlorophyll a fluorescence of photosystem II, xanthophyll cycle activity, and ribulose‐1,5‐biphosphate carboxylase : oxygenase (Rubisco) activity and gene expression. Experiments consisted of daily cycles (i.e., the daylight period) and short‐term incubations (i.e., 1 h centered on local noon). Samples incubated at 25°C had significantly less UVR‐induced inhibition of carbon fixation and effective photochemical quantum yield compared to those incubated at 20°C. At 25°C Rubisco activity and gene expression were significantly higher than at 20°C. The higher Rubisco activity and gene expression were correlated with less dissipation of excess energy, evaluated via non‐photochemical quenching, and the de‐epoxidation state of the xanthophyll pigments, as more photons could be processed. An increase in temperature due to climate change would partially counteract the negative effects of UVR by increasing the response of metabolic pathways, such as those involved in Rubisco. This, in turn, may have important consequences for the ecosystem, as higher production (due to more Rubisco activity) could be expected under a scenario of global warming.

The spatial and temporal subsidence variability of the East Mesa Geothermal Field, California, USA, and its potential impact on the All American Canal System - Joo-Yup Han; R. R. Forster; D. E. Moser; A. L. J. Ford; J. Ramírez-Hernández; K. F. Tiampo (International Journal of Remote Sensing, 2011)

Why is Diaphanosoma (Crustacea: Ctenopoda) so common in the tropics? Influence of temperature and food on the population parameters of Diaphanosoma dubium, and a hypothesis on the nature of tropical cladocerans - Bo-Ping Han; Juan Yin; Xian Lin; Henri J. Dumont (Hydrobiologia, 2011)

The physico-chemical characterization of casein-modified surfaces and their influence on the adhesion of spores from a Geobacillus species - Jingtian Han; R Brent Seale; Patrick Silcock; A James McQuillan; Phil J. Bremer (Biofouling, 2011)

Rapid top–down regulation of plant C:N:P stoichiometry by grasshoppers in an Inner Mongolia grassland ecosystem - Guangming Zhang; Xingguo Han; James J. Elser (Oecologia, 2011)

Stoichiometric homeostasis of vascular plants in the Inner Mongolia grassland - Qiang Yu; James J. Elser; Nianpeng He; Honghui Wu; Quansheng Chen; Guangming Zhang; Xingguo Han (Oecologia, 2011)

Smoking and alcohol drinking increased the risk of esophageal cancer among Chinese men but not women in a high-risk population - Ming Wu; Jin-Kou Zhao; Zuo-Feng Zhang; Ren-Qiang Han; Jie Yang; Jin-Yi Zhou; Xu-Shan Wang; Xiao-Feng Zhang; Ai-Min Liu; Pieter van’ t Veer; Frans J. Kok; Ellen Kampman (Cancer Causes & Control, 2011)

Assessment of satellite-based rainfall estimates in urban areas in different geographic and climatic regions - Woo Suk Han; Steven J. Burian; J. Marshall Shepherd (Natural Hazards, 2011)

Spatial variations of atmospheric methane concentrations in China - Xiuying Zhang; Hong Jiang; Yueqi Wang; Ying Han; M. Buchwitz; O. Schneising; J. P. Burrows (International Journal of Remote Sensing, 2011)

All-trans- and 9-cis-retinoic acids activate the human cyclooxynase-2 gene: a role for DR1 as RARE or RXRE - Kyuyong Han; Irene Moon; Hyunjung J. Lim (Molecular Biology Reports, 2011)

Pelagic flatworm predation on daphniids in a subtropical reservoir: different effects on Daphnia galeata and on Ceriodaphnia quadrangula - Tian Wang; Lijuan Xiao; Qiuqi Lin; Bo-Ping Han; Henri J. Dumont (Hydrobiologia, 2011)

Atypical Aeromonas salmonicida infection in the black rockfish, Sebastes schlegeli Hilgendorf , in Korea - H‐J Han; D‐Y Kim; W‐S Kim; C‐S Kim; S‐J Jung; M‐J Oh; D‐H Kim (Journal of Fish Diseases, 2011)
Cultured black rockfish, Sebastes schlegeli , suffered mass mortalities during winter 2008 and spring 2009 in Korea, showing clinical signs of ulcer lesions and haemorrhages over their body surface. The aetiological agent was identified as Aeromonas salmonicida (strains RFAS‐1, ‐2 and ‐3), which is a non‐pigmented, slow‐growing bacterium. Phenotypes of RFAS strains showed variation, while 16S rRNA, gyrB , rpoD , dnaJ and recA gene sequences of all the strains were affiliated to A. salmonicida. In particular, vapA gene sequences of the strains were most closely related to one of the five subspecies of A. salmonicida subsp. masoucida (=KCCM 40239 T ). LD 50 values of RFAS‐1 for intraperitoneal and intramuscular injection were 1.5 × 10 5.25 and 1.5 × 10 6.4 cfu/rockfish, respectively. However, A. salmonicida strains KCCM 40239 T and SAS‐1, which originate from masou and chum salmon, respectively, were not pathogenic to black rockfish. RFAS strains, possessing A‐layer protein on their surface, exhibited β‐haemolytic activity against rockfish erythrocytes and capability to survive in rockfish serum, which seem to be associated with virulence.

Nicotinic acetylcholine receptor genes on chromosome 15q25.1 are associated with nicotine and opioid dependence severity - Porat M. Erlich; Stuart N. Hoffman; Margaret Rukstalis; John J. Han; Xin Chu; W. H. Linda Kao; Glenn S. Gerhard; Walter F. Stewart; Joseph A. Boscarino (Human Genetics, 2010)

Linking stoichiometric homoeostasis with ecosystem structure, functioning and stability - Qiang Yu; Quansheng Chen; James J. Elser; Nianpeng He; Honghui Wu; Guangming Zhang; Jianguo Wu; Yongfei Bai; Xingguo Han (Ecology Letters, 2010)
Ecology Letters (2010) 13: 1390–1399 Abstract Ecosystem structure, functioning and stability have been a focus of ecological and environmental sciences during the past two decades. The mechanisms underlying their relationship, however, are not well understood. Based on comprehensive studies in Inner Mongolia grassland, here we show that species‐level stoichiometric homoeostasis was consistently positively correlated with dominance and stability on both 2‐year and 27‐year temporal scales and across a 1200‐km spatial transect. At the community level, stoichiometric homoeostasis was also positively correlated with ecosystem function and stability in most cases. Thus, homoeostatic species tend to have high and stable biomass; and ecosystems dominated by more homoeostatic species have higher productivity and greater stability. By modulating organism responses to key environmental drivers, stoichiometric homoeostasis appears to be a major mechanism responsible for the structure, functioning and stability of grassland ecosystems.

Mapping of BrdU label-retaining dental pulp cells in growing teeth and their regenerative capacity after injuries - Yuko Ishikawa; Hiroko Ida-Yonemochi; Hironobu Suzuki; Kuniko Nakakura-Ohshima; Han-Sung Jung; Masaki J. Honda; Yumiko Ishii; Nobukazu Watanabe; Hayato Ohshima (Histochemistry and Cell Biology, 2010)

Master donor viruses A/Leningrad/134/17/57 (H2N2) and B/USSR/60/69 and derived reassortants used in live attenuated influenza vaccine (LAIV) do not display neurovirulent properties in a mouse model - J. Theo M. Voeten; Irina V. Kiseleva; Harrie L. Glansbeek; Stephanie M. C. Basten; Sandra K. M. Drieszen-van der Cruijsen; Larisa G. Rudenko; Han van den Bosch; Jacco G. M. Heldens (Archives of Virology, 2010)

Determination of Imazaquin and its Metabolite by Liquid Chromatography-Quadrupole-Time of Flight Tandem Mass - H. B. Yao; G. J. Han; G. X. Liu; Y. Xie; C. H. Wang (Bulletin of Environmental Contamination and Toxicology, 2010)

Does larval duration contribute to population genetic isolation of the Japanese eel Anguilla japonica ? - Y. S. HAN; C. L. HUNG; Y. IIZUKA; H. C. CHANG; B. J. CHANG; H. C. HO; J. C. SHIAO (Fisheries Management and Ecology, 2010)

The genome of Syntrophomonas wolfei : new insights into syntrophic metabolism and biohydrogen production - Jessica R. Sieber; David R. Sims; Cliff Han; Edwin Kim; Athanasios Lykidis; Alla L. Lapidus; Erin McDonnald; Lars Rohlin; David E. Culley; Robert Gunsalus; Michael J. McInerney (Environmental Microbiology, 2010)
Summary Syntrophomonas wolfei is a specialist, evolutionarily adapted for syntrophic growth with methanogens and other hydrogen‐ and/or formate‐using microorganisms. This slow‐growing anaerobe has three putative ribosome RNA operons, each of which has 16S rRNA and 23S rRNA genes of different length and multiple 5S rRNA genes. The genome also contains 10 RNA‐directed, DNA polymerase genes. Genomic analysis shows that S. wolfei relies solely on the reduction of protons, bicarbonate or unsaturated fatty acids to re‐oxidize reduced cofactors. Syntrophomonas wolfei lacks the genes needed for aerobic or anaerobic respiration and has an exceptionally limited ability to create ion gradients. An ATP synthase and a pyrophosphatase were the only systems detected capable of creating an ion gradient. Multiple homologues for β‐oxidation genes were present even though S. wolfei uses a limited range of fatty acids from four to eight carbons in length . Syntrophomonas wolfei , other syntrophic metabolizers with completed genomic sequences, and thermophilic anaerobes known to produce high molar ratios of hydrogen from glucose have genes to produce H 2 from NADH by an electron bifurcation mechanism. Comparative genomic analysis also suggests that formate production from NADH may involve electron bifurcation. A membrane‐bound, iron–sulfur oxidoreductase found in S. wolfei and Syntrophus aciditrophicus may be uniquely involved in reverse electron transport during syntrophic fatty acid metabolism. The genome sequence of S. wolfei reveals several core reactions that may be characteristic of syntrophic fatty acid metabolism and illustrates how biological systems produce hydrogen from thermodynamically difficult reactions.

Human Enteric Viruses in Groundwater - S. H. Park; E. J. Kim; T. H. Yun; J. H. Lee; C. K. Kim; Y. H. Seo; S. A. Oh; S. S. Choi; S. J. Cho; M. S. Kim; G. Y. Han; M. Y. Kim; et al. (Food and Environmental Virology, 2010)

Female BRCA mutation carriers with a preference for prophylactic mastectomy are more likely to participate an educational-support group and to proceed with the preferred intervention within 2 years - Karin M. Landsbergen; Judith B. Prins; Yvonne J. L. Kamm; Han G. Brunner; Nicoline Hoogerbrugge (Familial Cancer, 2010)

Population structure of the olive flounder ( Paralichthys olivaceus ) in Korea inferred from microsatellite marker analysis - W.‐J. Kim; K.‐K. Kim; H.‐S. Han; B.‐H. Nam; Y.‐O. Kim; H.‐J. Kong; J.‐K. Noh; M. Yoon (Journal of Fish Biology, 2010)
The population structure of olive flounder Paralichthys olivaceus was estimated using nine polymorphic microsatellite (MS) loci in 459 individuals collected from eight populations, including five wild and three hatchery populations in Korea. Genetic variation in hatchery (mean number of alleles per locus, A = 10·2–12·1; allelic richness, A R = 9·3–10·1; observed heterozygosity, H O = 0·766–0·805) and wild (mean number of alleles per locus, A = 11·8–19·6; allelic richness, A R = 10·9–16·1; observed heterozygosity, H O = 0·820–0·888) samples did not differ significantly, suggesting a sufficient level of genetic variation in these well‐managed hatchery populations, which have not lost a substantial amount of genetic diversity. Neighbour‐joining tree and principal component analyses showed that genetic separation between eastern and pooled western and southern wild populations in Korea was probably influenced by restricted gene flow between regional populations due to the barrier effects of sea currents. The pooled western and southern populations are genetically close, perhaps because larval dispersal may depend on warm currents. One wild population (sample from Wando) was genetically divergent from the main distribution, but it was genetically close to hatchery populations, indicating that the genetic composition of the studied populations may be affected by hydrographic conditions and the release of fish stocks. The estimated genetic population structure and potential applications of MS markers may aid in the proper management of P. olivaceus populations.

Landscape‐scale analyses suggest both nutrient and antipredator advantages to Serengeti herbivore hotspots - T. Michael Anderson; J. Grant C. Hopcraft; Stephanie Eby; Mark Ritchie; James B. Grace; Han Olff (Ecology, 2010)
Mechanistic explanations of herbivore spatial distribution have focused largely on either resource‐related (bottom‐up) or predation‐related (top‐down) factors. We studied direct and indirect influences on the spatial distributions of Serengeti herbivore hotspots, defined as temporally stable areas inhabited by mixed herds of resident grazers. Remote sensing and variation in landscape features were first used to create a map of the spatial distribution of hotspots, which was tested for accuracy against an independent data set of herbivore observations. Subsequently, we applied structural equation modeling to data on soil fertility and plant quality and quantity across a range of sites. We found that hotspots in Serengeti occur in areas that are relatively flat and located away from rivers, sites where ungulates are less susceptible to predation. Further, hotspots tend to occur in areas where hydrology and rainfall create conditions of relatively low‐standing plant biomass, which, coupled with grazing, increases forage quality while decreasing predation risk. Low‐standing biomass and higher leaf concentrations of N, Na, and Mg were strong direct predictors of hotspot occurrence. Soil fertility had indirect effects on hotspot occurrence by promoting leaf Na and Mg. The results indicate that landscape features contribute in direct and indirect ways to influence the spatial distribution of hotspots and that the best models incorporated both resource‐ and predation‐related factors. Our study highlights the collective and simultaneous role of bottom‐up and top‐down factors in determining ungulate spatial distributions.

Effect of paraquat on the antioxidative enzyme activities and lipid peroxidation in opium poppy (Papaver somniferum L.) - R. Zhao; P. -Y. Guo; X. -Y. Yuan; J. -Y. Wang; M. -Q. Han (Journal of Plant Diseases and Protection, 2010)

Changes in the frequency, scale, and failing areas of latest Quaternary (<29.4 cal. ka B.P.) slope failures along the SW Ulleung Basin, East Sea (Japan Sea), inferred from depositional characters of densely dated turbidite successions - Sang Hoon Lee; Jang J. Bahk; Han J. Kim; Kyung E. Lee; Hyeong T. Jou; Bong C. Suk (Geo-Marine Letters, 2010)

A novel single-nucleotide polymorphism of thevisfatin gene and its associations with performance traits in the chicken - R. L. Han; X. Y. Lan; L. Z. Zhang; G. Ren; Y. J. Jing; M. J. Li; B. Zhang; M. Zhao; Y. K. Guo; X. T. Kang; H. Chen (Journal of Applied Genetics, 2010)

Internal reflection pattern of Korea Strait shelf mud (Nakdong River subaqueous delta) off southeast Korea and implications for Holocene relative base‐level change - Gwang H. Lee; Dae C. Kim; Mi K. Park; Soo C. Park; Han J. Kim; Hyeong T. Jou; Boo K. Khim (Island Arc, 2010)
The Korea Strait shelf mud (KSSM) (Nakdong River subaqueous delta) is the most conspicuous Holocene sedimentary feature in the inner shelf off southeast Korea. Analysis of multi‐channel sparker profiles and 14 C ages of sediment cores reveals that the KSSM consists of three seismic units at the depocenter (>60 m thick): (i) the thin transgressive bottom (> ca 8000 cal bp ); (ii) thick (>40 m) obliquely progradational middle ( ca 8000– ca 2600 cal bp ); and (iii) thin transgressive top ( ca 2600 cal bp –present) units. The relative base level, predicted from the internal reflection pattern of the KSSM, remained significantly deeper (up to >70 m) than global sealevel during much of the Holocene. The apparent gradual drop (∼20 m) of the relative base level during the deposition of the middle unit, followed by a rise, further suggests that base level does not conform to sealevel and is more sensitive than the relative sealevel is to the local oceanographic regime and processes.

Application of an Improved Flow-Stress-Damage Model to the Criticality Assessment of Water Inrush in a Mine: a Case Study - H. Q. Zhang; Y. N. He; C. A. Tang; Bashir Ahmad; L. J. Han (Rock Mechanics and Rock Engineering, 2009)

Estimated PBDE and PBB Congeners in Soil from an Electronics Waste Disposal Site - H.-M. Wang; Y.-J. Yu; M. Han; S.-W. Yang; Q. li; Y. Yang (Bulletin of Environmental Contamination and Toxicology, 2009)

Molecular characterization of hepatitis A virus isolated from acute gastroenteritis patients in the Seoul region of Korea - S.-H. Park; E.-J. Kim; J.-H. Lee; S.-S. Choi; M.-S. Kim; S.-S. Jung; G.-Y. Han; H.-S. Yun; D.-S. Chun; S.-S. Oh; H.-S. Kim (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Luminescent Donor-Acceptor β-Diketones: Modulation of Emission by Solvent Polarity and Group II Metal Binding - Guoqing Zhang; Shin Han Kim; Ruffin E. Evans; Byeong Hyo Kim; J. N. Demas; Cassandra L. Fraser (Journal of Fluorescence, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

Comments on “Abrupt-Interface Solution for Carbon dioxide Injection into Porous Media” by M. Dentz and D. Tartakovsky - Chuan Lu; Si-Yong Lee; Weon Shik Han; Brain J. McPherson; Peter C. Lichtner (Transport in Porous Media, 2009)

Genetic relationships between preharvest sprouting and dormancy in barley - S. E. Ullrich; H. Lee; J. A. Clancy; I. A. del Blanco; V. A. Jitkov; A. Kleinhofs; F. Han; D. Prada; I. Romagosa; J. L. Molina-Cano (Euphytica, 2009)

Hydrogeochemical Indicators of Groundwater Flow Systems in the Yangwu River Alluvial Fan, Xinzhou Basin, Shanxi, China - Dongmei Han; Xing Liang; Menggui Jin; Matthew J. Currell; Ying Han; Xianfang Song (Environmental Management, 2009)

Analysis of genetic structure and relationship among nine indigenous Chinese chicken populations by the Structure program - H. F. Li; W. Han; Y. F. Zhu; J. T. Shu; X. Y. Zhang; K. W. Chen (Journal of Genetics, 2009)

Embryogenic tissue initiation and somatic embryogenesis in Fraser fir (Abies fraseir [Pursh] Poir.) - Y. W. Kim; R. Newton; J. Frampton; K.-H. Han (In Vitro Cellular & Developmental Biology - Plant, 2009)

Physicochemical and Immunological Characterization of N,N,N-Trimethyl Chitosan-Coated Whole Inactivated Influenza Virus Vaccine for Intranasal Administration - Niels Hagenaars; Enrico Mastrobattista; Rolf J. Verheul; Imke Mooren; Harrie L. Glansbeek; Jacco G. M. Heldens; Han van den Bosch; Wim Jiskoot (Pharmaceutical Research, 2009)

Taking species abundance distributions beyond individuals - Hélène Morlon; Ethan P. White; Rampal S. Etienne; Jessica L. Green; Annette Ostling; David Alonso; Brian J. Enquist; Fangliang He; Allen Hurlbert; Anne E. Magurran; Brian A. Maurer; Brian J. McGill; et al. (Ecology Letters, 2009)
The species abundance distribution (SAD) is one of the few universal patterns in ecology. Research on this fundamental distribution has primarily focused on the study of numerical counts, irrespective of the traits of individuals. Here we show that considering a set of Generalized Species Abundance Distributions (GSADs) encompassing several abundance measures, such as numerical abundance, biomass and resource use, can provide novel insights into the structure of ecological communities and the forces that organize them. We use a taxonomically diverse combination of macroecological data sets to investigate the similarities and differences between GSADs. We then use probability theory to explore, under parsimonious assumptions, theoretical linkages among them. Our study suggests that examining different GSADs simultaneously in natural systems may help with assessing determinants of community structure. Broadening SADs to encompass multiple abundance measures opens novel perspectives in biodiversity research and warrants future empirical and theoretical developments.

Monitoring large herbivore diversity at different scales: comparing direct and indirect methods - Joris P. G. M. Cromsigt; Susan J. van Rensburg; Rampal S. Etienne; Han Olff (Biodiversity and Conservation, 2009)

The intergenic region of Arabidopsis thaliana cab1 and cab2 divergent genes functions as a bidirectional promoter - Anish Mitra; Jigang Han; Zhanyuan J. Zhang; Amitava Mitra (Planta, 2009)

Informative study designs to identify true parameter–covariate relationships - Phey Yen Han; Carl M. J. Kirkpatrick; Bruce Green (Journal of Pharmacokinetics and Pharmacodynamics, 2009)

A functional SNP in the MDM2 promoter, pigmentary phenotypes, and risk of skin cancer - Hongmei Nan; Abrar A. Qureshi; David J. Hunter; Jiali Han (Cancer Causes & Control, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Nonlinear cooperation of p53-ING1-induced bax expression and protein S-nitrosylation in GSNO-induced thymocyte apoptosis: a quantitative approach with cross-platform validation - Shaojin Duan; Lin Wan; Wenjiang J. Fu; Hong Pan; Qi Ding; Chang Chen; Peiwei Han; Xiaoyan Zhu; Liying Du; Hongxiao Liu; Yuxia Chen; Ximing Liu; et al. (Apoptosis, 2009)

Estimation of the gross primary production of an old‐growth temperate mixed forest using eddy covariance and remote sensing - J. B. Wu; X. M. Xiao; D. X. Guan; T. T. Shi; C. J. Jin; S. J. Han (International Journal of Remote Sensing, 2009)

Resistance to race 2 and cross-resistance to race 1 of Kabatiella caulivora in Trifolium subterraneum and T. purpureum - Hua Li; P. G. H. Nichols; S. Han; K. J. Foster; K. Sivasithamparam; M. J. Barbetti (Australasian Plant Pathology, 2009)

Cadmium and zinc-mediated oxidative burst in tobacco BY-2 cell suspension cultures - Anna Źróbek-Sokolnik; Han Asard; Kamilla Górska-Koplińska; Ryszard J. Górecki (Acta Physiologiae Plantarum, 2009)

Neural network determination of cloud attenuation to estimate insolation using MTSAT‐1R data - J.‐M. Yeom; K.‐S. Han; Y.‐S. Kim; J.‐D. Jang (International Journal of Remote Sensing, 2008)

Ivermectin inhibits LPS-induced production of inflammatory cytokines and improves LPS-induced survival in mice - X. Zhang; Y. Song; X. Ci; N. An; Y. Ju; H. Li; X. Wang; C. Han; J. Cui; X. Deng (Inflammation Research, 2008)

Is human placenta proteoglycan remodeling involved in pre-eclampsia? - Mohamad Warda; Fuming Zhang; Moustafa Radwan; Zhenqing Zhang; Nari Kim; Young Nam Kim; Robert J. Linhardt; Jin Han (Glycoconjugate Journal, 2008)

Identification of a recombinant dengue virus type 1 with 3 recombination regions in natural populations in Guangdong province, China - S.-P. Chen; M. Yu; T. Jiang; Y.-Q. Deng; C.-F. Qin; J.-F. Han; E.-D. Qin (Archives of Virology, 2008)

Effects of brassinolide on the survival, growth and drought resistance of Robinia pseudoacacia seedlings under water-stress - K. R. Li; H. H. Wang; G. Han; Q. J. Wang; J. Fan (New Forests, 2008)

Agrobacterium-mediated transformation of maize (Zea mays) with Cre-lox site specific recombination cassettes in BIBAC vectors - Juan M. Vega; Weichang Yu; Fangpu Han; Akio Kato; Eric M. Peters; Zhanyuan J. Zhang; James A. Birchler (Plant Molecular Biology, 2008)

Using oligonucleotide suspension arrays for laboratory identification of bacteria responsible for bacteremia - Xiao-li Hou; Han-liang Jiang; Qing-yi Cao; Li-ying Zhao; Barbara J. Chang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2008)

Changes in Chlorophyll Fluorescence in Maize Plants with Imposed Rapid Dehydration at Different Leaf Ages - Z. Z. Xu; G. S. Zhou; Y. L. Wang; G. X. Han; Y. J. Li (Journal of Plant Growth Regulation, 2008)

Cysts of PRKCSH mutated polycystic liver disease patients lack hepatocystin but express Sec63p - Esmé Waanders; Huib J. E. Croes; Cathy N. Maass; René H. M. Morsche; Hendrikus J. A. A. Geffen; J. Han J. M. Krieken; Jack A. M. Fransen; Joost P. H. Drenth (Histochemistry and Cell Biology, 2008)

Characterization of a Homogentisate Dioxygenase Mutant in Pseudomonas chlororaphis O6 - B. R. Kang; S. H. Han; S. M. Cho; A. J. Anderson; I. S. Kim; S. K. Park; Y. C. Kim (Current Microbiology, 2008)

Sea level and geostrophic current features from tandem TOPEX/Poseidon‐Jason data in the Newfoundland offshore - G. Han; J. Li (International Journal of Remote Sensing, 2008)

Carnivory and active hunting by the planktonic testate amoeba Difflugia tuberspinifera - Bo-Ping Han; Tian Wang; Qiu-Qi Lin; Henri J. Dumont (Hydrobiologia, 2008)

Genotypic differences in leaf biochemical, physiological and growth responses to ozone in 20 winter wheat cultivars released over the past 60 years - D. K. BISWAS; H. XU; Y. G. LI; J. Z. SUN; X. Z. WANG; X. G. HAN; G. M. JIANG (Global Change Biology, 2008)
Ozone (O 3 ) concentrations in periurban areas in East Asia are sufficiently high to decrease crop yield. However, little is known about the genotypic differences in O 3 sensitivity in winter wheat in relation to year of cultivar release. This paper reports genotypic variations in O 3 sensitivity in 20 winter wheat cultivars released over the past 60 years in China highlighting O 3 ‐induced mechanisms. Wheat plants were exposed to elevated O 3 (82 ppb O 3 , 7 h day −1 ) or charcoal‐filtered air ( 3 ) for 21 days in open top chambers. Responses to O 3 were assessed by the levels of antioxidative activities, protein alteration, membrane lipid peroxidation, gas exchange, leaf chlorophyll, dark respiration and growth. We found that O 3 significantly reduced foliar ascorbate (−14%) and soluble protein (−22%), but increased peroxidase activity (+46%) and malondialdehyde (+38%). Elevated O 3 depressed light saturated net photosynthetic rate (−24%), stomatal conductance (−8%) and total chlorophyll (−11%), while stimulated dark respiration (+28%) and intercellular CO 2 concentration (+39%). O 3 also reduced overall plant growth, but to a greater extent in root (−32%) than in shoot (−17%) biomass. There was significant genotypic variation in potential sensitivity to O 3 that did not correlate to observed O 3 tolerance. Sensitivity to O 3 in cultivars of winter wheat progressed with year of release and correlated with stomatal conductance and dark respiration in O 3 ‐exposed plants. O 3 ‐induced loss in photosynthetic rate was attributed primarily to impaired activity of mesophyll cells and loss of integrity of cellular membrane as evidenced by increased intercellular CO 2 concentration and lipid peroxidation. Our findings demonstrated that higher sensitivity to O 3 in the more recently released cultivars was induced by higher stomatal conductance, larger reduction in antioxidative capacity and lower levels of dark respiration leading to higher oxidative damage to proteins and integrity of cellular membranes.

Assessment of Human Immune Response to Mutans Streptococcal Glucosyltransferase Peptides Selected by MHC Class II Binding Probability - Shauna Culshaw; Xiaozhe Han; Karen La Rosa; Jean W. Eastcott; Daniel J. Smith; Martin A. Taubman (International Journal of Peptide Research and Therapeutics, 2007)

Characteristics of reactive nitrogen compounds and other relevant trace gases in the atmosphere at urban and rural areas of Korea during May–June, 2004 - Z.-H. Shon; G. Lee; S.-K. Song; M. Lee; J. Han; D. Lee (Journal of Atmospheric Chemistry, 2007)

Tobacco cultivars vary in induction of systemic resistance against Cucumber mosaic virus and growth promotion by Pseudomonas chlororaphis O6 and its gacS mutant - Choong-Min Ryu; Beom Ryong Kang; Song Hee Han; Song Mi Cho; Joseph W. Kloepper; Anne J. Anderson; Young Cheol Kim (European Journal of Plant Pathology, 2007)

A novel gene, Pi40(t), linked to the DNA markers derived from NBS-LRR motifs confers broad spectrum of blast resistance in rice - J. U. Jeung; B. R. Kim; Y. C. Cho; S. S. Han; H. P. Moon; Y. T. Lee; K. K. Jena (Theoretical and Applied Genetics, 2007)

Utilization of seagrass habitats by juvenile groupers and snappers in Banten Bay, Banten Province, Indonesia - Siti Nuraini; Eira C. Carballo; Wim L. T. van Densen; Marcel A. M. Machiels; Han J. Lindeboom; Leopold A. J. Nagelkerke (Hydrobiologia, 2007)

Monitoring of Aerial Pollutants Emitted from Swine Houses in Korea - Ki Y. Kim; Han J. Ko; Hyeon T. Kim; Yoon S. Kim; Young M. Roh; Cheol M. Lee; Chi N. Kim (Environmental Monitoring and Assessment, 2007)

The reference genetic linkage map for the multinational Brassica rapa genome sequencing project - Su Ryun Choi; Graham R. Teakle; Prikshit Plaha; Jeong Hee Kim; Charlotte J. Allender; Elena Beynon; Zhong Yun Piao; Pilar Soengas; Tae Ho Han; Graham J. King; Guy C. Barker; Paul Hand; et al. (Theoretical and Applied Genetics, 2007)

Nonadditive effects of litter mixtures on decomposition and correlation with initial litter N and P concentrations in grassland plant species of northern China - Ping Liu; Osbert J. Sun; Jianhui Huang; Linghao Li; Xingguo Han (Biology and Fertility of Soils, 2007)

Changes of chemical and nutrient composition of porcine blood during fermentation by Aspergillus oryzae - J. Z. Wang; M. Zhang; F. Z. Ren; B. Z. Han; L. Wang; S. W. Chen; A. Humera (World Journal of Microbiology and Biotechnology, 2007)

Redirecting retroviral tropism by insertion of hepatitis B virus PreS1 core peptide into the envelope - P. Qi; J.-X. Han; Y.-Q. Lu; C.-X. Wang (Archives of Virology, 2007)

Gene expression profiling reveals two separate mechanisms regulating apoptosis in rectal carcinomas in vivo - Elza C. de Bruin; Simone van de Pas; Cornelis J. H. van de Velde; J. Han J. M. van Krieken; Lucy T. C. Peltenburg; Corrie A. M. Marijnen; Jan Paul Medema (Apoptosis, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Reusable immunomagnetic beads in an enzyme immunoassay - F. C. Han; J. Luo; H. F. Guo; W. H. Zhang; D. C. He; X. J. Yan (World Journal of Microbiology and Biotechnology, 2007)

Importance of point sources on regional nitrous oxide fluxes in semi-arid steppe of Inner Mongolia, China - J. Holst; C. Liu; Z. Yao; N. Brüggemann; X. Zheng; X. Han; K. Butterbach-Bahl (Plant and Soil, 2007)

Effect of Cadmium in Feed on Organs and Meat Colour of Growing Pigs - Y.-J. Tu; X.-Y. Han; Z.-R. Xu; Y.-Z. Wang; W.-F. Li (Veterinary Research Communications, 2007)

Effects of boundary-layer stability on urban heat island-induced circulation - J.-J. Baik; Y.-H. Kim; J.-J. Kim; J.-Y. Han (Theoretical and Applied Climatology, 2007)

Manganese superoxide dismutase polymorphism and risk of skin cancer (United States) - Jiali Han; Graham A. Colditz; David J. Hunter (Cancer Causes & Control, 2007)

Approaching chickpea quantitative trait loci conditioning resistance to Ascochyta rabiei via comparative genomics - X. Y. Bian; R. Ford; T. R. Han; T. E. Coram; E. C. K. Pang; P. W. J. Taylor (Australasian Plant Pathology, 2007)

Removal of Alachlor and Pretilachlor by Laboratory-Synthesized Zerovalent Iron in Pesticide Formulation Solution - H. Y. Kim; I. K. Kim; J. H. Shim; Y.-C. Kim; T.-H. Han; K.-C. Chung; P. I. Kim; B.-T. Oh; I. S. Kim (Bulletin of Environmental Contamination and Toxicology, 2006)

Soil Nitrification and Denitrification Potentials in a Wheat Field Soil as Affected by Elevated Atmospheric CO2 and Rice Straw Incorporation - Y. Shi; S. Y. Wang; L. Han; J. Yue; L. X. Yang; Y. L. Wang; J. G. Zhu (Bulletin of Environmental Contamination and Toxicology, 2006)

Cloning of ATP‐dependent protease ClpXP genes in Aeromonas veronii - H‐J Han; H Kondo; G Vivekanandhan; I Hirono; T Aoki (Journal of Fish Diseases, 2006)

Pathogenicity of Edwardsiella tarda to olive flounder, Paralichthys olivaceus (Temminck & Schlegel) - H‐J Han; D‐H Kim; D‐C Lee; S‐M Kim; S‐I Park (Journal of Fish Diseases, 2006)
The LD 50 and cytotoxic and enzymatic activities of both cells and extracellular products (ECPs) of eight Edwardsiella tarda strains were determined and their bacterial superoxide dismutase gene (sodB) and catalase gene (katB) were sequenced. Strains were also examined for their ability to resist the immune responses of olive flounder, Paralichthys olivaceus . LD 50 values of strains (FSW910410, KE1, 2, 3, 4, 5 and 6) in olive flounder ranged between 10 2.5 and 10 5.3 cfu (colony forming units) per fish. Unlike the avirulent strain SU100 (LD 50 ≥ 10 7 ), all pathogenic strains were able to survive in flounder serum and head kidney leucocytes (except for KE2). The virulent strains possessed type I sodB and katB, whereas SU100 had type II sodB but not katB. However, there was no difference between avirulent and virulent strains in haemolytic and cytotoxic activities. The results of this study demonstrated that the ability of E. tarda to resist complement activity and phagocytosis is conferred by its superoxide dismutase and catalase, which thus play an essential role in the pathogenicity of this bacterium. In addition genotyping of sodB and kat B proved to be a very useful tool to distinguish virulent from avirulent strains.

Extent and pattern of DNA methylation alteration in rice lines derived from introgressive hybridization of rice and Zizania latifolia Griseb - Z. Y. Dong; Y. M. Wang; Z. J. Zhang; Y. Shen; X. Y. Lin; X. F. Ou; F. P. Han; B. Liu (Theoretical and Applied Genetics, 2006)

Complete assignment of the chromosomes of Gossypium hirsutum L. by translocation and fluorescence in situ hybridization mapping - Kai Wang; Xianliang Song; Zhiguo Han; Wangzhen Guo; John Z. Yu; Jing Sun; Jiaju Pan; Russell J. Kohel; Tianzhen Zhang (Theoretical and Applied Genetics, 2006)

Production of Indole-3-Acetic Acid in the Plant-Beneficial Strain Pseudomonas chlororaphis O6 Is Negatively Regulated by the Global Sensor Kinase GacS - Beom Ryong Kang; Kwang Yeol Yang; Baik Ho Cho; Tae Ho Han; In Seon Kim; Myung Chul Lee; Anne J. Anderson; Young Cheol Kim (Current Microbiology, 2006)

Genetic diversity of avian infectious bronchitis coronavirus strains isolated in China between 1995 and 2004 - S. W. Liu; Q. X. Zhang; J. D. Chen; Z. X. Han; X. Liu; L. Feng; Y. H. Shao; J. G. Rong; X. G. Kong; G. Z. Tong (Archives of Virology, 2006)

Leaching of Copper from an Industrial Sludge Applied on a Soil Column - J. Xu; S. Dai; X. Han; S. Sun; P. Zhang (Bulletin of Environmental Contamination and Toxicology, 2006)

N-acetylphytosphingosine-induced apoptosis of Jurkat cells is mediated by the conformational change in Bak - Y. Han; Y. Kim; H. Kang; S. H. Hong; Y. H. Kim; D. -S. Lim; C. Park; Y. -S. Yun; J. -Y. Song (Apoptosis, 2006)

Pioglitazone, a synthetic ligand for PPARγ, induces apoptosis in RB-deficient human colorectal cancer cells - C. J. Lee; J. S. Han; C. Y. Seo; T. H. Park; H. C. Kwon; J. S. Jeong; I. H. Kim; J. Yun; Y. S. Bae; J. Y. Kwak; J. I. Park (Apoptosis, 2006)

Interactions Between High pH and Iron Supply on Nodulation and Iron Nutrition of Lupinus albus L. Genotypes Differing in Sensitivity to Iron Deficiency - C. Tang; S. J. Zheng; Y. F. Qiao; G. H. Wang; X. Z. Han (Plant and Soil, 2006)

Radon distribution in groundwater of Taiwan - Y. L. Han; M. C. Tom Kuo; K. C. Fan; C. J. Chiang; Y. P. Lee (Hydrogeology Journal, 2006)

Delineating the northern part of the Socotra Basin, offshore Korea, using marine magnetics - M. Suh; T. F. Abdallatif; J. Han; S. Choi; J. Oh (Geo-Marine Letters, 2005)

Leaching Behavior of Copper (II) in a Soil Column Experiment - J. Xu; X. Han; S. Sun; F. Meng; S. Dai (Bulletin of Environmental Contamination and Toxicology, 2005)

The Oryza Map Alignment Project: The Golden Path to Unlocking the Genetic Potential of Wild Rice Species - Rod A. Wing; Jetty S. S. Ammiraju; Meizhong Luo; HyeRan Kim; Yeisoo Yu; Dave Kudrna; Jose L. Goicoechea; Wenming Wang; Will Nelson; Kiran Rao; Darshan Brar; Dave J. Mackill; et al. (Plant Molecular Biology, 2005)

Seasonal Variation of Chemical Composition in Fine Particles at Gosan, Korea - J. S. Han; K. J. Moon; B. J. Kong; S. J. Lee; J. E. Kim; Y. J. Kim (Environmental Monitoring and Assessment, 2005)

Arsenic, Cadmium, Chromium, Cobalt, and Copper in Different Types of Chinese Tea - W.-Y. Han; Y.-Z. Shi; L.-F. Ma; J.-Y. Ruan (Bulletin of Environmental Contamination and Toxicology, 2005)

Inhibiting the Sexual Behavior of Female Cotton Bollworm Helicoverpa armigera - W. X. Dong; B. Y. Han; J. W. Du (Journal of Insect Behavior, 2005)

Trends of summer dry spells in China during the late twentieth century - D.-Y. Gong; J.-A. Wang; H. Han (Meteorology and Atmospheric Physics, 2005)

Agrobacterium-mediated transformation of bottle gourd (Lagenaria siceraria Standl.) - J.-S. Han; C. K. Kim; S. H. Park; K. D. Hirschi; I.- G. Mok (Plant Cell Reports, 2005)

Effects of Acid Precipitation and Aluminum on Carbohydrate Metabolism in Mycorrhizae of Pinus massioniana - J. K. Tan; F. X. Kong; H. S. Cao; Y. Yu; X. B. Han (Bulletin of Environmental Contamination and Toxicology, 2005)

Time Course Biochemical Responses of Green Algae Scenedesmus obliquus to Aluminum and Low pH - S. A. Jusu; F. X. Kong; B. Q. Qing; J. K. Tan; X. B. Han (Bulletin of Environmental Contamination and Toxicology, 2004)

Efficient plant regeneration from cotyledon explants of bottle gourd (Lagenaria siceraria Standl.) - J-S. Han; D-G. Oh; I-G. Mok; H-G. Park; C. K. Kim (Plant Cell Reports, 2004)

Mutational analysis of OGG1, MYH, MTH1 in FAP, HNPCC and sporadic colorectal cancer patients: R154H OGG1 polymorphism is associated with sporadic colorectal cancer patients - I.-J. Kim; J.-L. Ku; H. C. Kang; J.-H. Park; K.-A. Yoon; Y. Shin; H.-W. Park; S. G. Jang; S.-K. Lim; S. Y. Han; Y.-K. Shin; M. R. Lee; et al. (Human Genetics, 2004)

Use of Pi5(t) markers in marker-assisted selection to screen for cultivars with resistance to Magnaporthe grisea - G. Yi; S.-K. Lee; Y.-K. Hong; Y.-C. Cho; M.-H. Nam; S.-C. Kim; S.-S. Han; G.-L. Wang; T.-R. Hahn; P.C. Ronald; J.-S. Jeon (Theoretical and Applied Genetics, 2004)

Experimental investigation of the mammary gland tumour phantom for multifrequency microwave radio-thermometers - J. W. Lee; S. M. Lee; K. S. Kim; W. T. Han; G. Yoon; L. A. Pasmanik; I. A. Ulyanichev; A. V. Troitsky (Medical & Biological Engineering & Computing, 2004)

Bacterial enteritis and the development of the larval digestive tract in olive flounder, Paralichthys olivaceus (Temminck & Schlegel) - D‐H Kim; H‐J Han; S‐M Kim; D‐C Lee; S‐I Park (Journal of Fish Diseases, 2004)
Three bacterial isolates obtained from diseased olive flounder larvae, Paralichthys olivaceus , were identified as Vibrio ichthyoenteri based on the results of phenotypic characterization and 16S rRNA gene sequencing studies. Bacterial enteritis was reproduced in 16 and 22 days post‐hatch (dph) larvae by administering brine shrimp nauplii, Artemia salina , dosed with the environmental isolates and reference strains of V. ichthyoenteri . To investigate the effect of the disease on development of the stomach, a pepsin activity assay and reverse transcription‐polymerase chain reaction (RT‐PCR) analysis of the expression of the pepsinogen gene were performed. Expression of olive flounder pepsinogen was detected from 30‐dph larvae and the increased level of pepsin activity coincided with reduced susceptibility to the disease. Growth rates of V. ichthyoenteri , V. anguillarum and Edwardsiella tarda were tested in artificial stomach conditions using HCl and porcine pepsin. All the strains of V. ichthyoenteri were inhibited by low pH conditions which corresponded with an increase in pepsin levels. This suggests that differentiation of the stomach in olive flounder larvae and juveniles, an essential physiological development, also provides the host with a non‐immunological defence mechanism.

Estimates of CO 2 uptake and release among European forests based on eddy covariance data - Albert I. J. M. Van Dijk; A. J. (HAN) Dolman (Global Change Biology, 2004)
The net ecosystem exchange (NEE) of forests represents the balance of gross primary productivity (GPP) and respiration (R). Methods to estimate these two components from eddy covariance flux measurements are usually based on a functional relationship between respiration and temperature that is calibrated for night‐time (respiration) fluxes and subsequently extrapolated using daytime temperature measurements. However, respiration fluxes originate from different parts of the ecosystem, each of which experiences its own course of temperature. Moreover, if the temperature–respiration function is fitted to combined data from different stages of biological development or seasons, a spurious temperature effect may be included that will lead to overestimation of the direct effect of temperature and therefore to overestimates of daytime respiration. We used the EUROFLUX eddy covariance data set for 15 European forests and pooled data per site, month and for conditions of low and sufficient soil moisture, respectively. We found that using air temperature (measured above the canopy) rather than soil temperature (measured 5 cm below the surface) yielded the most reliable and consistent exponential ( Q 10 ) temperature–respiration relationship. A fundamental difference in air temperature‐based Q 10 values for different sites, times of year or soil moisture conditions could not be established; all were in the range 1.6–2.5. However, base respiration ( R 0 , i.e. respiration rate scaled to 0°C) did vary significantly among sites and over the course of the year, with increased base respiration rates during the growing season. We used the overall mean Q 10 of 2.0 to estimate annual GPP and R. Testing suggested that the uncertainty in total GPP and R associated with the method of separation was generally well within 15%. For the sites investigated, we found a positive relationship between GPP and R, indicating that there is a latitudinal trend in NEE because the absolute decrease in GPP towards the pole is greater than in R.

Fine mapping of a malting-quality QTL complex near the chromosome 4H S telomere in barley - W. Gao; J. A. Clancy; F. Han; B. L. Jones; A. Budde; D. M. Wesenberg; A. Kleinhofs; S. E. Ullrich (Theoretical and Applied Genetics, 2004)

Identification and molecular modelling of a mutation in the motor head domain of myosin VIIA in a family with autosomal dominant hearing impairment (DFNA11) - Mirjam W. J. Luijendijk; Erwin van Wijk; Anne M. L. C. Bischoff; Elmar Krieger; Patrick L. M. Huygen; Ronald J. E. Pennings; Han G. Brunner; Cor W. R. J. Cremers; Frans P. M. Cremers; Hannie Kremer (Human Genetics, 2004)

Development of Oligonucleotide Primers for the Detection of Harmful Microcystis in Water - J.-E. Cho; S.-W. Bang; M.-S. Han (Bulletin of Environmental Contamination and Toxicology, 2004)

Characteristics of Ion Components and Trace Elements of Fine Particles at Gosan, Korea in Spring time from 2001 to 2002 - J. S. Han; K. J. Moon; J. Y. Ahn; Y. D. Hong; Y. J. Kim; S. Y. Ryu; S. S. Cliff; T. A. Cahill (Environmental Monitoring and Assessment, 2004)

Infections by the Yeast Kodomaea ( Pichia ) ohmeri : Two Cases and Literature Review - X. Y. Han; J. J. Tarrand; E. Escudero (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Nitrous Oxide Emission and Urease Activity in Wheat - H. Bai; Y. Zhang; J. Han; C. Li (Bulletin of Environmental Contamination and Toxicology, 2003)

Effect of temperature on the pathogenicity of entomopathogenic nematodes (Steinernema and Heterorhabditis spp.) to Delia radicum - S. Chen; J. Li; X. Han; M. Moens (BioControl, 2003)

Some technical aspects of magnetic stimulation coil design with the ferromagnetic effect - B. H. Han; S. Y. Lee; J. H. Kim; J. H. Yi (Medical & Biological Engineering & Computing, 2003)

Molecular dissection of a dormancy QTL region near the chromosome 7 (5H) L telomere in barley - W. Gao; J. A. Clancy; F. Han; D. Prada; A. Kleinhofs; S. E. Ullrich (Theoretical and Applied Genetics, 2003)

Novel types of mutation in the choroideremia (CHM) gene: a full-length L1 insertion and an intronic mutation activating a cryptic exon - José A. J. M. van den Hurk; Dorien J. R. van de Pol; Bernd Wissinger; Marc A. van Driel; Lies H. Hoefsloot; Ilse J. de Wijs; L. Ingeborgh van den Born; John R. Heckenlively; Han G. Brunner; Eberhart Zrenner; Hans-Hilger Ropers; Frans P. M. Cremers (Human Genetics, 2003)

Recognition and implication of tectonic loading-induced reheating in the northern Variscan front (Belgium and northern France), based on an illite Kbler index and oxygen isotope study - G. Han; J. Yans; M. Goudalier; F. Lacquement; R. M. Corfield; J. L. Mansy; F. Boulvain; A. Prat (International Journal of Earth Sciences, 2003)

Distribution and Sources of PAHs in Saemangeum Reclaimed Tidal Lands of Central Korea - J. Y. Cho; K. W. Han; J. H. Kim; J. K. Son; K. S. Yoon (Bulletin of Environmental Contamination and Toxicology, 2003)

Application of an Enhanced Electrokinetic Ion Injection System to Bioremediation - S. S. Kim; S. J. Han (Water, Air, & Soil Pollution, 2003)

Helix 6 of tBid is necessary but not sufficient for mitochondrial binding activity - X. Hu; Z. Han; J. H. Wyche; E. A. Hendrickson (Apoptosis, 2003)

Predicting atmospheric biases for real-time ambiguity resolution in GPS/GLONASS reference station networks - L. Dai; J. Wang; C. Rizos; S. Han (Journal of Geodesy, 2003)

Quaternary reactivation of Tertiary faults in the southeastern Korean Peninsula: Age constraint by optically stimulated luminescence dating - Jin‐Han Ree; Young‐Joon Lee; Ed J. Rhodes; Youngdo Park; Sung‐Tack Kwon; Ueechan Chwae; Jeong‐Soo Jeon; Bongjoo Lee (Island Arc, 2003)
Two groups of Quaternary faults occur in the southeastern Korean Peninsula. The first group is north‐northeast‐striking, high‐angle dextral strike–slip faults. The second group is north‐northeast‐striking, low‐angle reverse faults that represent the reactivation of the pre‐existing normal faults. Optically stimulated luminescence dating of Quaternary sediments cut by one of the reverse faults constrains the faulting age to post‐32 Ka. These faults seem to be capable of further slip under the current tectonic stress regime, as determined by recent earthquake events in northeast Asia. Therefore, the traditional concept that the southeastern Korean Peninsula is seismically stable should be reappraised.

River Flow Modelling Using Fuzzy Decision Trees - D. Han; I. D. Cluckie; D. Karbassioun; J. Lawry; B. Krauskopf (Water Resources Management, 2002)

Right Stereoisomers for Sex Pheromone Components of the Apple Leafminer, Lyonetia prunifoliella, in Korea - J. H. Park; K. S. Han; K. Mori; K. S. Boo (Journal of Chemical Ecology, 2002)

Predicting Blood–Brain Barrier Partitioning of Organic Molecules Using Membrane–Interaction QSAR Analysis - Manisha Iyer; Rama Mishra; Yi Han; A. J. Hopfinger (Pharmaceutical Research, 2002)

A Distinct Subclass of Mammalian Striated Myosins: Structure and Molecular Evolution of "Superfast" or Masticatory Myosin Heavy Chain - Han Qin; Michael K.H. Hsu; Brian J. Morris; Joseph F.Y. Hoh (Journal of Molecular Evolution, 2002)

The complete nucleotide sequence of Beet black scorch virus (BBSV), a new member of the genus Necrovirus - Y. Cao; Z. Cai; Q. Ding; D. Li; C. Han; J. Yu; Y. Liu (Archives of Virology, 2002)

Perturbations of Population Growth in a Microcosm by Industrial Metal Plating and Ice Cream Mills Wastewater and Landfill Leachate - S.-U. Wui; K. Cho; Y. Inamori; J.-S. Lee; M.-S. Han; J.-B. Lee (Bulletin of Environmental Contamination and Toxicology, 2002)

Mass production of Siberian ginseng plantlets through large-scale tank culture of somatic embryos - Choi Y.-E.; Lee K.-S.; Kim E.-Y.; Kim Y.-S.; Han J.-Y.; Kim H.-S.; Jeong J.-H.; Ko S.-K. (Plant Cell Reports, 2002)

Differential distribution of interneurons in the neural networks that control walking in the mudpuppy (Necturus maculatus) spinal cord - J. Cheng; K. Jovanovic; Y. Aoyagi; D. J. Bennett; Y. Han; R. B. Stein (Experimental Brain Research, 2002)

Pathogenicity and vaccine efficacy of a thymidine kinase gene deleted infectious laryngotracheitis virus expressing the green fluorescent protein gene - M. G. Han; C. H. Kweon; I. P. Mo; S. J. Kim (Archives of Virology, 2002)

Mutations in PATCHED-1, the receptor for SONIC HEDGEHOG, are associated with holoprosencephaly - Jeffrey E. Ming; Michelle E. Kaupas; Erich Roessler; Han G. Brunner; Mahin Golabi; Mustafa Tekin; Robert F. Stratton; Eva Sujansky; Sherri J. Bale; Maximilian Muenke (Human Genetics, 2002)

FURTHER CHARACTERIZATION OF BC3H1 MYOGENIC CELLS REVEALS LACK OF P53 ACTIVITY AND UNDEREXPRESSION OF SEVERAL P53 REGULATED AND EXTRACELLULAR MATRIX–ASSOCIATED GENE PRODUCTS - SANDRA B. SHARP; MARIA VILLALVAZO; MICKEY HUANG; RODOLFO GONZALEZ; IRANIA ALARCON; MATTHEW BAHAMONDE; DIANE M. D'AGOSTIN; SAGAR DAMLE; ALEX ESPINOSA; SEOG J. HAN; JESSICA LIU; PAULA NAVARRO; et al. (In Vitro Cellular & Developmental Biology - Animal, 2002)

Workshop on Bioanalytical Methods Validation for Macromolecules: Summary Report - Krys J. Miller; Ronald R. Bowsher; Abbie Celniker; Jacqueline Gibbons; Shalini Gupta; Jean W. Lee; Steve J. Swanson; Wendell C. Smith; Russell S. Weiner; Daan J. A. Crommelin; Ira Das; Binodh S. DeSilva; et al. (Pharmaceutical Research, 2001)

Physical and Chemical Properties of a Winter-Time Yellow Sand Event in Northeast Asia - B. G. Kim; J. Y. Ahn; H. R. Noh; C. J. Park; J. S. Han; S. U. Park (Water, Air, & Soil Pollution, 2001)

New Method to Calculate the N 2 Evolution from Mixed Venous Blood During the N 2 Washout - Decai Han; Duen-Ren Jeng; Julio C. Cruz; Xavier F. Flores; J. M. Mallea (Annals of Biomedical Engineering, 2001)

Accurate absolute GPS positioning through satellite clock error estimation - S.-C. Han; J. H. Kwon; C. Jekeli (Journal of Geodesy, 2001)

Identification of rice black-streaked dwarf fijivirus in maize with rough dwarf disease in China - S. Fang; J. Yu; J. Feng; C. Han; D. Li; Y. Liu (Archives of Virology, 2001)

Mutation analysis of subjects with 46, XX sex reversal and 46, XY gonadal dysgenesis does not support the involvement of SOX3 in testis determination - Han N. Lim; Gary D. Berkovitz; Ieuan A. Hughes; J. Ross Hawkins (Human Genetics, 2000)

Sequence variants and functional analysis of human papillomavirus type 16 E5 gene in clinical specimens - C.-H. Hsieh; Y.-P. Tsao; C.-H. Wang; C.-P. Han; J.-L. Chang; J.-Y. Lee; S.-L. Chen (Archives of Virology, 2000)

Physiological responses that account for the increased power output in speed skating using klapskates - Eveline A. M. Heijnsdijk; Jos J. de Koning; Gert de Groot; Maarten F. Bobbert; Han Houdijk (European Journal of Applied Physiology, 2000)

Physical mapping of the barley stem rust resistance gene rpg4 - A. Druka; D. Kudrna; F. Han; A. Kilian; B. Steffenson; D. Frisch; J. Tomkins; R. Wing; A. Kleinhofs (Molecular Genetics and Genomics, 2000)

An integrated genetic map of Populus deltoides based on amplified fragment length polymorphisms - R. L. Wu; Y. F. Han; J. J. Hu; J. J. Fang; L. Li; M. L. Li; Z. -B. Zeng (Theoretical and Applied Genetics, 2000)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

One-step polymerase chain reaction-based typing of Helicobacter pylori vacA gene: association with gastric histopathology - Shan-Rui Han; Thomas Schneider; Michael Loos; Sucharit Bhakdi; Markus J. Maeurer (Medical Microbiology and Immunology, 1999)

Degradation of chlorinated and brominated hydrocarbons by Methylomicrobium album BG8 - J. -I. Han; S. Lontoh; J. D. Semrau (Archives of Microbiology, 1999)

The nucleotide sequence of a Chinese isolate of wheat yellow mosaic virus and its comparison with a Japanese isolate - D. Li; L. Yan; N. Su; C. Han; Z. Hou; J. Yu; Y. Liu (Archives of Virology, 1999)

Genetic transformation of Cymbidium orchid by particle bombardment - J. Yang; H.-J. Lee; D. H. Shin; S. K. Oh; J. H. Seon; K. Y. Paek; K.-H. Han (Plant Cell Reports, 1999)

The Orientation of the Phosphorescence Dipole Moment of Erythrosine B Within Its Molecular Frame - M. P. Lettinga; E. M. Klarenbeek; Han Zuilhof; M. A. M. J. van Zandvoort (Journal of Fluorescence, 1999)

A mini binary vector series for plant transformation - Chengbin Xiang; Peng Han; Isabelle Lutziger; Kan Wang; David J. Oliver (Plant Molecular Biology, 1999)

QSAR for Polychlorinated Organic Compounds (PCOCs). I. Prediction of Partition Properties for PCOCs Using Quantum Chemical Parameters - J. Dai; C. Sun; S. Han; L. Wang (Bulletin of Environmental Contamination and Toxicology, 1999)

Isolation and mapping of the rabbit DM genes - E. Hermel; M. Han; Bishop Hague; Thomas Kindt; John J. Monaco (Immunogenetics, 1999)

Optimization of AFLP fingerprinting of organisms with a large-sized genome: a study on Alstroemeria spp. - T. H. Han; H. J. van Eck; M. J. De Jeu; E. Jacobsen (Theoretical and Applied Genetics, 1999)

In solium Selection for Arabidopsis Transformants Resistant to Kanamycin - Chengbin Xiang; Peng Han; David J. Oliver (Plant Molecular Biology Reporter, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Refined mapping of the gene for autosomal dominant retinitis pigmentosa (RP17) on chromosome 17q22 - A. I. den Hollander; S. D. van der Velde-Visser; Alfred J. L. G. Pinckers; Carel B. Hoyng; Han G. Brunner; Frans P. M. Cremers (Human Genetics, 1999)

Estimation of Target Hazard Quotients and Potential Health Risks for Metals by Consumption of Seafood in Taiwan - B.-C. Han; W. L. Jeng; R. Y. Chen; G. T. Fang; T. C. Hung; R. J. Tseng (Archives of Environmental Contamination and Toxicology, 1998)

Enhanced salidroside production in liquid-cultivated compact callus aggregates of Rhodiola sachalinensis: manipulation of plant growth regulators and sucrose - J. F. Xu; P. Q. Ying; A. M. Han; Z. G. Su (Plant Cell, Tissue and Organ Culture (PCTOC), 1998)

Response of The Lacewing Chrysopa cognata to Pheromones of its Aphid Prey - K. S. Boo; I. B. Chung; K. S. Han; J. A. Pickett; L. J. Wadhams (Journal of Chemical Ecology, 1998)

Influence of Different Fat Emulsion-Based Intravenous Formulations on the Pharmacokinetics and Pharmacodynamics of Propofol - Eugene H. Cox; Catherijne A. J. Knibbe; Victorine S. Koster; Mariska W. E. Langemeijer; Erica E. Tukker; Rogier Lange; Paul F. M. Kuks; Han J. M. Langemeijer; Loraine Lie-A-Huen; Meindert Danhof (Pharmaceutical Research, 1998)

Strategies for the improvement of salidroside production in cell suspension cultures of Rhodiola sachalinensis - J. F. Xu; C. B. Liu; A. M. Han; P. S. Feng; Z. G. Su (Plant Cell Reports, 1998)

cGMP facilitates calcium current via cGMP-dependent protein kinase in isolated rabbit ventricular myocytes - J. Han; Euiyong Kim; S. H. Lee; S. Yoo; Won-Kyung Ho; Y. E. Earm (Pflügers Archiv - European Journal of Physiology, 1998)

On the cutaneous receptors contributing to withdrawal reflex pathways in the decerebrate spinal rat - Han-Rong Weng; J. Schouenborg (Experimental Brain Research, 1998)

Rock-Shells ( Thais clavigera ) as an Indicator of As, Cu, and Zn Contamination on the Putai Coast of the Black-Foot Disease Area in Taiwan - B. C. Han; W. L. Jeng; M. S. Jeng; L. T. Kao; P. J. Meng; Y. L. Huang (Archives of Environmental Contamination and Toxicology, 1997)

Towards map-based cloning of the barley stem rust resistance genes Rpg1 and rpg4 using rice as an intergenomic cloning vehicle - A. Kilian; J. Chen; F. Han; B. Steffenson; A. Kleinhofs (Plant Molecular Biology, 1997)

Whole cell enzyme microencapsulation of Escherichia coli with oxygen-dependent inducible nar promoter - G.H. Seong; S.J. Han; H.N. Chang; J. Lee (Biotechnology Letters, 1997)

Chirp (2–7 kHz) echo characters in the Ulleung Basin - S. K. Chough; S. H. Lee; J. W. Kim; S. C. Park; D. G. Yoo; H. S. Han; S. H. Yoon; S. B. Oh; Y. B. Kim; G. G. Back (Geosciences Journal, 1997)

210 Pb-derived sediment accumulation rates in the southwestern East Sea (Sea of Japan) - G. H. Hong; S. H. Kim; C. S. Chung; D.-J. Kang; D.-H. Shin; H. J. Lee; S.-J. Han (Geo-Marine Letters, 1997)

Changes in late-embryogenesis-abundant (LEA) messenger RNAs and dehydrins during maturation and premature drying ofRicinus communis L. seeds - Bin Han; D. Wayne Hughes; Glenn A. Galau; J. Derek Bewley; Allison R. Kermode (Planta, 1997)

Cysteine ligand vibrations are responsible for the complex resonance Raman spectrum of azurin - Colin R. Andrew; Jane Han; Tanneke den Blaauwen; Gertie van Pouderoyen; Erik Vijgenboom; Gerard W. Canters; Thomas M. Loehr; J. Sanders-Loehr (JBIC Journal of Biological Inorganic Chemistry, 1997)

Effect of EHS matrix on expression of transgenes in HC11 cells - T. H. Lee; M. G. Baik; W. B. Im; C. S. Lee; Y. M. Han; S. J. Kim; K. K. Lee; Y. J. Choi (In Vitro Cellular & Developmental Biology - Animal, 1997)

Human Papillomavirus is More Prevalent in First Trimester Spontaneously Aborted Products of Conception Compared to Elective Specimens - P L Hermonat; L Han; P J Wendel; J G Quirk; S Stern; C L Lowery; T M Rechtin (Virus Genes, 1997)

Numerical bifurcation analysis of distance-dependent on-center off-surround shunting neural networks - Maartje E. J. Raijmakers; Han L. J. van der Maas; Peter C. M. Molenaar (Biological Cybernetics, 1996)

Effects of Liming on Uptake of Lead and Cadmium by Raphanus sativa - D.-H. Han; J.-H. Lee (Archives of Environmental Contamination and Toxicology, 1996)

Effects of liming on uptake of lead and cadmium by Raphanus sativa - D. -H. Han; J. -H. Lee (Archives of Environmental Contamination and Toxicology, 1996)

Mitochondrial DNA restriction map for the mediterranean fruit fly,Ceratitis capitata - Bruce A. McPheron; Gail E. Gasparich; Ho-Yeon Han; Gary J. Steck; Walter S. Sheppard (Biochemical Genetics, 1994)

A neural network algorithm for the multiple traveling salesmen problem - E. Wacholder; J. Han; R. C. Mann (Biological Cybernetics, 1989)

Nucleotide sequence of the human? 1-globin gene - J. M. Gonzalez-Redondo; I. S. Han; Y. -C. Gu; T. H. J. Huisman (Biochemical Genetics, 1988)

Mirex in human milk in upstate New York - B. Bush; J. Snow; S. Connor; L. Rueckert; Y. Han; P. Dymerski; D. Hilker (Archives of Environmental Contamination and Toxicology, 1983)

Regulation of amidase formation in mutants from Pseudomonas aeruginosa PAO lacking glutamine synthetase activity - Dick B. Janssen; Patricia M. Herst; Han M. L. J. Joosten; Chris van der Drift (Archives of Microbiology, 1982)

Nitrogen control in Pseudomonas aeruginosa: A role for glutamine in the regulation of the synthesis of NADP-dependent glutamate dehydrogenase, urease and histidase - Dick B. Janssen; Patricia M. Herst; Han M. L. J. Joosten; Chris van der Drift (Archives of Microbiology, 1981)

Effect of growth condition on enzymes of the citric acid cycle and the glyoxylate cycle in the photosynthetic bacterium Rhodopseudomonas palustris - J. H. Eley; K. Knobloch; T. -W. Han (Antonie van Leeuwenhoek, 1979)